Undesirable risks of ozone-resistant bacteria (ORB): biofilm formation potentials and control strategy - Hao-Bin Wang; Yin-Hu Wu; Yuan Bai; Zhuo Chen; Rui-Ning Wang; Han Liu; Nozomu Ikuno; Nakata Koji; Hong-Ying Hu (Water Research, 2026)

Developing radio frequency technology for enhancing the processing characteristics of gluten-free rice dough based on gelatinization degree - Dongsheng Hu; Yingqi Tian; Jiahong Yuan; Mengge Li; Rui Li; Shaojin Wang (Journal of Food Engineering, 2026)

A comprehensive evaluation of digestate gasification in biogas atmospheres towards the integration of anaerobic digestion and gasification - Rui Zhang; Zhuang Yuan; Hongru Li; Zhi Wang; Shengquan Zhou; Xiaochao Zhu; Zhanjun Cheng; Beibei Yan (Bioresource Technology, 2026)

Role of glutamine in promoting the proliferation and chondrogenic differentiation of ATDC5 cells: based on transcriptomic analysis - Rui-hao Zhang; Wen-huan Yuan; Ze-long Wang; Qi-rui Yang; Yi Sun; Quan-nian Shao; Wen-ji Wang; Jing Wang (Molecular Biology Reports, 2026)

Lateral impact performance of concrete-encased concrete-filled steel tubular (CECFST) members after exposure to fire: Tests and analysis - Yuan Zheng; Wen-Da Wang; Sun-Hang Ji; Yan-Li Shi; Wei Xian; Rui Wang (Engineering Structures, 2026)

Experimental and numerical study of diaphragm in-plane stiffness on the seismic performance of building structures with DCPCF - Yuan-yuan Sun; Rui Pang; Shu-ting Liang; Yi-ming Wen; Chun-lin Wang (Engineering Structures, 2026)

UPCRISPR: an ultrafast, one-tube multiplexed nucleic acid detection system for resolving the diagnostic gray zone in HPV16/18 detection - Linlin Bai; Dianwei Liu; Chunyan Qian; Weiqi Yuan; Kaiming Guo; Yao Wang; Feng Qian; Mingmin Shi; Bei Wang; Rui Wang (Analytica Chimica Acta, 2026)

Occurrence, detection methods, and remediation technologies of per- and polyfluoroalkyl substances (PFAS) in soils - Yina Ma; Kang Lei; Shuwen Xue; Yong Wang; ShunHao Ai; Changjian Shang; Kunlong Hui; Ying Yuan; Rui Meng; Yuting Zhao (Process Safety and Environmental Protection, 2026)

Microbiome dysbiosis and metabolic reprogramming in kiwifruit peel during Botrytis cinerea infection - Jingsheng Chen; Rui Ma; Yu Zhao; Yuan Sui; Zhuo Chen; Xianmei Xiao; Zhenshuo Wang; Jia Liu (Postharvest Biology and Technology, 2026)

Resistivity and acoustic emission responses during the loading failure process of frozen red clay - Ziyu Wang; Qiang Sun; Nianqin Wang; Jingjing Nan; Shaoli Liu; Yuan Xin; Rui Lyu; Shaofei Wang (Journal of Applied Geophysics, 2026)

Impacts of engineering activities on the permafrost environment in the Hola Basin in the Northern Da Xing'anling Mountains in Northeast China - Hongwei Wang; Xiaoying Li; Ruixia He; Juan Zhang; Wenhui Wang; Yuan Qi; Jinlong Zhang; Rui Yang; Yan Li; Xiaoying Jin; Shuai Huang; Jianjun Tang; et al. (Engineering Geology, 2026)

Enhanced degradation of sulfamethoxazole in dielectric barrier discharge plasma via Zn tetrahedral site doping-mediated d-band center engineering of CoFe2O4 - Xiaojing Wang; Rui Cao; Na Huang; Mengmeng Du; Mingyao Yuan; Jia Ma; Fan Zhang; Jiaqi Jiang; Zhenxing Zeng; Yanzong Zhang; Zhilin Li; Shihuai Deng (Chemical Engineering Journal, 2026)

Amplitude-controlled dynamic structural colors on wrinkling surfaces for facile multilevel strain-resolved optical encryption - Dengchong Feng; Shirui Wu; Yuxin Liu; Qi Guo; Rui Chen; Yu Chen; Yuzhao Yang; Haiqiang Wu; Zhiquan Zhao; Shaolin Lu; Zetong Ma; Cheng Wang; et al. (Chemical Engineering Journal, 2026)

A review of atmospheric black carbon research progress in China - Qi Zhou; Shunyao Wang; Shujun Bie; Junjie Cai; Yingjun Chen; Yuan Cheng; Xiang Ding; Jianwei Gu; Jie Li; Weijun Li; Dantong Liu; Jiaying Liu; et al. (Atmospheric Environment, 2026)

A lyophilized RPA–CRISPR/Cas13d one-pot platform for rapid detection of porcine circovirus type 3 - Li-Na Shao; Zheng-Luo; Bao-Ling Liu; Tong-Xu; Yuan-Meng Wang; Jia-Qi Duan; Lei-Zhao; You-You Li; Yang-Ming Dai; Qin-Rui Jia; Le-Yi Zhang; Ling-Zhu; et al. (Analytica Chimica Acta, 2026)

Kosakonia oryziphila KC516 mediated growth promotion of Cosmos bipinnatus in phosphogypsum by modulating rhizosphere geochemistry and root transcriptome - Jing Zhang; Hao-Tian Dong; Yuan-Chun Yang; Rui Liu; Shuai Wang; Ao-Li Zhang; Yuan Su; Ming-Hua Dong; Yan-Ru Cao; Hua-Li Zhang (Environmental Geochemistry and Health, 2026)

Environmental DNA metabarcoding complements bottom trawling and detects fish species beyond recorded ranges in the Chukchi Borderland, Central Arctic Ocean - Hai Li; Fang Yang; Xiang Zhang; Ran Zhang; Rui Wang; Xing Miao; Shigang Liu; Puqing Song; Yuan Li; Longshan Lin (Marine Environmental Research, 2026)

Corrigendum to “TBBPA induced hepatocyte ferroptosis by PCBP1-mediated ferritinophagy” [J Hazard Mater 494 (2025) 138515] - Rui-Qi Liu; Yu-Tong Wu; Yue Cheng; Yuan-Hang Chang; Muhammad Asmat Ullah Saleem; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2026)

Extracellular polymeric substances-mediated detoxification of roxarsone in anaerobic granular sludge: Molecular insights and the critical role of proteins - Yuxuan Wang; Guanbao Yao; Rui Tang; Lei Chen; Shoujun Yuan; Zhen-Hu Hu; Xinmin Zhan (Journal of Hazardous Materials, 2026)

Time-resolved structural remodeling and bioactivity changes of Lentinula edodes polysaccharides during fermentation by Limosilactobacillus fermentum CICC 21828 - Yue Liu; Saiqun Wang; Lu Liu; Zidan Zhao; Rui Cai; Jing Guo; Tianli Yue; Yahong Yuan; Zhouli Wang (Food Bioscience, 2026)

Constructing synthetic microbial communities containing Komagataeibacter spp. for kombucha production: Impacts on bioactive compounds, functionality and sensory profiles - Shiqi Li; Shuhui Hu; Yuhe Zhen; Lujie Chu; Xingnan Wang; Yahong Yuan; Tianli Yue; Rui Cai; Zhouli Wang (Food Microbiology, 2026)

CXCL8 is associated with aflatoxin B1–triggered injury and caspase-3 activation in porcine kidney epithelial PK15 cells: integrated transcriptomics and CRISPR/Cas9 knockout - Jianlin Yuan; Yuhan Ma; Jinfeng Li; Xizhu Chen; Yiping Wen; Rui Wu; Xinfeng Hang; Heng Huang; Senyan Du; Yiping Wang; Qi-Gui Yan; Xiaobo Huang; et al. (Food and Chemical Toxicology, 2026)

Simultaneous treatment of aquatic pesticides and microplastics onto hexagonal g-C3N4 nanotubes/AgCl@Ag with nitrogen vacancies: Removal activity and mutual effects - Leyi Huang; Rui Shan; Yuting Gan; Juhai Liu; Lun Lu; Yazhuo Wang; Libin Wu; Dong Liang; Haoran Yuan (Environmental Research, 2026)

Two-phase flow in clayey silt hydrate reservoirs drives migration and clogging of fine clay particles - Jiang Lei; Wei Guo; Yuan Wang; Wen Zhang; Huie Chen; Pengyu Zhang; Rui Jia (Engineering Geology, 2026)

A novel physics-driven remeshing technique for particle finite element method - Wen-Rui Sun; Ke-Jian Wang; Wen-Qi Guan; Xue Li; Wei Zhang; Wei-Hai Yuan (Computers and Geotechnics, 2026)

Entropy-driven engineering in AFe2O4 spinel enabling broadband microwave absorption - Xinglai Yuan; Wei Li; Qiancheng Gao; Fan Zhang; Ye Yuan; Xiaohan Wang; Yanqiu Zhu; Mi Tian; Hailong Wang; Rui Zhang; Biao Zhao; Qinghu Wang; et al. (Chemical Engineering Journal, 2026)

Diverse dynamical responses of a memristive bi-membrane photosensitive neuron model - Haotong Song; Ao Tan; Yuan Chai; Zhaojun Yan; Tingfang Wang; Rui Zhu (BioSystems, 2026)

Different drivers of active and inert carbon fraction on forest soil aggregate stability: a functional partitioning approach - Jing Lin; Rui Wang; Miao Xia; Jian-cong Zhang; Peng Qiu; Ke-xin Zhang; Bo Chang; Yu-lin Zhang; Tian-zi Xie; Yi Jian; Jia-yuan Wang; Shan-shan Guo (Journal of Soils and Sediments, 2026)

PTPσ mediates the integration of grafted neuronal tissueoids with host neural pathways after complete spinal cord injury - Rui Mao; Yuan-Huan Ma; Jin-Yuan Xiao; Qing-Shuai Wei; Yin-Chun Zhao; Qi-Xing Hu; Hou-Ge Li; Ke-Jun Zhang; Lai-Jian Wang; Hui-Juan Shi; Li-Zhi Peng; Jun-Hua Wang; et al. (Science China Life Sciences, 2026)

Species Divergence in Oxytocin-Dependent Yawning on a Conserved Glutamatergic Erection Circuit - Yan-Chu-Fei Zhang; Qing-Wu Zheng; Yang Lu; Hao-Yuan Wang; Jiao Cang; Xin-Rui Wu; Lin-Yao Fan; Liang Li; Ni-Na Zhang; Xiao-Yang Zhang; Jing-Ning Zhu; Jian Jing; et al. (Neuroscience Bulletin, 2026)
Yawning coupled with penile erection is a conserved neurobehavioral syndrome mediated by the paraventricular hypothalamus (PVH). However, the distinct roles of oxytocin and its co-transmitters remain unresolved. Using chemogenetics, we showed that activation of PVH oxytocin neurons was sufficient to elicit both responses, whereas silencing these neurons abolished them. Viral tracing revealed that these neurons project collaterally to the brainstem reticular nucleus and spinal cord to spatially coordinate autonomic and somatic motor outputs. By dissecting the molecular mechanisms using CRISPR-Cas9, we found that vesicular glutamate transporter 2 (VGLUT2)-dependent glutamatergic transmission provides the primary drive for both behaviors, whereas the oxytocin peptide is selectively required for yawning but dispensable for erection. Comparative analyses across rats, hamsters, and mice demonstrated that while the glutamatergic erectile circuit was conserved, mice lacked spontaneous yawning and were resistant to apomorphine-induced yawning. These findings suggest a hierarchical co-transmission framework in which fast glutamatergic signaling provides the core drive, while oxytocin confers behavioral specificity.

Microbe-mediated coupling of soil disease suppression and rhizobial symbiosis in legume diversified cropping systems - Xiang-Yu Zhang; Rui Yuan; Xue Guo; Wen-Xue Zhang; Hao-Ran Li; Cao-Yue Wu; Jun-Yu Zhao; Ting-Ting Zhang; Hong-Wei Wang; Ricardo A. R. Machado; Stefan Scheu; Yong Jia; et al. (Plant and Soil, 2026)

AGR2-high cells drive a FOXM1-mediated pro-malignancy program in non-functional pancreatic neuroendocrine tumors (NF-PanNETs) and informatively predict patient outcomes - Junya Peng; Rui Jiang; Jiajuan Tu; Wanli Liu; Lu Ping; Ruikang Dun; Wenyu Zhang; Hao Chen; Yihong Shi; Xu Pan; Panpan Jia; Mengjie Li; et al. (Science Bulletin, 2026)

Long-term changes in spatio-temporal heterogeneities of vegetation greenness and land surface temperature in China - Rui Yao; Yongjie Li; Tingting Ma; Minfeng Yuan; Zhihao Zhang; Siyuan Chen; Chuan Wang; Binghan Wang; Zhenyu Fu; Hengwei Li (Remote Sensing Applications: Society and Environment, 2026)

Groundwater-mediated controls and future projections of carbon stocks in coastal wetlands - Xulong Gong; Ying Liang; Xue Jiang; Rui Ma; Yuan Liu; Shun Hu; Yanxin Wang (Journal of Hydrology, 2026)

Compartment-specific host association and mobility shape ARG risk in aquaculture systems - Zhong-Quan Jiang; Rui-Kai Xing; Di Peng; Yuan-Hao Ren; Tian-Yi Wei; Wen-Bo Guo; Zhe-Min Shen; Chao-Nan Wang; Feng-Li Zhang; Tao Yuan (Journal of Hazardous Materials, 2026)

Effects of ultrasound, blanching, and ethanol pretreatments on drying characteristics, microstructure, and quality of apricots using hot air-assisted radio frequency energy - Jiahong Yuan; Dongsheng Hu; Qianjie Xiong; Rui Li; Liling Yang; Shaojin Wang (Innovative Food Science & Emerging Technologies, 2026)

The Ca-N-C ligand in the pyrolysis carbon-based single-atom catalyst enhance the olefin selectivity in the pyrolysis process of regenerated PP - Kaiwen Yun; Xixi Lian; Rui Shan; Guoqiang Wei; Shuxiao Wang; Haoran Yuan; Yong Chen (Biomass and Bioenergy, 2026)

A Process-based classification of meteorological mechanisms influencing airborne pollen concentrations in northern and northwestern China - Zining Yuan; Huiyu Ning; Xingqin An; Qingyu Wei; Defang Wei; Wenqiao Xue; Ning He; Lina Di; Xinli Yang; Ying Li; Rui Li; Hongjian Li; et al. (Atmospheric Research, 2026)

Cobalt Sites as Electron Transfer Hubs in Medium-entropy FeCoMnZnCu@NC: Driving Multi-site Cooperation for Efficient Singlet Oxygen Generation - Jia Ma; Mingyao Yuan; Rui Cao; Na Huang; Zhenxing Zeng; Yanzong Zhang; Shihuai Deng; Xiaojing Wang (Water, Air, & Soil Pollution, 2026)

Genetic dissection of a key dynamic growth period QTL for source–sink-related traits and its breeding application potential in wheat - Meng Yuan; Hongke Ding; Yunkai Yue; Chuanliang Zhang; Yuze Wang; Dandan Zhang; Shipeng Li; Ruiqi Nie; Jia Liu; Yanchuan Huang; Jinyu Han; Sufu Deng; et al. (Theoretical and Applied Genetics, 2026)

Analysis of Arbuscular Mycorrhizal Fungal Community in Soil of Sugarcane at Different Tillage Depths - Qun-Qing Huang; Sheng Wang; Ying-Jie Nong; Kai-Mao Zhong; Yi-Cheng Su; Xiao-Juan Qin; Jin-Lian Zhang; Yi-Hao Kang; Ting-Su Chen; Shi-Yuan Zeng; Xi-Chao Deng; Ming-Guo Jiang; et al. (Sugar Tech, 2026)

CRISPR/Cas9 system inhibits largemouth bass virus infection in vitro and in vivo - Rui-Long He; Mao-sheng He; Xin-Yuan Jiang; Yi-Wang; Hao-Liang; Xiang-Yi Bu; Kun Xu; Fei Ling; Gao-Xue Wang; Hai-Feng Jiang (Aquaculture, 2026)

Acute Stress Drives Adaptive Anxiety via Excitatory-Inhibitory Imbalance in the Prefrontal-Amygdala Circuit in Male Mice - Jia-Xin Zou; En Cao; Zhi-Hao Wang; Rui Han; Xing-Yan Lu; Cheng-Yuan Huang; Xia Qin; Wei-Zhu Liu; Wen-Hua Zhang; Bing-Xing Pan (Neuroscience Bulletin, 2026)

Cross-species comparative transcriptomic analysis of spermatozoa reveals species-specific regulatory networks linked to fertilization-associated genes in cattle, sheep and goats - Yue Zhao; Linfeng Bai; Qiqi Jiang; Hao Xiao; Fangyuan Liu; Bilige Wuyun; Rihan Wu; Chunxia Hao; Rui Ding; Peng Yuan; Lizhi Wang; Ying Lu; et al. (Science China Life Sciences, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

A nationwide analysis of hospitalised patients with lower respiratory infections in China: life-stage-specific pathogen spectra, co-detection networks, and sex disparities - Yamin Sun; Min Wang; Tian Qin; Jue Liu; Jiale Yuan; Pei Li; Xinchang Lun; Zhigang Wang; Linghang Wang; Rui Song; Xi Wang; Ronghua Jin; et al. (Science Bulletin, 2026)

A root cause diagnosis strategy based on error correction instantaneous granger causality algorithm for non-stationary industrial processes - Rui Chen; Yuan-Qiang Zhou; Li-Lan Liu; Jian-Guo Wang; Yuan Yao; Chen Peng (Process Safety and Environmental Protection, 2026)

Undescribed triterpenoid ellagitannins from Castanopsis calathiformis and their potential antiproliferative and hypoglycemic activity - Ya-feng Wang; Ying-rong Bao; Rui-jie He; Nao Pang; Zhang-bin Liu; Bing-yuan Yang; Gui-qin Li; Yong-lin Huang (Phytochemistry, 2026)

A new pathway to enhance the oceanic carbon sink: inorganic carbonate precipitation driven by calcium–alkali coupling - Shan Shan Liu; Jin Ming Song; Xue Gang Li; Hua Mao Yuan; Li Qin Duan; Jun Lei Li; Bao Xiao Qu; Qi Dong Wang; Jun Ma; Jian Wei Xing; Zhi Bo Wang; Rui Wang; et al. (Journal of Environmental Management, 2026)

Integrative multi-omics combined with molecular docking and molecular dynamics simulations elucidates the mechanism driving the transition from green notes to fruity aroma during musang king durian ripening - Zhongyan Li; Tianci Yan; Bin Xu; Xulu Luo; Yumei Ding; Wei Fan; Qin Qiao; Shaojie Yuan; Hui Guo; Meng Zhang; Yan Zhao; Rui Wang; et al. (Food Research International, 2026)

Distinct differences of rice grain quality caused by developmental stage and cultivar: A widely targeted metabolomics perspective - Xuexia Yuan; Pingxiang Liu; Rui Gao; Jingxiu Bi; Tong Zhao; Haining Hao; Xia Li; Yutao Wang (Food Chemistry, 2026)

Engineered MBene-integrated anisotropic aerogel with synergistic hydrogen-bond network and superior photothermal conversion for efficient solar-driven desalination and purification - Xinyi Wang; Rongtao Zheng; Cuilian Wen; Lijin Luo; Jiansen Wen; Haonan Zhao; Rui Xiong; Frank Marken; Yin Yuan; Baisheng Sa (Desalination, 2026)

Lymph node–targeting GM-CSF vesicles produced in situ by ultrasound-activated bacterial factories for enhanced immunotherapy - Yue Yuan; Beibei Zhang; Shaobo Duan; Ruiqing Liu; Juan Zhang; Rui Zhang; Qi Zhou; Linlin Zhang; Xiaoxia Xu; Zesheng Li; Yuanyuan Liu; Xiaoxiao Li; et al. (Chemical Engineering Journal, 2026)

Spatial and environmental niche differentiation facilitates sympatric macaques' coexistence in montane-canyon landscapes: Implications for conservation - Wei Zhou; Yuan Wang; Deyan Ge; Qisen Yang; Gang Song; Jilong Cheng; Tian Tian; Yu Zhang; Jinbo Xu; Ying Liu; Weibo Wang; Xiaochuan Wang; et al. (Biological Conservation, 2026)

An approach for detecting hemodynamic parameters in the carotid arterial system based on the priori relationship between blood pressure and arterial radius - Jin Wang; Yong-Jiang Li; Yu-Yuan Zhang; Jing-Rui Gu; Xian-Wei Wang; Dong Chen; Kai-Rong Qin (Medical & Biological Engineering & Computing, 2026)

Sex-specific alterations of intrinsic brain activity and functional connectivity in adolescent obsessive-compulsive disorder - Mingming Li; Xiaochi Yuan; Chenchen Zhang; Rui Li; Bin Wang; Kun Li (Medical & Biological Engineering & Computing, 2026)

Intensifying ocean stratification reduces vertical phosphate supply and carbon sink magnitude - Rui Wang; Xuegang Li; Jinming Song; Zhibo Wang; Shanshan Liu; Guorong Zhong; Yanjun Wang; Jun Ma; Huamao Yuan; Liqin Duan (Limnology and Oceanography, 2026)
In recent decades, global warming‐driven ocean stratification has profoundly affected nutrient cycling. As the largest marginal sea in the northwestern Pacific, the South China Sea (SCS) provides a representative setting to examine these responses. Based on two decades of temperature, salinity, and nutrient datasets, we quantified the evolution of stratification in the SCS, its impacts on the upward transport of deep‐water phosphate (PO 4 3− ), and the resulting changes in carbon sink. Results show an increasing intensification of stratification, with an upward shift of the thermocline's upper boundary, a downward shift of its lower boundary, increased thickness, and weakened vertical mixing. Despite enhanced external inputs from rivers and atmospheric deposition and reduced phytoplankton consumption of PO 4 3− in the mixed layer, PO 4 3− concentrations have declined persistently, indicating a substantial reduction in nutrient flux from the deep water across the thermocline into the surface layer. The minimum net reduction of PO 4 3− in the upper water column (mixed layer plus thermocline) was −0.047 Gmol·yr −1 . This decline in PO 4 3− supply constrained primary production and reduced CO 2 uptake, leading to an estimated carbon sink reduction of 2.21 × 10 5 t CO 2 ·yr −1 in the SCS.

ERK1/2 activation in anti-inflammatory effects and underlying signaling mechanisms - Kaiwen Tao; Lin Xu; Chao Cheng; Fukang Yuan; Yicheng Yu; Lidan Zhang; Runmin Li; Rui Xia; Haibei Dong; Xingqi Wang (Inflammation Research, 2026)

Influence of Rate Effects on Fracture-Induced Opening of Interlayer Branch Fractures - Wen-rui Wang; Zong-qing Zhou; Hua-qing Ma; Xue-lin Zheng; Lei Chen; Cheng-lu Gao; Zhi-yuan Liu (Rock Mechanics and Rock Engineering, 2026)

Dihydromyricetin attenuates LPS-induced liver injury in chicks through the JNK signaling pathway - Lina Jia; Jiarui Liu; Zhenghua Ji; Liang Yuan; Yingchao Gong; Xinru Jiang; Xianan Fan; Changwen Li; Rui Li; Haoran Wang; Fangping Liu (Research in Veterinary Science, 2026)

Lignin-based sunscreen materials: A review of mechanisms of action, precision modification strategies, multifunctional application advances, challenges and prospects - Yuan Chen; Zibo Yu; Rui Tang; Jiayi Sun; Xigao Jian; Jinyan Wang; Xiaozhou Zhang; Xing Wang; Jingyu Xu (Journal of Environmental Chemical Engineering, 2026)

Dependence of Fe2O3 crystal planes on CO oxidation performance for CuOx/Fe2O3 catalysts - Yuan She; Wenkang Niu; Rui Liu; Hao Meng; Changqing Peng; Xuanxuan Wang; Jiawei Qiang (Chemical Engineering Journal, 2026)

Corrigendum to: “Photothermal modulation of the regenerative microenvironment for reversing optic nerve injury” [Chem. Eng. J. 524 (2025) 169698] - Kexin Tan; Jiayu Wang; Qianyue Zhang; Shuo Wu; Haiyang Zhang; Yusha Liu; Zhaohan Qu; Siwei Liu; Rui Huang; Yan Liu; Yang Wang; Yingzhi Chen; et al. (Chemical Engineering Journal, 2026)

Improved eradication of apple stem grooving virus and apple chlorotic leaf spot virus in apple rootstocks by combining thermotherapy with electrotherapy - Xiao-Yan Ma; Qing Li; Zhi-Wei Kang; Ming-Yuan Jing; Ya-Ting Zhang; Min-Rui Wang; Dong Zhang; Lu Bao; Juan-Juan Ma (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Influence of ecological factors on the accumulation of active substances in Camellia nitidissima - Xiao-Xia Zhao; Meng-Xue Su; Shuang-Shuang Li; Hui Gao; Guo-Yue Yan; Shu-Rui Wang; Yan-Yuan Bai; Yang-Jiao Xie (Plant Biosystems, 2026)

A Novel ML–NWP Coupled Optimization Approach on a Reconstructed WRF Model - Hai Chu; Yuan Cao; Rui Wang; Jianming Xu; Lei Chen; Xuliang Fan; Shiqi Chen; Jianhai Guo; Junjing Wu (Journal of Meteorological Research, 2026)

Low abundance microorganisms enhance soil multifunctionality by emphasizing fungal roles as mediated by plant biomass - Ze-Ying Zhao; Xiao-Bin Xiong; Peng-Yang Wang; Jia-Cheng Guo; Yinglong Chen; Hong-Yan Tao; Nan Chang; Cheng-Rui Bi; Yun-Lu Chen; Yuan Song; You-Cai Xiong (Applied Soil Ecology, 2026)

Natural longevity modulator: aging modulatory effects of Eurycoma longifolia Jack polysaccharides in C. elegans and D. melanogaster - Yan Liu; Hailing Wang; Rui Wu; Yuan Tian; Xin Meng (Biogerontology, 2026)

Deficiency of TEX264-mediated reticulophagy is linked to ER stress-induced neuronal necroptosis: Implication of fluoride-associated hippocampal injury and cognitive dysfunction - Ge Du; Quan Yuan; Rui Liu; Jiaming Liang; Milan Yang; Yufei Gao; Xiaoli Liu; Siman Lin; Rui Zhang; Binbin Wang; Dongmei Wang; Hua Fan (Journal of Environmental Sciences, 2026)

Physicochemical properties, antioxidant activity, antibacterial properties, and fruit preservation potential of black soldier fly chitosan films - Bin-Qiao Yuan; Ting-Hao Yu; Jun-Kui Huang; Xin-Rui Ren; Run-Jia Wang; Guo-Xin Huang; Nortoji A. Khujamshukurov; Da-Wei Huang; Jin-Hua Xiao (Food Bioscience, 2026)

Triterpenoids in the leaves of Schisandra chinensis (Turcz.) Baill. treated AD by inducing mitophagy through activation of MCL-1 - Shi-Qi Xu; Xin Meng; Xu Yang; Gang-Tao Bu; Si-Yi Wang; Meng-Meng Li; Yi-Qiang Zhang; Zhi-Chao Hao; Wei Guan; Qi-Shan Chen; Li-Li Zhang; Rui-Yan Wu; et al. (Food Bioscience, 2026)

Study on the effects of gestational arsenic exposure on the developmental toxicity of brain tissue in mice offspring using network toxicology and RNA-seq - Zitong Wang; Wenjin Qiao; Ruigang Liu; Yuan Lv; Binjie Niu; Tianxu Li; Mengling Zhang; Yanhui Xiang; Rui Qiao; Dapeng Tai (Food and Chemical Toxicology, 2026)

Incorporating Thermal Adaptation and Acclimation Improves Light‐Use Efficiency Modeling for Estimating Gross Primary Production in Tibetan Plateau Grasslands - Gaofei Yin; Jiangliu Xie; Yu Wang; Rui Chen; Yajie Yang; Dujuan Ma; Wenping Yuan; Qiaoyun Xie; Da Wei; Huai Chen; Xinwei Liu; Aleixandre Verger; et al. (Global Change Biology, 2026)
The optimal temperature for photosynthesis (Topt), the temperature at which photosynthesis peaks, is crucial for estimating gross primary production (GPP). Most models, however, apply biome‐specific Topt, overlooking the spatial and temporal variability driven by the genetic adaptation and interannual thermal acclimation of plants, thus introducing systematic error in GPP estimation. We mapped Topt of Tibetan Plateau (TP) grassland averaged over 1982–2018, using satellite‐derived near‐infrared reflectance of vegetation as a proxy of photosynthesis, and projected future Topt under different scenarios of shared socioeconomic pathways (SSPs) using space‐for‐time substitution. We assessed the effects of Topt adaptation on current GPP estimation and acclimation on projected GPP using a light‐use efficiency model (i.e., EC‐LUE model). The spatial heterogeneity of Topt was pronounced across the TP grassland, with higher values in the northeast and lower values in the southwest, averaging 9.32°C ± 3.15°C. Topt tended to increase from 2040 to 2080 across all SSPs, with the slowest increase under SSP1‐2.6 (0.015°C y −1 ) and the fastest increase under SSP5‐8.5 (0.061°C y −1 ). Incorporating Topt adaptation into the EC‐LUE model improved the accuracy of GPP estimation, with R 2 increasing by 7.19% and RMSE decreasing by 11.40%, compared to the model with a fixed Topt. In contrast, ignoring the adaptation of Topt led to systematically lower GPP values across 77.9% of the TP grassland, resulting in an overall reduction of estimated GPP by 7.07% (0.07 g C m −2 d −1 ). Ignoring the acclimation of Topt led to systematically higher projected GPP on the TP, ranging from 2.87% ± 8.96% (SSP1‐2.6) to 3.83% ± 5.97% (SSP3‐7.0) across different scenarios, covering more than 70% of TP regions. These findings highlight the necessity of incorporating both the adaptation and acclimation of Topt into GPP models to enhance the monitoring of the carbon cycle.

Responses of ecological stability in subtropical coastal phytoplankton communities to varying N:P ratios under present and future scenarios - Jichen Chen; Yonglong Xiong; Jingke Ge; Xin Zhao; Yuan Feng; Xu Li; Chi Song; Xiao Yang; Rui Zhang; Jin-Yu Terence Yang; Wuchang Zhang; Shengyao Sun; et al. (Water Research, 2026)

Editor's note “Phosphorus – the main limiting factor in riverine ecosystems in China” [Sci. Total Environ. 870 (2023) 161613] - Yan Chen; Jie Chen; Rui Xia; Yuan Zhang; Kai Zhang; Shanlin Tong; Ruining Jia; Qiang Hu; Lu Wang; Xiaojiao Zhang (Science of The Total Environment, 2026)

Nanoimprinted topological laser in the visible - Qiang Zhang; Rui Duan; Yutian Ao; Lin Wang; Xuehong Zhou; Xuyong Yang; Qing Zhang; Xiao-Cong Yuan; Baile Zhang; Handong Sun (Science Bulletin, 2026)

Conjugated organic polymer enables external-sacrificial-agent-free photocatalytic uranium extraction with efficiency boosted by oxygen pre-activation - Xuefeng Tian; Jipeng Li; Xuewen Cao; Jiacheng Zhang; Rui Huang; Peng Lin; Ning Wang; Yihui Yuan (Science Bulletin, 2026)

Effects of suspended sediment on the survival and settlement of Crassostrea ariakensis and Crassostrea sikamea larvae: Results from lab experiments - Nan-nan Li; Yu Han; Yuan-ge Chen; Wei-liang Dong; Long-ling Ouyang; Rui-liang Fan; Wei Jiang; Jia-feng Fang; Nian Wei; Jin-ming Wang; Wei-min Quan; Jian Zeng (Regional Studies in Marine Science, 2026)

CoTiO3 immobilized on nickel foam for degradation of levofloxacin via peroxymonosulfate activation: Electron transfer pathways and degradation mechanism - Zhonghua Mu; Peng Cui; Rui Gao; Jikai Liu; Wei Li; Yushu Zhang; Wenqiang Ma; Hairui Li; Shiqi Wu; Shuzheng Zhang; Zhaohui Wang; Lei Yang; et al. (Process Safety and Environmental Protection, 2026)

Quantitative study on the cave environmental factors for the fractionation of stable oxygen isotopes during the deposition of speleothem - Yue Jin; Chun-Jie Wang; Jian Zhang; Wen-Jun Sun; Chao-Jun Chen; Yao Wu; Hua-Yan Li; Yue-Hua Xiang; Yue-Yuan Lin; Xin-Rui Ye; Xin-Yan Li; Zhong-Lin Deng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Geochemistry of tourmaline in granitic rocks from the Zharigana and Caolong areas, Northern Tibet: Implications for the identification of lithium-mineralizing plutons - Ling Ma; Jin-Sheng Zhou; Qiang Wang; Lin Ma; Jin-Heng Liu; Wu-Fu Li; Bing-Zhang Wang; Chun-Tao Wang; Jian-Dong Liu; Xin-Yuan Zhang; Mao-Rui Liu; Zhi-Wei Yu; et al. (Lithos, 2026)

Role of iron oxides in stabilization of soil organic carbon along vegetation distribution gradient in coastal wetland, Southeastern China - Rui Zhang; Lijie Pu; Jiawei Tao; Jiayi Xie; Sihua Huang; Xiaoqing Wang; Ye Yuan; Rui Zhong; Jiahao Zhai; Lu Yumeng (Journal of Environmental Management, 2026)

Single-atom calcium catalysts with C-N-Ca coordination improve the efficiency of preparing olefins from plastics - Kaiwen Yun; Xixi Lian; Rui Shan; Guoqiang Wei; Shuxiao Wang; Haoran Yuan; Yong Chen (Journal of Cleaner Production, 2026)

Effect of Mo on ZnSO4 resistance over FeCe catalyst from vanadium slag for low-temperature NH3-SCR of NO - Yuan She; Hao Meng; Wenkang Niu; Changqing Peng; Junjie Wang; Xuanxuan Wang; Rui Liu; Zhifeng Ding (Journal of Environmental Chemical Engineering, 2026)

Energy input rate as a key switch: tuning product distribution and carbon structure in waste tire pyrolysis via conventional and microwave heating - Peng Liu; Shuxiao Wang; Jing Gu; Rui Shan; Yanzhi Sun; Junqing Pan; Haoran Yuan; Yong Chen (Fuel, 2026)

Shading stress decreases the taste quality of rice by altering the structural and functional properties of protein - Xiaofeng Ai; Fei Deng; Qiuping Li; Yunchuan Peng; Rui Wang; Xiurong Hu; Rui Liu; Yujie Yuan; Li Wang; Hong Cheng; Youfeng Tao; Xiaolong Lei; et al. (Food Chemistry, 2026)

Influences of vegetation distribution on soil organic carbon accumulation and stability in a coastal wetland, Southeast China - Rui Zhang; Lijie Pu; Jiawei Tao; Jiayi Xie; Ye Yuan; Rui Zhong; Jiahao Zhai; Yumeng Lu; Xiaoqing Wang; Lu Qie; Geli He; Sihua Huang (CATENA, 2026)

Overexpression of PtrPYL11 enhance drought tolerance in Populus: evidence from genome-wide identification and comparative transcriptome profiling - Shuang-Lian Deng; Shu-Ying Wei; Rui-Quan Wang; Yuan Zhang; Hao Li; Xing-Yu Liu; Xin-Ran Yu; Guan-Ru Ren; Ting Wang; Fang He (Plant Cell Reports, 2026)

Thermodynamic Analysis and Dynamic Evolution of Microscopic Physicochemical Properties During the Oxidation Process of Low-Rank Coal - Linhao Xie; Hongqing Zhu; Rui Li; Lei Zhang; Qi Yuan; Tianyu Li; Houwang Wang (Natural Resources Research, 2026)

Establishment and application of multiple cross displacement amplification coupled with lateral flow biosensor (MCDA-LFB) for visual and rapid detection of Candida glabrata - Yan Yuan; Yuhong Zhou; Yanfeng Zhou; Rui Ye; Jingrun Lu; Yizhe Wang; Fang Wei; Fukuan He; Honglan Yu; Yu Wang (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Rapid and Simple Detection of Enterocytozoon Bieneusi Using Lateral Flow Assay Based on Recombinase Polymerase Amplification or Nested PCR Combined with CRISPR–Cas12a - Yi-Yang Liu; Yue-Rong Lv; Jun-Tao Jia; Rong Zhang; Bo Yang; Shi-Yuan Xue; Hasi Bayaer; Alateng Bagen; Rui-Bin Chen; Siqin Tunala; Rui Wang; Yu-Lin Ding; et al. (Acta Parasitologica, 2026)

A Distributed Maritime Target Classification Method Based on Broad Learning and MobilityFirst - Zhenqi Wang; Fei Teng; Shilong Liu; Liang-En Yuan; Rui Wang (Journal of Marine Science and Engineering, 2026)
Marine target classification is a key technology for unmanned surface vehicles (USVs) to perform ocean surveillance. Traditional maritime target classification methods require improvements in both accuracy and processing speed when handling classification tasks. In this paper, a distributed maritime target classification (DMTC) method based on broad learning and MobilityFirst is proposed. Firstly, a multi-model collaborative classification and fusion framework is proposed to achieve feature consistency fusion. Secondly, to enhance the security and privacy of communication in autonomous surface vehicles, the MobilityFirst approach is employed to improve information complementarity among multiple models within the distributed framework. Finally, the broad learning system, as the model’s classification layer, reduces the training complexity. Extensive experimental results demonstrate that this proposed approach surpasses single-model and distributed methods in accuracy, F1 score, and the area under the precision–recall curve (AUPR). This approach offers a clear advantage in multi-ship classification tasks while simultaneously enhancing the model’s generalization capability.

Comprehensive analysis of Clade A PP2C family in poplar unveils PtrPP2C-9 as a negative regulator of osmotic stress tolerance through ABF3/GBF3 network - Yuan Zhang; Rui-Quan Wang; Xin-Yi Wang; Shu-Ying Wei; Hao Li; Shuang-Lian Deng; Jia-Hui Liu; Ting Wang; Liang-Hua Chen; Fang He (Plant Science, 2026)

Depleting SfCarE: Innovative strategies for enhancing chlorantraniliprole toxicity through mixing with carbaryl in Spodoptera frugiperda (Lepidoptera: Noctuidae) - Qinqin Wang; Lin Zhou; Li Wang; Xiangshuai Li; Pei Liang; Changhui Rui; Huizhu Yuan; Li Cui (Pesticide Biochemistry and Physiology, 2026)

Numerical assessment of erosion risk for composite hydrofoils by the potential energy theoretical method - Ruhan Shao; Rui Yuan; Housheng Zhang; Qin Wu; Biao Huang; Guoyu Wang (Ocean Engineering, 2026)

Endoplasmic reticulum stress-induced CHOP activation mediates NLRP3 inflammasome-dependent pyroptosis in BDE-47-induced cognitive dysfunction - Quan Yuan; Rui Zhang; Jun Hu; Siman Lin; Ying Zhu; Junhong Geng; Ge Du; Xiao Yang; Yipin Zhao; Dongmei Wang; Binbin Wang; Hua Fan (NeuroToxicology, 2026)

CRISPR/Cas9-mediated knockout of the 22 kDa α-prolamin genes orchestrates the regulation of functional amino acid content in foxtail millet - Rui Zhao; Jiayi Chen; Yongchao Li; Maosheng Jin; Kejin Liu; Yang Liu; Lulu Gao; Guanghui Yang; Xiangyang Yuan; Xiaoqian Chu; Jia-Gang Wang (Journal of Plant Physiology, 2026)

Insights into the low-temperature NH3-SCR of NO performance and mechanism over vanadium slag catalyst - Yuan She; Hao Meng; Wenkang Niu; Changqing Peng; Junjie Wang; Rui Liu; Xuanxuan Wang (Fuel, 2026)

Resistant dextrin/xanthan gum gels protect probiotics for application to ionizing radiation shielding - Minting Wang; Rui Sun; Liuchan Zeng; Shumin Du; Yubao Fang; Bo Zhuang; Bochuan Yuan; Yiguang Jin (Food Research International, 2026)

Alpaca nanobody-based sandwich ELISA for specific detection of Salmonella enteritidis in chicken - Liang Yuan; Shibo Wang; Yani Ren; Zhenghua Ji; Xinru Jiang; Beili Hao; Shuangshuang Hao; Xiaoxi Han; Changwen Li; Yicong Chang; Rui Li; Fangping Liu (Food Control, 2026)

Enhancing functional metabolites and flavor volatiles of kiwifruit juice fermented with selenium-enriched Limosilactobacillus fermentum Ln-9 - Ling Liu; Xueer Wang; Zeyu Hu; Shiqi Li; Bowen Duan; Weiteng Tan; Zhouli Wang; Rui Cai; Yahong Yuan; Tianli Yue (Food Microbiology, 2026)

Self-replenishing metabolically enhanced probiotic delivery strategy to alleviate ulcerative colitis through intestinal homeostasis remodeling and aryl hydrocarbon receptor signaling activation - Rui Sun; Jiayi Chen; Jingkai Fan; Ying Wang; Xueer Wang; Yue Liu; Zhouli Wang; Tianli Yue; Yahong Yuan (Chemical Engineering Journal, 2026)

Thermosensitive hydrogel with Ganoderma lucidum polysaccharide–ferulic acid nanoparticles and rhEGF for enhanced diabetic wound healing - Fei Li; Tingting Liu; Qi Zhang; Wenbao Wang; Xiaoxing Ma; Rui Ma; Cheng Yuan; Cuiyan Han; Xiaoyu Sui (Chemical Engineering Journal, 2026)

SLM-Fabricated CuCrZr TPMS Heat Exchangers: Influence of Structural Design on Fluid Transport Characteristics - Xiaoqing Yang; Yaqin Yang; Chao Suo; Bin Liu; Xueli Chen; Zezhou Kuai; Yaoxian Zhang; Yuan Gao; Zhonghua Li; Rui Wang (Transport in Porous Media, 2026)

CRISPR/Cas9-mediated α-prolamin gene (Seita.8G190200) mutagenesis increases the content of functional amino acids in foxtail millet (Setaria italica) - Rui Zhao; Jiayi Chen; Yongchao Li; Dan-Ying Chen; Xueting Kang; Shuqi Dong; Xiangyang Yuan; Xiaorui Li; Lulu Gao; Guanghui Yang; Xiaoqian Chu; Jia-Gang Wang (Plant Cell Reports, 2026)

Trade-off or synergy: did nature-based climate solutions bring co-benefits for ecological conservation? — Evidence from China - Qi Wang; Yuan Hu; Weizhong Zeng; Rui Chen (Environment, Development and Sustainability, 2026)

Integrating CO2-EOR and Sequestration via Assisting Steam Huff and Puff in Offshore Heavy Oil Reservoirs with Bottom Water - Guodong Cui; Kaijun Yuan; Haiqing Cheng; Quanqi Dai; Xi Chen; Rui Wang; Zhe Hu; Zheng Niu (Journal of Marine Science and Engineering, 2026)
CO2-assisted steam huff and puff is an effective method to improve oil recovery and store CO2 in heavy oil reservoirs. However, few studies focused on complex geological formations, such as bottom water. The bottom water condition not only complicates the process of oil production and CO2 sequestration, but also makes migration and distribution of oil, water and CO2 unclear. In this paper, a numerical geological model of an offshore heavy oil reservoir with bottom water is established to analyze the influence of bottom water on injection and production parameters, oil recovery and CO2 storage capability under vertical and horizontal well layouts. The results show that the bottom water could maintain the formation pressure, but reduce the steam chamber radius and heavy oil utilization area, increase water production and decrease the oil–water ratio. CO2 could enhance oil recovery in the bottom water reservoir. Oil development indicators of the horizontal well are higher than the vertical well. Meanwhile, CO2-assisted steam huff and puff use in the bottom water reservoir can create a high-pressure and -temperature environment to make CO2 supercritical, as it has better CO2 storage capability and efficiency. The CO2 storage efficiency of the horizontal well is 63% larger than the vertical well. Thus, the horizontal well layout should be used as a priority if bottom water presents. Conducted analysis of bottom water formation sensitivity parameters shows that the advantageous formation conditions are high oil saturation, porosity of 0.2–0.4 and permeability of 2000–3000 mD. The influence degrees of each formation parameter were evaluated as well.

Quantifying the critical regulator role of irradiation-enhanced electric field in nanoplastics aggregation with heavy metals - Yaowu Zhang; Xianzheng Yuan; Ying Tang; Xinmin Liu; Fengxin Zhao; Yan Peng; Xinping Gao; Lin Wang; Lijing Wang; Rui Tian; Rui Li; Hang Li (Water Research, 2026)

Identification of novel B-cell neutralizing epitopes in goose Astrovirus type 2 - Shichao Yuan; Rui Fu; Bangfeng Xu; Wenqing Wang; Huamao Ding; Xue Pan; Chunxiu Yuan; Qinfang Liu; Zhifei Zhang; Qiaoyang Teng; Xiaona Shi; Minghao Yan; et al. (Veterinary Microbiology, 2026)

Wnt pathway activation unlocks disease-neutral proliferative potential in human iPSC-derived cardiomyocytes: A comparative study across healthy and inherited cardiac disease models - Yafei Zhou; Wenjun Huang; Jie Wang; Haiyang Yuan; Yanmin Zhang; Rui Zhou (Tissue and Cell, 2026)

Nitrogen fertilizer strategies modulate gaseous nitrogen losses and improve maize yield and nitrogen use efficiency under saline-alkali stress in coastal reclaimed farmland - Xiaoqing Wang; Jiayi Xie; Wenjing Li; Lijie Pu; Pengjun Chen; Jijun Han; Chenliang Du; Sihua Huang; Rui Zhang; Rui Zhong; Ye Yuan; Jiahao Zhai; et al. (Soil and Tillage Research, 2026)

Zinc finger protein ZNF638 in brown fat deteriorates type 1 diabetes via retinol binding protein 4 - Meiyao Meng; Shuang Liu; Yinzhao Zhong; Jingyi Hu; Lijun Zhu; Jin Qiu; Rui Wang; Yuan Luo; Yingwen Wang; Wenhao Zhou; Guangyu Shan; Zhenyu Du; et al. (Science Bulletin, 2026)

Controls of surface water-groundwater interaction on the migration and transformation of dissolved organic matter in coastal area - Ying Liang; Xulong Gong; Rui Ma; Changjian Zou; Xue Jiang; Chen Liu; Kaige Ma; Yuan Liu; Yanxin Wang (Journal of Hydrology, 2026)

Mechanistic insights into product distribution and bromine fixation during co-pyrolysis of cattle manure with organic components of printed circuit boards - Wenqi Guan; Dong Liang; Che Zhao; Danni Li; Shuxiao Wang; Rui Shan; Haoran Yuan; Yong Chen (Journal of Environmental Chemical Engineering, 2026)

Montmorillonite-enhanced nitrogen fixation and emission reduction during food wast pyrolysis - Hongyuan Chen; Danni Li; Yazhuo Wang; Yaoxin Xiao; Dong Liang; Gangqi Cheng; Rui Shan; Haorang Yuan; Yong Chen (Fuel, 2026)

Tailoring a simplified and steady-state kombucha consortium for newly-formulated kiwifruit beverage production: Impacts on untargeted/targeted metabolites, antioxidant capacities and flavor profiles - Shiqi Li; Keying Chu; Rong Guo; Jiamin Wu; Xingnan Wang; Jing Guo; Yahong Yuan; Tianli Yue; Rui Cai; Zhouli Wang (Food Research International, 2026)

Isothiazolinone biocide aggravate disinfection-resistant bacterial fouling on reverse osmosis membranes - Yu-Qing Xu; Zheng-Yang Huo; Yuan Bai; Yun Wang; Wen-Long Wang; Hao-Bin Wang; Yu-Jia Gao; Rui-Ning Wang; Chen-Yu Li; Han Liu; Wei E. Huang; Hong-Ying Hu; et al. (Desalination, 2026)

Synergistic anion confinement and gradient desolvation enable oriented Zn deposition in MOF–polymer hydrogel electrolytes - Chengze Li; Rui Wang; Guoqiang Yuan; Jiabao Li; Mohsen Shakouri; Wenting Li; Huan Pang (Chemical Engineering Journal, 2026)

Sustainable production of Microalgae-Derived turbostratic graphene via flash Joule heating - Fuyuan Wang; Rui Huang; Yujie Yu; Shaojunyan Tan; Ruijie Yuan; Jianyong Yin; Shijie Zhang (Bioresource Technology, 2026)

Tree of life and conservation of gymnosperms in China - Chang-Wang Ma; Dan Xie; Hong Du; Kai-Yuan Huang; Yuan-Yuan Feng; Zhou-Rui Wei; Xin-Quan Liu; Cheng-Ru Li; Jing-Jing Sun; Xiao-Xin Wei; Zhi-Heng Wang; Wei-Hua Xu; et al. (Science China Life Sciences, 2026)

The potential relationships between soil microbial communities and seed germination in the floodplain wetlands - Meng-Li Wang; Rui-Si Zhao; Xiao-Kan Wang; Jia-Ying Tian; Qian-Kun Hu; Long-Yi Yuan; You-Cai Xiong; Ai-Tian Ren (Plant and Soil, 2026)

Genome-wide identification of TGA transcription factors in wheat and the TaTGA13 negatively modulates stripe rust resistance - Jiajie Liu; Rui Li; Mingjie Xiang; Xunyin Yuan; Yifan Tian; Xuanqi Zhang; Jingyao Wang; Jianhui Wu; Qingdong Zeng; Dejun Han (Plant Science, 2026)

Tectonic uplift of the western segment of the East Kunlun Mountains since early Miocene times: Constraints from detrital zircon fission track geochronology and subsurface data - Yadong Wang; Wei Zhou; Sihua Yuan; Yuan Rui (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Research on the failure modes of frozen loess under uniaxial compression with varying moisture contents - Yuan Xin; Qiang Sun; Pingye Guo; Jingjing Nan; Jishi Geng; Ziyu Wang; Rui Lv; Shaoli Liu (Journal of Applied Geophysics, 2026)

Study on the flame inhibition characteristics and mechanism of R1233zd(E) - Rui Zhai; Zhijun Li; Yuan Zhuang; Bin Ye; Hongling Zhao; Lei Tang; Ke Wang (International Journal of Refrigeration, 2026)

Preparation of high polyphenol-low caffeine instant tea powder by exploring and regulating the changes of key functional compounds during kombucha fermentation - Rui Sun; Jingkai Fan; Yubo Zhou; Zinuo Lei; Silong Yang; Ying Wang; Zhouli Wang; Yahong Yuan; Tianli Yue (Food Chemistry, 2026)

Synergistic 3d-5d orbital interactions on oxygen vacancy-rich Pt/TiO2 for enhanced photothermal catalytic oxidation of propylene - Xiaoxiao Zhu; Weidong Yuan; Siyi Song; Tong Chen; Wenjun Xiong; Sibo Wang; Jinpeng Hu; Rui Liu; Zhu Luo; Jinlong Wang; Ang Gao; Yanbing Guo (Chemical Engineering Journal, 2026)

ADAM17 Supports Disinhibition of Pre-sympathetic Glutamatergic Neurons Through Microglial Chemotaxis - Jiawei Wang; Zihan Qiu; Yue Han; Hanxue Wu; Miao Yuan; Yan Liu; Huichao Wang; Shenglan Yuan; Dengfeng Gao; Lina Sun; Xingjuan Chen; Eric Lazartigues; et al. (Neuroscience Bulletin, 2026)

Performance of heavy metals in the intertidal zone surface sediments of the Yellow River Estuary under water-sediment regulation scheme - Shan Shan Liu; Jin Ming Song; Xue Gang Li; Hua Mao Yuan; Li Qin Duan; Jun Ma; Feng Min Pan; Jian Wei Xing; Chen Long Feng; De Tong Tian; Zhi Bo Wang; Rui Wang (Marine Pollution Bulletin, 2025)

Testis-specific gene C3ORF22/BC048671 is dispensable for spermiogenesis and male fertility - Shiyue Du; Yongfu Liu; Le Wang; Liuliu Shi; Xiaoying Zhao; Zhongcheng Yang; Wei Yuan; Xiaoying Deng; Jiahua Liu; Shenglei Feng; Rui Chen (Reproductive Biology, 2025)

New insights into sink-source dynamics of mangrove for microplastics: Quantitative evidences from field observation and resuspension simulation - Rui Li; Chao Yan; Qirui Wu; Xiangmei Cheng; Hua Wang; Zaizhi Yang; Zuobing Liang; Di Tian; Ning Yuan; Lei Hou; Lei Gao (Journal of Hazardous Materials, 2025)

Effects of sun drying combined with baking processes on the flavor quality of Chongqing Tuocha raw tea - Hongyu Luo; Rui Chang; Shanmin Chen; Yueyun Liu; Yi Wang; Linying Yuan; Juan Yang; Ying Zhang; Ruiqi Duan; Quan Wu; Yingfu Zhong (Food Chemistry, 2025)

Trace polymer additive-mediated H-bond reconstruction and water-deficient Helmholtz layer for 4500 h Zn anodes - Huijie Li; Zichun Yuan; Leyao Li; Qiang Yu; Fuxin Wang; Rui Li; Yanxia Yu; Dezhou Zheng; Xihong Lu (Chemical Engineering Journal, 2025)

Different Chemical Fertilization Levels Affect Arbuscular Mycorrhizal Fungal Communities in Rhizosphere Soils of Ratoon Sugarcane - Xiao-Juan Qin; Sheng Wang; Ying-Jie Nong; Yi-Hao Kang; Jin-Lian Zhang; Shi-Yuan Zeng; Ting-Su Chen; Yang-Rui Li (Sugar Tech, 2025)

Phosphorus speciation, controlling factors, and ecological risk assessment in lagoon sediments: a case study of the Shamei Lagoon, Qionghai, Hainan - Kun Yuan; Xuan Mu; Guangning Xiao; Kexin Li; Wantong Zhou; Rui Wang; Shisheng Wang (Frontiers in Marine Science, 2025)
The Shamei Lagoon in Qionghai, Hainan, is an ecologically significant coastal wetland system that has recently faced increasing ecological risks due to phosphorus (P) pollution. In this study, 22 sediment samples were systematically collected from the main lagoon body, river inlets, and the transitional zone to the open sea. A comprehensive approach incorporating standardized phosphorus fractionation, spatial interpolation, redundancy analysis, and ecological risk assessment was used to investigate P speciation, spatial distribution patterns, controlling factors, and ecological risks. The results showed that: (1) Total phosphorus (TP) concentrations ranged from 261.87 to 875.74 mg/kg, with a mean of 415.72 mg/kg, comparable to typical lagoons in China. Inorganic phosphorus (IP) dominated the P fractions (mean: 317.70 mg/kg), with Fe/Al-bound phosphorus (Fe/Al-P, mean: 183.52 mg/kg) markedly exceeding Ca-bound phosphorus (Ca-P, mean: 105.88 mg/kg). Organic phosphorus (OP) had the lowest contribution (mean: 98.02 mg/kg). (2) The primary sources of P pollution were agricultural runoff and aquaculture waste, industrial discharges and vessel leakage, and regional calcareous deposition. High TP and OP concentrations were concentrated in the southwest river inlet zone, directly linked to fertilizer runoff and tourism-related wastewater. IP levels were elevated in the southern region, driven by hydrodynamic processes. Fe/Al-P was enriched in the central lagoon, likely associated with oil degradation from vessels. Secondary peaks of Ca-P occurred in the southwest aquaculture zone and the northeastern mangrove area, attributed to feed residues and shell debris, respectively. (3) Cation exchange capacity (CEC) was identified as the primary controlling factor for spatial variation in P speciation (explained variance: 46.0%, p < 0.01), followed by organic matter (OM), while pH exhibited a marked negative regulatory effect. (4) At 45.5% of sampling sites, TP levels exceeded the ecological safety threshold (600 mg/kg), and 18 sites, mainly located near the river mouth and central lagoon, were classified as heavily polluted, posing a threat to aquatic ecological security. These findings indicate that sediment P pollution in the Shamei Lagoon is driven by multiple anthropogenic activities. Mitigation strategies should prioritize control of agricultural non-point sources, aquaculture residues, and vessel oil pollution, along with sediment remediation focused on enhancing CEC.

Injectable Hyaluronic Acid Hydrogels Crosslinked by Structure-engineered Aldehyde-functionalized β-Cyclodextrin Derivatives for Long-term Controlled Voriconazole Delivery - Chao Yang; Meng Xin; Yufu Jiang; Wenqian Wang; Wenhui Li; Junlin Quan; Wancong Zhou; Rui Yuan; Zhe Chen; Depeng Shi; Zhijian Ji; Xingxing Yue; et al. (AAPS PharmSciTech, 2025)

Prevalence and risk factors of Giardia duodenalis in sheep and goats in global: A systematic review and meta-analysis - Zhengyi Li; Wei Wei; Yuan Ma; Luyao Hao; Yuan Guo; Rui Wang (Preventive Veterinary Medicine, 2025)

Microplastics modulate neutrophil migration via an ROShistone lactylation positive feedback loop - Yi-li Wang; Xiao-chen Yuan; Chun-jiao Wei; Ke-yun Li; Lin-xi Zuo; Hao-yi Zhang; Rui-chen Ding; Ren Zhou; Yun-hua Zhang; Da-long Ren (Journal of Hazardous Materials, 2025)

The correlation between temperature change and lung cancer risk altered by air particulate pollutants: Nationwide analysis - Shenxuan Zhou; Yanchi Wang; Zhenyu Li; Yiran Liu; Rui Zhu; Bo Liu; Jiacan Yuan; Mingna Wu; Jing Xiao; Hanpeng Lai; Anhui Ning; Yan Zhang; et al. (Journal of Cleaner Production, 2025)

Higher ammonia oxidizing activity of comammox cooperates with ammonia-oxidizing bacteria to release N2O in river ecological restoration areas - Yuantao Wang; Shenghua Zhang; Rui Jia; Xin He; Ang Li; Dongdan Yuan (Journal of Environmental Management, 2025)

Multifunctional double-layer film incorporated Pickering emulsions and polyphenol-anthocyanin co-pigmentation for maintaining and monitoring shrimp freshness - Shiqi Li; Shuo Zhang; Xuerong Hu; Jiale Zhao; Xingnan Wang; Yahong Yuan; Tianli Yue; Rui Cai; Qian Ge; Zhouli Wang (Food Research International, 2025)

Laboratory characterization of VOC evaporative emissions from light-duty plug-in hybrid electric vehicles: Environmental impact comparison with conventional vehicles - Ling Li; Rui Yuan; Wei Hu; Hualong Xu; Pingjiang Lv; Qin Xu; Jun Wang; Xue Jiang; Jianxun Tan; Jianli Yin; Zhenliang Li; Dan Zhang (Environmental Pollution, 2025)

Wireless gas sensor based on monolayer Ti3C2Tx-modified GaN/CuO heterostructures for ultrafast and trace detection of NO2 gas - Haineng Bai; Cheng Feng; Rui Guo; Yiru Chen; Wenfeng Yuan; Yunxiao Du; Yamin Feng; Weifeng Liu; Kuili Liu; Fuqiang Guo; Jin Wang; Dunjun Chen; et al. (Chemical Engineering Journal, 2025)

Photothermal modulation of the regenerative microenvironment for reversing optic nerve injury - Kexin Tan; Jiayu Wang; Qianyue Zhang; Shuo Wu; Haiyang Zhang; Yusha Liu; Zhaohan Qu; Siwei Liu; Rui Huang; Yan Liu; Yang Wang; Yingzhi Chen; et al. (Chemical Engineering Journal, 2025)

The synergistic effect of triazine-N and secondary amine-N anchors iodine species with MXene composite cathode for stable aqueous Zn–I2 battery - Jing Ma; Yaoyao Linghu; Kai Yuan; Rui Zhou; Hui Gao; Peihua Zhao; Shaohui Guo; Huiqi Wang; Yongping Qu; Chao Shen; Keyu Xie (Chemical Engineering Journal, 2025)

SIRT3 promotes mitophagy to attenuate fumonisin B1-induced chicken hepatocyte senescence and antagonism of lycopene - Yuan-Hang Chang; Ming-Shan Chen; Hong-Mei Zhu; Rui-Qi Liu; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yue Cheng; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2025)

Constructing MoxTi1-x catalytic pairs to enhance photoelectron transfer for emerging contaminants photocatalytic removal - Hai-Yuan Chi; Jian-bin Su; Sheng-tai Hou; Ze-hua Wang; Xi-tong Li; Wen-long Zhang; Hong-jie Wang; Rui Liu (Journal of Cleaner Production, 2025)

Comparative effects of improved schemes with shape adjustment and composite packaging on radio frequency heating of two-component rice - Yingqi Tian; Mengge Li; Jiahong Yuan; Dongsheng Hu; Rui Li; Hosahalli Ramaswamy; Shaojin Wang (Innovative Food Science & Emerging Technologies, 2025)

Preparation of nanocellulose/tannic acid-stabilized emulsions combined synergistic co-pigments incorporated polysaccharide-based film for fresh-keeping monitoring and efficient preservation - Shiqi Li; Xueer Wang; Xinyan Li; Xingnan Wang; Rui Cai; Yahong Yuan; Tianli Yue; Junjun Wang; Zhouli Wang (Innovative Food Science & Emerging Technologies, 2025)

The role of hydrolysis on the fibrillization of walnut protein: Self-assembly behavior, structural characteristics - Chang Li; Rui Chen; Jiangjuan Yuan; Feng Jin; Fengjun Wang (Food Chemistry, 2025)

Community metagenomics, widely targeted metabolomics and volatilomics analysis reveal dynamic mechanism and correlation pattern in kombucha - Shiqi Li; Shuo Zhang; Rong Liu; Leran Wang; Xingnan Wang; Yahong Yuan; Tianli Yue; Rui Cai; Zhouli Wang (Food Bioscience, 2025)

Impact of amplicon length on the identification of edible oils based on real-time PCR - Kai Chen; Bin Xiao; JianZhi Luo; XueWei Yuan; Juan Zhang; Songxue Wang; Rui Zhang; Nan Wang; LiQiang Liu; AiKe Li; Ailiang Chen (Food Control, 2025)

Synthesis of confined palladium nanocatalysts in crystalline hemoglobin framework: An ultrastable nanoreactor for Cr(VI) detoxification - Xiao-Qian Jin; Jia-Lei Li; Jun-Bin Xiong; Rui Zhang; Chen-Yuan Li; Xue-Ting Wang; Wei-Hong Guo; Da-Chuan Yin (Environmental Research, 2025)

Utilizing a three-zone control model of adaptive concentrating photovoltaic facade to enhance visual comfort and energy benefits - Bo Wang; Yifan Xu; Hao Wang; Xinshuo Zhang; Yuan Chen; Rui Tang; Ayin Yan; Mengli Zhang; Ying He (Energy and Buildings, 2025)

Rockburst Severity Prediction Under Few-Shot Conditions Using Feature Fusion Learning - Xin Cai; Liye Chen; Yichao Rui; Ruishan Cheng; Zilong Zhou; Jixiong Zhang; Hang Yuan; Yunmin Wang (Natural Resources Research, 2025)
Accurate and efficient prediction of rockburst severity is crucial for the safe construction of deep rock engineering, but only a limited number of recorded rockburst data cannot enable the reliable prediction. This paper presents an innovative method for predicting rockburst severity, termed Feature Fusion Learning (FFL). It combines feature fusion with machine learning models and category voting techniques, enabling square-level amplification of sample data to address the challenge of few-shot in predicting rockburst severity. The performance of this method is evaluated against two typical data augmentation techniques (i.e., noise injection and synthetic minority over-sampling technique) combined with three machine learning models (i.e., extreme gradient boosting, light gradient boosting machine, and random forest). The results indicate that the FFL method exhibits superior performance across all metrics compared to the other models. In addition, feature importance assessments and a comparative study on the effect of amount of prior data on the prediction performance of the FFL method are conducted. The results reveal that the FFL method effectively enriches the feature dimensions while preserving the information and properties of the original feature variables. Moreover, the FFL method shows high robustness when applied to datasets with varying sample sizes.

Genetic diversity analysis and duplicates identification of new sweetpotato accessions collected in China - Jie Wang; Rui Yuan; Qinglian Li; Yao Wang; Donglan Zhao; Lingxiao Zhao; An Zhang; Xibin Dai; Shizhuo Xiao; Tong Ning; Zhilin Zhou; Qinghe Cao (Genetic Resources and Crop Evolution, 2025)

Deinococcus lichenicola sp. nov., A Bacterium Isolated from a Lichen Sample - Guo-Hua Chen; Lian-Shuang Xiong; Rui Yang; Shu-Ya Zuo; Qing Yuan; Li-Song Wang; Cheng-Lin Jiang; Xin-Yu Wang; Yi Jiang (Current Microbiology, 2025)

Efficient acidified food wastewater treatment by synergistic microalgae and aerobic bacterial consortium - Rui Ma; Wusi Yang; Wenjing Chen; Yutao Wang; Yupeng Yuan; Yingqiang Sun (Algal Research, 2025)

Research progress on programmed cell death of cardiomyocytes in pressure-overload hypertrophic cardiomyopathy - Fei Xiao; Hui-Li Li; Jia-Rui Wang; Hui-Min Wu; Yu-Qi Cai; Jia-Wan Wang; Hao Che; Gang Li; Zheng-Yuan Xia; Yu-Bo Xie; Sheng Wang (Apoptosis, 2025)

Acute high-altitude hypoxia induced NLRP3 inflammasome activation in pulmonary artery smooth muscle cells by BMAL1 targeting mitochondrial VDAC1-mediated MtDNA leakage - Si-Yuan He; Ying-Rui Bu; Jin Xu; Yu-Meng Wang; Tian-Xi Feng; Pei-Jie Li; Yi-Xiao Zhao; Yi-Ling Ge; Man-Jiang Xie (Apoptosis, 2025)

Identification and characterization of a new strain of Ictalurid herpesvirus 1 isolated from channel catfish in China - Fei Yu; Jiehua Xu; Sheng Yuan; Yi Yang; Siyang Song; Kai Hao; Rui Yuan; Yu Wang; Xiaohui Chen; Zhe Zhao (Aquaculture, 2025)

Silicon supplementation via carriers to enhance diatom competition with cyanobacterial blooms and remediate eutrophic waters - Rui Zhou; Bang Xiao; Li Zhao; Yangyang Tang; Wei Yang; Huazu Liu; Xiangdong Zhang; Chaowei Yuan; Xinqi Wang; Xizi Long; Qiang He; Wei Li (Water Research, 2025)

Anti-neuroinflammatory naphthol dimers from the marine-derived fungus Penicillium sp. HQ1-23 - Yuan-Han Xie; Chun-Hong Wang; Rong Wang; Hui Jia; Fei Liu; Zi-Hong Peng; Ya-Hui Zhang; Jun Li; Rui-Yun Yang; Li-Jun Zhang; Wei-Feng Xu (Phytochemistry, 2025)

Enhancement of soil DOC and electron transport by biochar strengthens Cd immobilization via iron oxides transformations in waterlogged soils - Xin Chen; Tianren Si; Senhan Wang; Rui Yuan; Rongjun Bian; Xiaoyu Liu; Xuhui Zhang; Lianqing Li; Genxing Pan (Journal of Environmental Management, 2025)

Inactivation of Penicillium spp. in apple juice by pulsed light and the exploration of its mechanisms - Guolong Li; Saiqun Wang; Yu Li; Lu Cui; Rui Cai; Tianli Yue; Yahong Yuan; Zhouli Wang (Food Control, 2025)

BaTiO3 dressed in carbon multifunctional layer achieving high areal capacity zinc metal batteries - Rui Wang; Jing Xu; Shijun Luo; Yan Guo; Baohe Yuan; Lei Xu; Junming Li; Yongqi Zhang; Yusheng Wang; Wenpeng Yang; Jinbing Cheng; Yongsong Luo (Chemical Engineering Journal, 2025)

Monolayer graphene interlayer enhanced flexible gas sensor with fast response and high strain tolerance for wearable ammonia monitoring - Chen Wang; Ziran Wang; Feng Xu; Luyang Zhang; Haoyu Yuan; Zaiyu Zhang; Chaqi Gai; Zhongjing Ren; Haipeng Wang; Rui You; Peng Yan (Chemical Engineering Journal, 2025)

Spatial confinement of Bi/TiO2 nanoparticles with an abundant heterointerface in hollow carbon spheres for durable sodium storage - Zhao Li; Rui Yuan; Yangwu Hou; Xinde Wei; Zhaozhao Zhu; Yamei Wang; Shilong Xu; Lei Chen; Yan Wang; Rui Wu; Qingquan Kong; Jun Song Chen (Chemical Engineering Journal, 2025)

A unique demersal fish fauna in the Chukchi Borderland, Central Arctic Ocean - Ran Zhang; Hai Li; Puqing Song; Rui Wang; Jing Zhang; Tianci Wang; Shusen Fu; Shigang Liu; Yuan Li; Xing Miao; Lei Yang; Longshan Lin (Reviews in Fish Biology and Fisheries, 2025)

Dynamics of the soil-rice interface in a Japonica rice rotation system: investigating silicon accumulation and soil labile silicon pools in depleted paddy systems of the Taihu Plain, China - Huang Sihua; Yumeng Lu; Qiqi Yang; Gaili He; Lu Qie; Jiayi Xie; Xiaoqing Wang; Rui Zhang; Ye Yuan; Jiahao Zhai; Rui Zhong; Jiawei Tao; et al. (Plant and Soil, 2025)

Transcriptome Profiling of the Primary and Crown Root in Response to Nitrate in Foxtail Millet (Setaria italica) - Xueting Kang; Jian-Hong Hao; Jiayi Chen; Xuan Zhou; Dan-Ying Chen; Rui Zhao; Ru Meng; Shuqi Dong; Xiangyang Yuan; Xiaorui Li; Lulu Gao; Guanghui Yang; et al. (Journal of Plant Growth Regulation, 2025)

Unprecedented triterpenes with anti-inflammatory activity from Limax maximus - Ya-feng Wang; Pei-de Tang; Rui-jie He; Zhang-bin Liu; Yong-qiong Wei; Jun Ruan; Bing-yuan Yang; Yong-lin Huang (Journal of Natural Medicines, 2025)

Efficient and selective gold recovery from practical e-waste and electroplating wastewater using protein crystals - Xiao-Qian Jin; Jia-Lei Li; Chen-Yuan Li; Liang-Liang Chen; Xue-Ting Wang; Wen-Pu Shi; Jun-Bin Xiong; Rui Zhang; Wei-Hong Guo; Da-Chuan Yin (Resources, Conservation and Recycling, 2025)

A vision foundation model-based method for large-scale forest disturbance mapping using time series Sentinel-1 SAR data - Yuping Tian; Feng Zhao; Ran Meng; Rui Sun; Yuan Zhang; Yanyan Shen; Bin Wang; Jie Liu; Mingze Li (Remote Sensing of Environment, 2025)

One-billion-year-old eukaryotic algal fossil Arctacellularia from North China and its implications for the evolution of pre-Cryogenian filamentous multicellularity - Rui Huang; Guangjin Li; Jiayue Wang; Qing Tang; Mingyang Qiu; Qian Chen; Hanzhi Qu; Chengxi Wu; Wenfei Cui; Xianqin Yan; Chuanming Zhou; Xunlai Yuan; et al. (Precambrian Research, 2025)

Hydrodynamic and geomorphological responses of tidal flats to extreme climate events - Renzhi Li; Ya Ping Wang; Rui Yuan; Ning Zhao; Bixuan Tang; Zhixuan Feng; Bruno Castelle (Journal of Hydrology, 2025)

TBBPA induced hepatocyte ferroptosis by PCBP1-mediated ferritinophagy - Rui-Qi Liu; Yu-Tong Wu; Yue Cheng; Yuan-Hang Chang; Muhammad Asmat Ullah Saleem; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2025)

Virus communities rather than bacterial communities contribute more on nutrient pool in polluted aquatic environment - Qiaoling Yu; Xueqian Hu; Yuan Qian; Yu Wang; Chenwei Shi; Rui Qi; Petr Heděnec; Zhibiao Nan; Huan Li (Journal of Environmental Sciences, 2025)

Prediction and changing patterns of physicochemical properties of rice flour during radio frequency heating - Dongsheng Hu; Jiahong Yuan; Mengge Li; Yingqi Tian; Gaoji Yang; Liumin Fan; Rui Li; Shaojin Wang (Innovative Food Science & Emerging Technologies, 2025)

Adaptive neofunctionalization of ancestral CYP6SN2vB following duplication contributes to abamectin resistance in Chilo suppressalis Walker - Shuai Wang; Yuan Xie; Chong Liu; Jin-Wei Liu; Fang-Rui Guo; Song-Tao Qiao; Yu-Ji Xing; Shun-Fan Wu; Chris Bass; Cong-Fen Gao (Insect Biochemistry and Molecular Biology, 2025)

Surface seawater Chlorophyll-a variability in the South China Sea: Influence of pCO2 and co-varying environmental factors - Rui Wang; Xuegang Li; Jinming Song; Zhibo Wang; Guorong Zhong; Huamao Yuan; Liqin Duan (Environmental Research, 2025)

Corrigendum to “Infection mechanisms of Pochonia chlamydosporia: A breakthrough in Fasciola hepatica egg control” [Vet. Parasitol. 337 (2025)110463] - Luyao Hao; Hongyou Liu; Fengmiao Zhao; Yuan Ma; Zhengyi Li; Rui Wang (Veterinary Parasitology, 2025)

Infection mechanisms of Pochonia chlamydosporia: A breakthrough in Fasciola hepatica egg control - Luyao Hao; Hongyou Liu; Fengmiao Zhao; Yuan Ma; Zhengyi Li; Rui Wang (Veterinary Parasitology, 2025)

Fabrication of multifunctional sandwich-structured electrospun magnetic film for preventing postoperative recurrence of hepatocellular carcinoma and abdominal adhesions - Rui Wang; Xuanxuan Li; Liang Yan; Jinlong Hu; Haojie Lu; Jiaming Yao; Zhongxu Yuan; Jinshan Liu; Hongyu Xu; Xu Yan; Wenyong Wu; Baoqiang Cao (Chemical Engineering Journal, 2025)

Rapeseed transcription factor BnaC9bHLH35 promotes root growth and improves nitrogen use efficiency under low nitrate conditions - Qin-Xin Fang; Haokun Cheng; Zhongni Ma; Qiuyan Xu; Huanpeng Wang; Yunru Yan; Mengting Sun; Rui Wang; Wenlong Liu; Saeed Ullah; Yuhang Fan; Chunchun Huang; et al. (Theoretical and Applied Genetics, 2025)

Genome-wide characterization of soybean bile acid: sodium symporter genes reveals a positive role of GmBASS2-2 in salt stress response - Xunchao Zhao; Yan Zhang; Yuan Li; Xiuli Rui; Jie Wang; Yuhang Zhan; Yongguang Li; Xue Zhao; Yingpeng Han (Theoretical and Applied Genetics, 2025)

Correlation study of 5-HT in brain with cognitive function and anxious-like behavior in APP/PS1 transgene mice - Li Yuan; Linshan An; Rui Xie; Jiahong Cai; Dong Li; Xiaorong Chen; Wenjing Guo; Yinran Lin; Chunjing Zhu; Yongli Chang; Kunbo Wang; Weina Han; et al. (Sleep and Biological Rhythms, 2025)

Chemical constituents from the stems of Erythropalum scandens - Qiao-dan Pan; Yuan-he Huang; Li-yang Zhao; Wei-rui Wang; Bing-an Wei; Ying-ying Xu; Xian Wei (Phytochemistry Letters, 2025)

Study on the flame retarding mechanism of HFC-134a on hydrocarbon refrigerants - Rui Zhai; Xiang Li; Yuan Zhuang; Bin Ye; Xiangnong Liu; Qingqing Li; Lei Tang; Ke Wang (International Journal of Refrigeration, 2025)

In situ synthesized carbon quantum dots@metal organic framework via corroding Ni foam for efficient oxygen evolution reaction - Yuzhen Zhang; Huajun Zhou; Peihua Zhao; Kai Yuan; Rui Zhou; Hui Gao; Yongping Qu; Yanzhong Wang (Fuel, 2025)

Intelligent double-layer pads containing blueberry anthocyanins/citric acid/tricolor lake for chilled pork real-time freshness monitoring - Junna Sun; Ye Zhang; Rui Liu; Jian Du; Qingdai Liu; Tianxin Wang; Yuan Wang; Hao Wang (Food Chemistry, 2025)

The novel MAT1-1-2 gene of golden-flower fungus from fuzhuan brick tea is required for normal colony morphology and sexual development, and affects metabolism - Jie Wang; Rui Zhang; Zhenglin Fei; Changfa Yang; Yilong Li; Yaya Yuan; Qilan Hu; Caiyan Tang; Zhonghua Liu; Mingzhi Zhu; Yongyi Ge (Food Bioscience, 2025)

Migration of acrylamide from food contact paper products and preliminary risk assessment - Wei Liu; Dajin Yang; Ziyi Wang; Rong Zhao; Sai Fan; Rui Yuan; Ruiying Tu; Daoyuan Yang; Jie Gao; Haixia Sui (Food Packaging and Shelf Life, 2025)

Metabolic and ecological responses of denitrifying consortia to different carbon source strategies under fluctuating C/N conditions - Rui-Zhe Sun; Yuan Pan; Jun Wang; Tong Gao; Han-Qing Yu; Jin Wang (Environmental Research, 2025)

Understanding the role of plastic additives in the pyrolysis of plastic wastes: Impact of additives on product selectivity, kinetics, and mechanistic pathways - Letian Zhang; Nan Zhou; Linyao Ke; Yuan Zeng; Qiuhao Wu; Jiahui Zhang; Rui Liao; Liangliang Fan; Krik Cobb; Roger Ruan; Yuhuan Liu; Yunpu Wang (Chemical Engineering Journal, 2025)

Multi-shank flexible implantable neural interface for long-term olfactory neuron recording toward odor perception - Qunchen Yuan; Jiale Wang; Chunlian Qin; Shunuo Shang; Haoze Xu; Fan Wu; Yong Qiu; Haoting Zhang; Rui Sun; Ping Wang; Liujing Zhuang; Hao Wan (Chemical Engineering Journal, 2025)

Comparative study on the effect of H2O/air/CO2 on the gasification results of wheat straw - Shuxiao Wang; Dexin Kong; Rui Shan; Jing Gu; Haoran Yuan; Yong Chen (Biomass and Bioenergy, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

A case study on facing climate change: optimizing planting density and date of summer maize for stable grain yield in the North China Plain - Zhendong Liu; Shiyu Wei; Xiudi Shangguan; Xin Wang; Meng Yuan; Rui Zong; Quanqi Li (Regional Environmental Change, 2025)

Antimicrobial Peptides: Classification, Mechanism, and Application in Plant Disease Resistance - Yuan-Zhen Wu; Jin Wang; Ying-Hui Hu; Qi-Shuo Sun; Rui Geng; Li-Na Ding (Probiotics and Antimicrobial Proteins, 2025)

Mesoscopic interpretation of fines clogging-induced permeability changes in completely decomposed granite - Rui Chen; Zhi-yuan Luo; Ai-guo Li; Hao Wang; Lei-lei Liu; Liang-liang Zhang (Bulletin of Engineering Geology and the Environment, 2025)

Development of a highly efficient seeding breeding system of Notopterygium incisum - Si Cheng Yao; Qiao Jia Peng; Na Su; Yuan Yuan Jiang; Jin Qiu Liao; Long Wang; Xue Xue Deng; Rui Wu Yang; Xiang Yun Chen; Li Zhang (Plant Biotechnology Reports, 2025)

Distribution, removal and potential factors affecting antibiotics occurrence in leachate from municipal solid waste incineration plants in China - Xuan Rui; Huabo Gong; Jinwen Hu; Haiping Yuan; Yawei Wang; Lixia Yang; Nanwen Zhu (Water Research, 2025)

Tracking of single virus: Dual fluorescent labeling of pseudorabies virus for observing entry and replication in the N2a cells - Mingzhi Li; Li Pan; Caoyuan Ma; Hongxia Wu; Guangtao Xiang; Lian-Feng Li; Tao Wang; Rui Luo; Yongfeng Li; Di Liu; Huanjie Zhai; Moon Assad; et al. (Veterinary Microbiology, 2025)

CYP321F3 mediates metabolic resistance to methoxyfenozide in rice stem borer, Chilo suppressalis - Fang-Rui Guo; Shu-Chao Wang; Yan Liu; Shuai Wang; Jing-Mei Huang; Hao Sun; Lin-Feng He; Yuan Xie; Song-Tao Qiao; Feng-Xia Yang; Chris Bass; Cong-Fen Gao; et al. (Pesticide Biochemistry and Physiology, 2025)

The Quanjishan Charnia assemblage from the northern Qaidam Basin, Tibetan Plateau, and implications for palaeoecology and taphonomy of Ediacaran fronds - Chengxi Wu; Alexander G. Liu; Yarong Liu; Xiaopeng Wang; Guangjin Li; Hanzhi Qu; Rui Huang; Mingyang Qiu; Wentao Zheng; Yunpeng Sun; Hongyi Shi; Qing Ouyang; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Study on the improvement of Rye bread quality by bacterial Laccase derived from Streptomyces coelicolor - Ran Zhang; Yanhua Li; Yuan Gao; Fengyun Wang; Peng Zhou; Yan Zhang; Ying Li; Kaiyue Wang; Ting Rui; Guilan Zhu; Jingjing Wang; Zemin Fang (Journal of Cereal Science, 2025)

Low perception of climate change by farmers and herders on Tibetan Plateau - Jiawei Yi; Yuan Tian; Nicholas P. Simpson; Yunyan Du; Ting Ma; Chengqun Yu; Talbot M. Andrews; Tao Pei; Xinjie Zha; Chenghu Zhou; Wei Sun; Shaowei Li; et al. (Global Environmental Change, 2025)

Inactivation activity and mechanism of natural antimicrobial agents against Alicyclobacillus spp. in apple juice - Rui Cai; Linlin Gao; Yuxiang Zhang; Lu Cui; Yahong Yuan; Zhouli Wang; Tianli Yue (Food Control, 2025)

Bacterial cellulose-based Pickering emulsions reinforced with silver and silica nanoparticles for advanced antibacterial and hydrophobic food packaging solutions - Qimin Chen; Fan Yang; Yalong Hou; Zhiyang Li; Di Yuan; Chao Liu; Feihong Hu; Rui Zhao; Huili Wang; Wenxia Liu; Fengshan Zhang; Qiang Wang; et al. (Carbohydrate Polymers, 2025)

Downregulation of HSPB1 and MGST1 Promotes Ferroptosis and Impacts Immune Infiltration in Diabetic Cardiomyopathy - Yaoli Xie; Bin Liang; Zhijun Meng; Rui Guo; Caihong Liu; Yi Yuan; Wei Mu; Yajing Wang; Jimin Cao (Cardiovascular Toxicology, 2025)

Applicability analysis of passive containment heat remove system calculation model based on integrated code - Nan Zhang; Shuai Yuan; Xiang Xia; Chang Wang; Rui Hao (Annals of Nuclear Energy, 2025)

Formation design for interplanetary shock imaging interferometric array - Yuan Wang; Li Deng; Jingye Yan; Rui Li; Xiucong Sun; Tianshan Dong; Shenggang Liu (Advances in Space Research, 2025)

TadpoleTraits : A Global Database on Morphological Traits of Tadpoles of Anura - Yanfang Song; Rui Tian; Yongle Wang; Pingfan Wei; Tao Zhang; Shuaiwei Luo; Zhiyong Yuan; Weiwei Zhou (Global Ecology and Biogeography, 2025)
Motivation Functional diversity is an important dimension of biodiversity. In animals, most species have complex life cycles, such that the same species can display great differences in traits and ecological roles across different life history stages. Consequently, the patterns and driving factors of functional diversity can vary considerably among the different life stages. However, research on stages other than adults is rare, with data scarcity being a potential reason. The order Anura of Amphibia is a highly diverse group of terrestrial vertebrates, comprising more than 7800 species. Anurans have complex life cycles, and our knowledge about functional traits of the larval stage is extremely limited. To fill this gap, we collected morphological traits of tadpoles globally and compiled a database covering 1993 species to facilitate future studies. This database can help us gain a more comprehensive understanding of anuran biodiversity. Additionally, it offers a valuable tool for testing ecological and evolutionary hypotheses related to complex life cycles in animals. Main Types of Variables Contained Twenty‐three traits collected from literature and 11 traits obtained by image measuring. Spatial Location and Grain Global. Major Taxa and Level of Measurement Anura, species. Software Format xlsx.

Experimental and Numerical Investigation on Mechanical Properties of Large-Diameter Metallurgically Clad Pipes - Feng Wang; Yanan Gao; Zhiguo Hu; Shuo Yang; Zhenying Cui; Rui Fu; Lin Yuan (Journal of Marine Science and Engineering, 2025)
Bimetallic-clad pipes demonstrate exceptional advantages in transporting corrosive oil and gas through the combination of the load-carrying capacity of the base material and the anti-corrosive function of the thin layer of corrosion-resistant alloy. This study investigates the mechanical properties of 24-inch X65 + Alloy625 metallurgically clad pipes through experimental tests and finite element analysis. Uniaxial tensile testing with digital image correlation reveals uniform deformation between the base and clad layers until interfacial failure initiates at an average strain threshold of 34.17%. Microstructural characterization shows continuous metallurgical bonding, with the X65 layer exhibiting polygonal ferrite and bainitic phases, contrasting with the austenitic equiaxed grain structure of Alloy625. In terms of numerical modeling, finite element analyses that consider both initial geometric imperfections and manufacturing-induced residual stresses are performed to evaluate the bending response of the clad pipe. The effect of initial ovality and residual stresses on its bending capacity is also studied.

Based on NRCS and the Doppler centroid anomaly in SAR images to retrieve the nearshore bathymetry - Rui Qi; Jiamin Lin; Jian Wang; Xiaonan Yao; Xiaoqing Wang; Xinzhe Yuan; Lei Cui; Peiqing Yang; Xingyi Su (International Journal of Remote Sensing, 2025)

The Effect of the Marine Environment on the Distribution of Sthenoteuthis oualaniensis in the East Equatorial Indian Ocean - Shigang Liu; Liyan Zhang; Peng Lian; Jianhua Kang; Puqing Song; Xing Miao; Longshan Lin; Rui Wang; Yuan Li (Fishes, 2025)
Sthenoteuthis oualaniensis is one of the most commercially important marine cephalopod species distributed throughout tropical and subtropical waters of the Indo-Pacific Seas. The Indian Ocean is a main fishing ground for S. oualaniensis with a high population density. To explore the distribution of S. oualaniensis in the east equatorial Indian Ocean, four surveys were carried out using light-lift-net fishing vessels. Meanwhile, marine environmental data were also collected, including the sea surface temperature, sea temperature at 100 m depth, mixed layer depth, sea surface chlorophyll-a concentration, sea surface height, and eddy kinetic energy. Generalized Additive Models were used to analyze the relationship between the catch per unit effort (CPUE) for S. oualaniensis and environmental factors. The results showed that the average CPUE of S. oualaniensis was 14.55 kg/h in the four surveys, which was considerably lower than in the South China Sea and Northwest Indian Ocean. In terms of seasonal distribution, the high-CPUE stations were closer to the continental shelf in spring, while they shifted towards the deeper and offshore water in autumn, demonstrating a seasonal migration trend. Pearson correlation analysis showed that CPUE reflected a significant negative correlation with both sea temperature at 100 m depth and eddy kinetic energy (p

Promotional role of Ru in bimetallic catalysts for selective transfer hydrogenation of bio-based furfural - Yaoxin Xiao; Yazhuo Wang; Jun Zhang; Gangqi Cheng; Dong Liang; Rui Shan; Haoran Yuan; Yong Chen (Journal of Environmental Chemical Engineering, 2025)

Biochar-supported Fe₃O₄ nanoparticles affects bacterial community diversity and phosphorus speciation transformation during pig manure aerobic composting by generating hydroxyl radicals and hydrogen peroxide - Ning Yuan; Kang Wang; Jia Zhou; Nana Luo; Rui Yu (Journal of Environmental Chemical Engineering, 2025)

The research on the synergistic improvement of water retention capacity and eating quality of marinated pork meat by the combination of basic arginine and acidic aspartic acid - Kuo Xu; Ao-Jing Lv; Rui-Ling Dong; Yu-Cong Li; Li-Ting Zeng; Yang Wang; He-Shuai Li; Jun Qi; Hu-Hu Wang; Chun-Hui Zhang; Guo-Yuan Xiong; Qing-Yong Zhang (Food Chemistry, 2025)

Expanding glacial lakes and assessing outburst susceptibility of moraine-dammed lakes using logistic regression in the Yigong Tsangpo Basin, Tibet, China - Ziyang Yuan; Rui Wang; Wei Zhou; Ningsheng Chen; Runfang Liu; Jinzhu Mao; Tao Wang (Natural Hazards, 2025)

Unraveling Neurotoxicity Discrepancies: Comparative In vitro and In vivo Analysis of Colistin and Polymyxin B and the Underlying Mechanisms - Rui Yang; Debiao Xiang; Fang Yuan; Yuan Yang; Pengkai Wang; Bing Xu; Xin Li (Molecular Neurobiology, 2025)

Association between sleep quality and serum biomarkers among long-term hot spring bathers: a cross-sectional study - Fen Yang; Yue Zou; Ying-ying Zhang; Hong-xia Li; Yi-hang Xu; Bao-chao Zhang; Lin-xuan Liao; Meng-xi Cao; Rui-xue Wang; Yuan Yuan; Yun Zhou; Da-yong Zeng; et al. (International Journal of Biometeorology, 2025)

Botryorhodine J, a new anti-MRSA depsidone isolated from endophytic fungus Alternaria alternata Pas11 - Wen-Yuan Li; Cheng-Cheng Hu; Jin-Hai Liu; Heng-Jie Wang; Ling-Pan Lu; Min Qiao; Ya-Ling Jiang; Rui Wu (Natural Product Research, 2025)

Pre-industrial Common Era temperature fluctuations in South China inferred based upon bacterial tetraether lipids from Lake Poyang - Rui Miao; Hong Yang; Qin Leng; Yuwei Chen; Shangbin Xiao; Xiaoke Qiang; Xiangzhong Li; Yuan Yao; Zenghao Zhao; Hongxuan Lu; Zhonghui Liu; Huanye Wang; et al. (Quaternary Science Reviews, 2025)

RNA interference-mediated silencing of GNBP2 reduces the immunity of stored pest Tribolium castaneum against bacteria - Jingxiu Bi; Xiangjun Ma; Yuying Jiang; Pingxiang Liu; Rui Gao; Tong Zhao; Xuexia Yuan; Haining Hao; Bin Li; Yutao Wang (Pesticide Biochemistry and Physiology, 2025)

Insight into resistance relaxation characteristics of proton exchange membrane fuel cell in purge operation: Experiment, application, and mechanisms - Yuqing Li; Hao Yuan; Xueyuan Wang; Xuezhe Wei; Jiangong Zhu; Rui Ma; Lei Gao; Haifeng Dai (Journal of Cleaner Production, 2025)

Inactivation activity and mechanism of high-voltage pulsed electric fields combined with antibacterial agents against Alicyclobacillus spp. in apple juice - Rui Cai; Zhihuan Jing; Yue Li; Xinyi Zhong; Qingling Sheng; Tianli Yue; Zhouli Wang; Yahong Yuan (International Journal of Food Microbiology, 2025)

A fluorescent aptasensor for deoxynivalenol detection based on Nb.BbvCI-assisted targeted-responsive three-way junctions integrated DNA walking machine - Kai Wang; Xiaohai Yan; Jiamin Wu; Jianrui Qi; Mengge Ning; Menghui Li; Rui Sun; Zhouli Wang; Yahong Yuan; Tianli Yue (Food Chemistry, 2025)

A rapid and nondestructive quantitative detection method for total and organic selenium in selenium-enriched kefir grain based on hyperspectral imaging - Menghui Li; Jinyi Yang; Xing Guo; Rui Sun; Gechao Zhang; Wenhui Liu; Yuanye Liu; Zhouli Wang; Yahong Yuan; Tianli Yue (Food Control, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Thermally driven organic-inorganic interactions in sedimentary basins: A review from source rocks to reservoirs - Guanghui Yuan; Yingchang Cao; Zhijun Jin; Hans-Martin Schulz; Zihao Jin; Rui Fang; Xiaoyang Zhao; Keyu Liu; Jixuan Wang (Earth-Science Reviews, 2025)

Effect of torrefaction pretreatment on catalytic pyrolysis of bagasse: A study on torrefaction method and atmosphere - Rui Liao; Xiaojie Tian; Liangliang Fan; Hui Li; Yuan Zeng; Linyao Ke; Qiuhao Wu; Roger Ruan; Yuhuan Liu; Yunpu Wang (Chemical Engineering Journal, 2025)

Facile aqueous fabrication of superhydrophobic carbon black-based photothermal melamine sponge for multi-state oil cleanup - Meile Gong; Yuan Meng; Tianke Wang; Wandi Zhang; Rui Xie; Zhao Wang (Chemical Engineering Journal, 2025)

Dynamics of soil phosphorus fractions during the early recovery stage of two typical plantations in China after strip clearcutting - Linhui Zhang; Jihong Li; Su Chen; Wenlan Huang; Lulu Huang; Hongfeng Zhu; Yuanxiang Tang; Han Li; Chengming You; Lixia Wang; Sining Liu; Hongwei Xu; et al. (CATENA, 2025)

Shifting soil N regimes over a 70-year chronosequence of wetland reclamation and restoration - Kexin Li; Nannan Wang; Rui Su; Yunjiang Zuo; Jianzhao Liu; Ying Sun; Xinhao Zhu; Ziyu Guo; Lihua Zhang; Changchun Song; Ning Chen; Sergei Lupakov; et al. (CATENA, 2025)

The Impact of Different Mating Systems on Locomotion in Drosophila melanogaster - Rui Han; Jun Zhang; Ruo-Xi Wang; Jia-Xin Xu; Kai-Chen Weng; An-Xin Wang; Hao Huang; Yu-Yuan Lu; Yi-Jie Chen; Yu-Chen Wang (Journal of Insect Behavior, 2025)

Antagonistic activity of Pochonia chlamydosporia against three helminth eggs and characterization of its serine protease - Luyao Hao; Fengmiao Zhao; Yuan Guo; Yuan Ma; Zhengyi Li; Wen Wang; Hongliang Luo; Rui Wang (Veterinary Parasitology, 2025)

Fertilization effects on soil organic matter chemistry - Dengjie Zhou; Rui Mou; Lihua Wang; Jingru Liu; Yuanxiang Tang; Ji Chen; Petr Heděnec; Zhenfeng Xu; Bo Tan; Xinglei Cui; Han Li; Li Zhang; et al. (Soil and Tillage Research, 2025)

Insights into the photoaging behavior of biodegradable and nondegradable microplastics: Spectroscopic and molecular characteristics of dissolved organic matter release - Xiaoyang Wu; Yifan Liu; Yaofeng Jin; Yue Wang; Mengjie Yuan; Kunyu He; Xiaoyan Zhang; Qin Chen; Zhijing Xue; Rui Wang; Xiaoyun Li (Journal of Hazardous Materials, 2025)

Development and characterization of a γ-PGA/PVA/SDBS cross-linked network foam for dust suppression in tunneling construction - Xinjiao Tian; Yixiang Huang; Qiang Zhang; Hongxiang Wang; Jinqian Zeng; Chaoqun Yuan; Jiefeng Pan; Rui Wang; Zhenming Li (Journal of Environmental Chemical Engineering, 2025)

A rapid and sensitive sandwich assay for the detection of Alicyclobacillus acidoterrestris in apple juice based on magnetosome immunomagnetic separation combined with quantum dots immunoassay technology - Jianrui Qi; Kai Wang; Xiaohai Yan; Xinru Dong; Rui Sun; Yahong Yuan; Tianli Yue (Food Chemistry, 2025)

Precise and panoramic study on the nutritional components of specific milk of goats and sheep - Xiaowei Wang; Qian Li; Qiu Zhang; Yanzhi Wu; Rui Chen; Yinggang Sun; Yuan Pan; Siyi Li; Zeying Wang (Food Chemistry, 2025)

Corrigendum to “Probiotics encapsulated by gelatin and hyaluronic acid via layer-by-layer assembly technology for enhanced viability” [Food Hydrocolloids 153 (August 2024), 109967] - Leran Wang; Xinyi Zhong; Shiqi Li; Xiaoshuang Liu; Kai Wang; Rui Cai; Tianli Yue; Yahong Yuan; Zhouli Wang (Food Hydrocolloids, 2025)

Roles of S100A1 and S100A10 from hybrid grouper (Epinephelus lanceolatus♂ × Epinephelus fuscoguttatus♀) in immune response to Vibrio infection - Sheng Yuan; Ying Huang; Quan Wang; Yan Shi; Xiao-Rui Song; Zhe Zhao (Fish & Shellfish Immunology, 2025)

Global identification and regulatory network analysis reveal the significant roles of lncRNAs during anther and pollen development in Arabidopsis - Dong Zhou; Ruiqi Song; Yuan Fang; Rui Liu; Chenjiang You; Yijie Wang; Li Huang (Plant Cell Reports, 2025)

The Effect of Disc Degeneration on the Biomechanical Response of the Lumbar Spine under Vibration Loading Condition - Bin Zhang; Tian-Cheng Li; Xin Wang; Rui Zhu; Cheng-Fei Du; Yuan Xie (Journal of Medical and Biological Engineering, 2025)

The long noncoding RNA ALEX1 confers a functional phase state of ARF3 to enhance rice resistance to bacterial pathogens - Meng-Qi Lei; Rui-Rui He; Yan-Fei Zhou; Lu Yang; Zhen-Fei Zhang; Chao Yuan; Wen-Long Zhao; Yu Cheng; Jian-Ping Lian; Yu-Chan Zhang; Wen-Tao Wang; Yang Yu; et al. (Molecular Plant, 2025)

Effective removal of Pb from industrial wastewater: A new approach to remove Pb from wastewater based on engineered yeast - Hao Luo; Zheng Su; Yang Liu; Dong-Fang Yuan; Rui Wang; Yu-Hang Ning; Dong-Jiao Zhang; Xian-Ke Chen; Zhao-Bao Wang; Xue-Yan Gao; Yue-Chao Zhang; Guang Cheng; et al. (Journal of Hazardous Materials, 2025)

Designing double-layer smart packaging with sustained-release antibacterial and antioxidant activities for efficient preservation and high-contrast monitoring - Shiqi Li; Ling Liu; Silong Yang; Xingnan Wang; Yahong Yuan; Tianli Yue; Rui Cai; Zhouli Wang (Food Hydrocolloids, 2025)

A multirisk-rescued biomimetic nanozyme against periodontitis via inflammation targeting and microenvironment reprogramming - Lin Li; Rui-Xin Wu; Jia Wang; Rui Jin; Xin-Yu Zhang; Mei Xu; Si-Yao Li; Rui Gao; Bei-Min Tian; Xiao-Tao He; Fa-Ming Chen; Yuan Yin (Chemical Engineering Journal, 2025)

Enhancement of thermal conductivity of graphene-based phase change composites by alternating positive and negative pressures during perfusion - Ruichuan Li; Xianxian Sun; Rui Zhang; Shasha Wang; Qiqi Liu; Peijia Bai; Ye Yuan; Yibin Li (Chemical Engineering Journal, 2025)

Two novel butyrolactone lignan dimers from leaves of Castanopsis chinensis and their anti-inflammatory activities - Ya-Feng Wang; Ping Lin; Nao Pang; Zhang-Bin Liu; Bing-Yuan Yang; Rui-Jie He; Yong-Lin Huang (Journal of Natural Medicines, 2025)

Leifsonia stereocauli sp. nov., Isolated from Stereocaulon tomentosum Fr. Lichen - Shu-Ya Zuo; Lian-Shuang Xiong; Qing Yuan; Guo-Hua Chen; Rui Yang; Li-Song Wang; Cheng-Lin Jiang; Xin-Yu Wang; Yi Jiang (Current Microbiology, 2025)

Nanozymes featuring a mesoporous silica shell for rapid enrichment and ultrasensitive lateral flow immunoassay of influenza A - Jing Liang; Xiaoxian Liu; Zhenzhen Liu; Xuanming Xu; Yinuo Sun; Yuan Chen; Rui Xiao; Yajie Wang (Analytica Chimica Acta, 2025)

Heterogeneous precipitation behavior and mechanism during the adsorption of cationic heavy metals by biochar: Roles of inorganic components - Rui Han; Yuan Gao; Yongfeng Jia; Shaofeng Wang (Journal of Hazardous Materials, 2024)

AHR activation relieves deoxynivalenol-induced disruption of porcine intestinal epithelial barrier functions - Zi-Yan Hu; Shang-Jia Yang; Yuan-Hang Chang; Xue-Qi Wang; Rui-Qi Liu; Fu-Wei Jiang; Ming-Shan Chen; Jia-Xin Wang; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Yi Zhao; et al. (Journal of Hazardous Materials, 2024)

Exploring the dynamic characteristic of typical kombucha induced by symbiotic microbiota succession from four Chinese regions: A comprehensive analytical framework - Shiqi Li; Ruinan Wang; Rong Liu; Leran Wang; Xingnan Wang; Jianping Wei; Yahong Yuan; Tianli Yue; Rui Cai; Zhouli Wang (Food Research International, 2024)

Green fabrication of modified lignin/zeolite/chitosan-based composite membranes for preservation of perishable foods - Zhan-Chao Li; Meng-Yao Su; Xiao-Yu Yuan; Hai-Qing Lv; Rui Feng; Li-Jie Wu; Xiao-Ping Gao; Yan-Xia An; Zhan-Wei Li; Miao-Yun Li; Gai-Ming Zhao; Xiao-Peng Wang (Food Chemistry, 2024)

Metabolomic analysis of umami taste variation in Pyropia haitanensis throughout the harvest cycle - Zihan Yuan; Haibin Pan; Juanjuan Chen; Yuting Zhang; Qijun Luo; Rui Yang; Peng Zhang; Tiegan Wang; Haimin Chen (Food Chemistry, 2024)

Corrigendum to “A critical review on graphene oxide membrane for industrial wastewater treatment” [Environ. Res. 223 (2023) 115409] - Ye-Chen An; Xiao-Xu Gao; Wen-Li Jiang; Jing-Long Han; Yuan Ye; Tian-Ming Chen; Rui-Yun Ren; Jia-Hui Zhang; Bin Liang; Zhi-Ling Li; Ai-Jie Wang; Nan-Qi Ren (Environmental Research, 2024)

Iron-doped diesel exhaust early-in-life inhalation-induced cardiopulmonary toxicity in chicken embryo: Roles of ferroptosis and acyl hydrocarbon signaling - Siyi Wang; Xinxian Gong; Junhua Yuan; Jing Huang; Rui Zhao; Jing Ji; Meinan Wang; Xiaoyu Shi; Wenya Xin; Yuxu Zhong; Yuxin Zheng; Qixiao Jiang (Environmental Pollution, 2024)

Sub-millimeter scale 3D integration strategy enables ultrahigh-density and ultralow-crosstalk flexible tactile sensor array for robotic e-skin application - Shaoxiong Hu; Rui Wang; Wei Zhu; Yue Huang; Ying Li; Yuchen Yang; Qingqing Zhang; Yuedong Yan; Chen Lin; Yuan Deng (Chemical Engineering Journal, 2024)

Microwave pyrolysis of Choerospondias axillaris seeds with their derived biochar for comprehensive utilization of the biomass - Ruolan Zhou; Xiaojie Tian; Xiaofei Wang; Yuan Zeng; Linyao Ke; Qiuhao Wu; Rui Liao; Roger Ruan; Liangliang Fan; Yunpu Wang (Chemical Engineering Journal, 2024)

Different polysaccharide-enhanced probiotic and polyphenol dual-functional factor co-encapsulated microcapsules demonstrate acute colitis alleviation efficacy and food fortification - Rui Sun; Zhongyi Lv; Ying Wang; Menghui Li; Jianrui Qi; Kai Wang; Haihua Yang; Tianli Yue; Yahong Yuan (Carbohydrate Polymers, 2024)

Complex dynamic behavioral transitions in auditory neurons induced by chaotic activity - Guodong Huang; Shu Zhou; Rui Zhu; Yunhai Wang; Yuan Chai (BioSystems, 2024)

Circulating CD8 + LGALS9 + T Cell Population Exhibiting Low Cytotoxic Characteristics are Decreased in Patients with Systemic Lupus Erythematosus - Qi Li; Guochong Wang; Zihang Yuan; Rui Kang; Yaxin Li; Ayibaota Bahabayi; Ziqi Xiong; Zhonghui Zhang; Chen Liu (Immunologic Research, 2024)

Sirtuin 7 ameliorates cuproptosis, myocardial remodeling and heart dysfunction in hypertension through the modulation of YAP/ATP7A signaling - Yu-Fei Chen; Rui-Qiang Qi; Jia-Wei Song; Si-Yuan Wang; Zhao-Jie Dong; Yi-Hang Chen; Ying Liu; Xin-Yu Zhou; Jing Li; Xiao-Yan Liu; Jiu-Chang Zhong (Apoptosis, 2024)

Pilot study to reconstruct life history of Diaphus thiollierei from the Arabian Sea by otolith microstructure and microchemistry - Lisheng Wu; Wenxin Zhuang; Qiaohong Liu; Rui Wang; Yuan Li; Longshan Lin; Shufang Liu; Shaoxiong Ding (Acta Oceanologica Sinica, 2024)

Innovative beverage creation through symbiotic microbial communities inspired by traditional fermented beverages: current status, challenges and future directions - Shiqi Li; Xiaoshuang Liu; Leran Wang; Kai Wang; Menghui Li; Xingnan Wang; Yahong Yuan; Tianli Yue; Rui Cai; Zhouli Wang (Critical Reviews in Food Science and Nutrition, 2024)

Towards better understanding the urban environment and its interactions with regional climate change - The WCRP CORDEX Flagship Pilot Study URB-RCC - Gaby S. Langendijk; Tomas Halenka; Peter Hoffmann; Marianna Adinolfi; Aitor Aldama Campino; Olivier Asselin; Sophie Bastin; Benjamin Bechtel; Michal Belda; Angelina Bushenkova; Angelo Campanale; Kwok Pan Chun; et al. (Urban Climate, 2024)

Divergent responses of woody plant leaf and root non-structural carbohydrates to nitrogen addition in China: Seasonal variations and ecological implications - Rui Mou; Yi Jian; Dengjie Zhou; Jihong Li; Yao Yan; Bo Tan; Zhenfeng Xu; Xinglei Cui; Han Li; Li Zhang; Hongwei Xu; Lin Xu; et al. (Science of The Total Environment, 2024)

Peering through the hedge: Multiple datasets yield insights into the phylogenetic relationships and incongruences in the tribe Lilieae (Liliaceae) - Deng-Feng Xie; Juan Li; Jia-Hui Sun; Rui-Yu Cheng; Yuan Wang; Bo-Ni Song; Xing-Jin He; Song-Dong Zhou (Molecular Phylogenetics and Evolution, 2024)

Iron-modified biochars and their aging reduce soil cadmium mobility and inhibit rice cadmium uptake by promoting soil iron redox cycling - Tianren Si; Xin Chen; Rui Yuan; Siyu Pan; Yan Wang; Rongjun Bian; Xiaoyu Liu; Xuhui Zhang; Stephen Joseph; Lianqing Li; Genxing Pan (Journal of Environmental Management, 2024)

Multi-omics analysis of five species of milk and specific composition links within each species - Qian Li; Xiaowei Wang; Qiu Zhang; Yanzhi Wu; Rui Chen; Yinggang Sun; Yuan Pan; Siyi Li; Zeying Wang (Food Chemistry, 2024)

Molecular characterization, spatio-temporal expression patterns of crtc2 gene and its immune roles in yellow catfish (Pelteobagrus fulvidraco) - Wan-Hong Zeng; Zheng-Yong Wen; Xiu-Ying Wei; Yu He; Luo Zhou; Peng Hu; Qing-Chao Shi; Chuan-Jie Qin; Jun Wang; Rui Li; Xiao-Ying Jing; Wei Hu; et al. (Fish & Shellfish Immunology, 2024)

Dynamics of impure CO2 and composite oil in mineral nanopores: Implications for shale oil recovery and gas storage performance - Lu Wang; Run Zou; Yifan Yuan; Yifan Zhang; Rui Zou; Liang Huang; Yisheng Liu; Zhan Meng; Hao Chen (Chemical Engineering Journal, 2024)

Rational design of pulse-electrolysis protocols promotes molten-salt electrorefining - Leyang Li; Ruiyang Sun; Rui Yuan; Manpeng Lin; Linlin Wang; Qi Wang; Jiguo Tu; Handong Jiao; Shuqiang Jiao (Chemical Engineering Journal, 2024)

Tuning local charge polarization of covalent organic frameworks for enhanced photocatalytic uranium (VI) reduction - Xiao-Xing Wang; Cheng-Rong Zhang; Rui-Xiang Bi; Zhi-Hai Peng; Hao-Xuan He; Rui Zhang; An-Min Song; Jia-Xin Qi; Xiao-Juan Chen; Xin Liu; Yuan-Jun Cai; Ru-Ping Liang; et al. (Chemical Engineering Journal, 2024)

Comprehensive investigation of daytime radiative cooling technology for sustainable grain storage: A combined approach of field measurement and CFD simulations - Chongjia Lin; Yunlong Wang; Zhihang Zhao; Xisheng Lin; Rui Li; Zhaoping Zheng; Xuhua Shen; Zhongqing Lang; Weizhi Zhou; Jinbei Wang; Dan Yuan; Yankai Sun; et al. (Building and Environment, 2024)

Yr29 combined with QYr.nwafu-4BL.3 confers durable resistance to stripe rust in wheat cultivar Jing 411 - Mingjie Xiang; Bo Tian; Jianghao Cao; Shengjie Liu; Caie Zhou; Xiaoting Wang; Yibo Zhang; Jiale Li; Xunying Yuan; Jufen Wan; Rui Yu; Weijun Zheng; et al. (Theoretical and Applied Genetics, 2024)

Soil organic phosphorus is mainly hydrolyzed via phosphatases from ectomycorrhiza-associated bacteria rather than ectomycorrhizal fungi - Jing Yuan; Rui Yan; Xueqiong Zhang; Kai Su; Hui Liu; Xin Wei; Ran Wang; Lanlan Huang; Nianwu Tang; Shanping Wan; Wei Liu; Hans Lambers; et al. (Plant and Soil, 2024)

Deltamethrin increased susceptibility to Aeromonas hydrophila in crucian carp through compromising gill barrier - Xiping Yuan; Hao Wu; Jinwei Gao; Can Yang; Zhenzhen Xiong; Jiayu Wu; Chongrui Wang; Dong Liu; Jianzhong Shen; Rui Song (Chemosphere, 2024)

Exploration of hydrogen-rich gas evolution mechanism during vitrinite pyrolysis: A combined TG-MS and ReaxFF study - Yuan-Yuan Jiang; Jie-Ping Wang; Jin-Xiao Dou; Rui Guo; Li-Hua Fan; Guang-Yue Li; Ying-Hua Liang; Jiang-Long Yu (Fuel, 2024)

Antimicrobial activity and mechanism of chitosan-coated epsilon-poly-lysine nanoliposomes against Alicyclobacillus spp. in apple juice - Rui Cai; Yunhao Liang; Yahong Yuan; Qingling Sheng; Zhouli Wang; Tianli Yue (Food Control, 2024)

“Fast-charging” mechanism of Li3VO4 from the perspective of material science for lithium-ion battery - Rui Wang; Yuan Li; Gaoyang Li; Yihan Fu; Youzhi Wu; Fen Ran (Chemical Engineering Journal, 2024)

The LINGO-1-deficient neural stem cell-derived neural tissueoid showed enhanced retention and neuronal relay in the transected spinal cord - Ge Li; Li-Jun Huang; Bao Zhang; Shu Liu; Jing-Hua Liang; Ying Ding; Xiang Zeng; Bi-Qin Lai; Yuan-Huan Ma; Ya-Qiong Wang; Rui Wang; Hong-Bo Zhang; et al. (Chemical Engineering Journal, 2024)

Suppression the glucose-induced ferroptosis in endothelial cells by 4OI-loading exosomes hydrogel for the treatment of diabetic foot ulcer - Kuo Shen; Rui Zheng; Bangrui Yu; Hao Zhang; Peng Wang; Peng Zhao; Jijun Chen; Yixuan Yuan; Yuhang Wang; Kejia Wang; Yanhui Jia; Ruizhi Wang; et al. (Chemical Engineering Journal, 2024)

Enhancing reaction kinetics in aprotic magnesium-air batteries using a freestanding flexible metal-free carbon fiber cathode - Wenbo Liu; Ning Wang; Rui Zhong; Fanfan Liu; Yongjun Wu; Qianyi Zhang; Xiaoyan Chen; Yanmei Li; Minghui Yu; Rui Xu; Yifei Yuan; Dan Luo; et al. (Chemical Engineering Journal, 2024)

A study on the monitoring of landslide deformation disasters in Wenxian County, Longnan City based on different time-series InSAR techniques - Jinlong Zhang; Rui Yang; Yuan Qi; Hui Zhang; Juan Zhang; Qianhong Guo; Chao Ma; Hongwei Wang (Natural Hazards, 2024)

RIP3 regulates doxorubicin-induced intestinal mucositis via FUT2-mediated α-1,2-fucosylation - Wei Wen; Xiaomin Hu; Jialin Liu; Fanxin Zeng; Yihua Xu; Ye Yuan; Chunyan Gao; Xueting Sun; Bo Cheng; Jue Wang; Xinli Hu; Rui-Ping Xiao; et al. (Inflammation Research, 2024)

Association of prenatal multiple metal exposures with child neurodevelopment at 3 years of age: A prospective birth cohort study - Yun Qiu; Yuxin Liu; Ming Gan; Weiting Wang; Tao Jiang; Yangqian Jiang; Hong Lv; Qun Lu; Rui Qin; Shiyao Tao; Lei Huang; Xin Xu; et al. (Science of The Total Environment, 2024)

Degradation of mycotoxins by pulsed light and evaluation of the safety of degradation products - Lige Qi; Xinyi Zhong; Linlin Gao; Rui Cai; Tianli Yue; Yahong Yuan; Zhouli Wang; Xubo Zhao (Journal of Food Engineering, 2024)

TiO2 thermal stress deformation induced to promote photocatalytic CO2 reduction - Yixuan Shen; Kaifeng Gong; Le Chen; Jiafan Wang; Tao Wang; Yuan Gao; Jie Niu; Rui Zhu; Qizhen Liu; Jiang Wu; Ping He (Fuel, 2024)

Enzymatically green-produced bacterial cellulose nanoparticle-stabilized Pickering emulsion for enhancing anthocyanin colorimetric performance of versatile films - Shiqi Li; Rong Liu; Jiale Zhao; Shuo Zhang; Xuerong Hu; Xingnan Wang; Zhenpeng Gao; Yahong Yuan; Tianli Yue; Rui Cai; Zhouli Wang (Food Chemistry, 2024)

Immobilization of pancreatin based on ultrasound-assisted polydopamine functionalized magnetic porous chitosan for the detoxification of ochratoxin A in wine - Saiqun Wang; Tianmin Guo; Xiaoxue Mei; Xinyi Zhong; Linlin Gao; Rui Cai; Tianli Yue; Yahong Yuan; Zhenpeng Gao; Zhouli Wang (Food Chemistry, 2024)

Ion confinement effect enabled by carboxymethyl cellulose/tannic acid hybrid hydrogel electrolyte toward stable zinc anode - Xiangye Li; Yuan Li; Rui Wang; Dahui Wang; Fen Ran (Chemical Engineering Journal, 2024)

Wearable hydrogel-based health monitoring systems: A new paradigm for health monitoring? - Xintao Wang; Haixia Ji; Li Gao; Rui Hao; Ying Shi; Junyan Yang; Yuan Hao; Jiahui Chen (Chemical Engineering Journal, 2024)

A versatile bilayer smart packaging based on konjac glucomannan/alginate for maintaining and monitoring seafood freshness - Shiqi Li; Xuerong Hu; Shuo Zhang; Jiale Zhao; Ruinan Wang; Leran Wang; Xingnan Wang; Yahong Yuan; Tianli Yue; Rui Cai; Zhouli Wang (Carbohydrate Polymers, 2024)

Analyzing fishery data and exploring the resource status of Antarctic krill based on its environmental dependence - Rui Wang; Shigang Liu; Ran Zhang; Hai Li; Puqing Song; Yuan Li; Longshan Lin (Fisheries Oceanography, 2024)
Antarctic krill Euphausia superba is a key species in the Southern Ocean ecosystem and has important ecological value. It is also one of the main fishery resources in the Southern Ocean with high economic value. In recent years, with the development of krill fishery and rapid climate change, the conservation and management of krill resources have faced unprecedented challenges. The krill resource is different from the general fishery resources. Due to the krill schooling characteristics, fishery data has some advantages over scientific survey data. Reviewing and analyzing the krill fishery data is necessary. Therefore, in this study, four fishery resource indices (FRIs) were calculated based on Antarctic krill fishery data, and based on the environmental dependence of Antarctic krill, the FRI with the strongest environmental dependence was screened by using the Gradient Forest Model, and the step changes of the FRI with strongest environmental dependence was examined by using the sequential t‐test analyses of regime shifts (STARS). The generalized additive model (GAM) to analyze the correlation between the FRI with the strongest environmental dependence and the main environmental factors, and then explore the resource status of Antarctic krill in the study area. The model results showed that the “FRI_hual” had the strongest environmental dependence and was a better indicator of the status of the Antarctic krill in the study area than the others. In the 2009–2010 year, “FRI_hual” had an obvious regime shift. The interaction of environmental factors “ice_area_2” and “SSH_1” has a great impact on “FRI_hual”. Methods used and results obtained in the study can provide new ideas and a scientific reference for future work, including integrated stock assessment of krill and krill resource monitoring, conservation, and management based on the ecosystem.

Correction: Decoupling and decomposition analysis of industrial carbon emissions and economic growth in China from a dynamic perspective - Ye Yuan; Yumeng Lu; Jiayi Xie; Jiawei Tao; Xiaowei Chuai; Sihua Huang; Rui Zhang; Jiahao Zhai; Xiaoqing Wang; Lijie Pu (Environment, Development and Sustainability, 2024)

Improving effect of N-acetylcysteine on growth and intestinal health in juvenile Cyprinus carpio involve the Nrf2/MAPK/NF-κB pathways - Rui Zhu; Deng-Lai Li; Bao-Yuan Zhang; Liang Li; Guo-Jun Shang; Hao-Tong Wang; Zhi-Yong Yang; Xiao-fang Wei; Si-Tong Meng; Si-Ying Liu; Yin-Tao Wang; Li-Fang Wu; et al. (Aquaculture, 2024)

MARCH1 and MARCH2 inhibit pseudorabies virus replication by trapping the viral cell-to-cell fusion complex in trans-Golgi network - Rui Huang; Cui-Hong Rao; Yuan-Zhe Bai; Changqing Yu; Meng Chen; Jin-Mei Peng; Shi-Jia Xu; Yue Sun; Meng Fandan; Chuang Lyu; Mirwaise Khan; Tong-Qing An; et al. (Veterinary Microbiology, 2024)

Quartz trace element geochemistry and internal morphology as proxies for provenance characterization: Results from the Marwar basin, NW India - Jun Zhang; Rui Li; Manoj K. Pandit; Ting-Guang Lan; Qing Xiong; Yuan-Bao Wu; Jun-Hong Zhao; Wei Wang (Precambrian Research, 2024)

The transport of bismuth in HCl-bearing aqueous vapour and low-density aqueous supercritical fluids: Implications for natural systems - Xin-Song Wang; A.E. Williams-Jones; Rui-Zhong Hu; Qi Liu; Fei-Xiang Liu; Yuan Mei; Zi-Qi Jiang; Lin-Bo Shang; Jing-Jing Zhu; Xian-Wu Bi (Geochimica et Cosmochimica Acta, 2024)

Probiotics encapsulated by gelatin and hyaluronic acid via layer-by-layer assembly technology for enhanced viability - Leran Wang; Xinyi Zhong; Shiqi Li; Xiaoshuang Liu; Kai Wang; Rui Cai; Tianli Yue; Yahong Yuan; Zhouli Wang (Food Hydrocolloids, 2024)

Manganese oxides/graphene aerogels as lightweight microwave absorbers for extreme environment application - Jieping Wang; Shaohua Shi; Yongzhu Yan; Gengping Wan; Haoxiang Zhai; Xiang Yuan; Liang Li; Changlong Du; Rui Liu; Guizhen Wang (Chemical Engineering Journal, 2024)

Computational biology-based study of the molecular mechanism of spermidine amelioration of acute pancreatitis - Yan Shen; Hongtao Duan; Lu Yuan; Aiminuer Asikaer; Yiyuan Liu; Rui Zhang; Yang Liu; Yuanqiang Wang; Zhihua Lin (Molecular Diversity, 2024)

Distribution, risk evaluation, and source allocation of cesium and strontium in surface soil in a mining city - Jia-li Li; Chun-dan Gan; Xin-yue Du; Xue-ying Yuan; Wen-lin Zhong; Meng-qi Yang; Rui Liu; Xiao-yu Li; Hao Wang; Yu-liang Liao; Zheng Wang; Mu-cheng Xu; et al. (Environmental Geochemistry and Health, 2024)

Effect of internal and external chaotic stimuli on synchronization of piezoelectric auditory neurons in coupled time-delay systems - Guodong Huang; Shu Zhou; Rui Zhu; Yunhai Wang; Yuan Chai (Cognitive Neurodynamics, 2024)

Decoupling and decomposition analysis of industrial carbon emissions and economic growth in China from a dynamic perspective - Ye Yuan; Yumeng Lu; Jiayi Xie; Jiawei Tao; Xiaowei Chuai; Sihua Huang; Rui Zhang; Jiahao Zhai; Xiaoqing Wang; Lijie Pu (Environment, Development and Sustainability, 2024)

Quercetin regulates dendritic cell activation by targeting STAT4 in the treatment of experimental autoimmune encephalomyelitis - Fang Zhou; Yu-Xin Guo; Rui Gao; Xiao-Yu Ji; Yu-Xuan Tang; Li-Bin Wang; Yuan Zhang; Xing Li (Toxicology and Applied Pharmacology, 2024)

SAD2 functions in plant pathogen Pseudomonas syringae pv tomato DC3000 defense by regulating the nuclear accumulation of MYB30 in Arabidopsis thaliana - Tiantian Shi; Yuan Zheng; Rui Wang; Sha Li; Andi Xu; Luoying Chen; Yuanhang Liu; Rong Luo; Chenchen Huang; Yinglu Sun; Jinfeng Zhao; Xiaoying Guo; et al. (Plant Science, 2024)

Phyllanthus emblica Linn: A comprehensive review of botany, traditional uses, phytonutrients, health benefits, quality markers, and applications - Qin-Ge Ma; Lei Wang; Rong-Hua Liu; Jin-Bin Yuan; Hui Xiao; Zhang-Yang Shen; Jia-Xin Li; Jia-Zeng Guo; Lan Cao; Hui-Lian Huang; Rong-Rui Wei (Food Chemistry, 2024)

Metagenomic data highlight shifted nitrogen regime induced by wetland reclamation - Kexin Li; Nannan Wang; Fenghui Yuan; Xinhao Zhu; Yunjiang Zuo; Jianzhao Liu; Ziyu Guo; Ying Sun; Rui Su; Lihua Zhang; Sergei Lupakov; Yanyu Song; et al. (Biology and Fertility of Soils, 2024)

Attitude inversion of space debris based on the laboratory-tested photometry dataset - Shu-Shu Wang; Hou-Yuan Lin; An-Ming Kang; Jin-Rui Men; Chang-Yin Zhao (Advances in Space Research, 2024)

AKR1C2 genetic variants mediate tobacco carcinogens metabolism involving bladder cancer susceptibility - Yanping Xiao; Yang Shen; Hui Song; Fang Gao; Zhenguang Mao; Qiang Lv; Chao Qin; Lin Yuan; Dongmei Wu; Haiyan Chu; Meilin Wang; Mulong Du; et al. (Archives of Toxicology, 2024)

Three new quinic acid derivatives and a new shikimic acid derivative from the leaves of Castanopsis orthacantha - Xue-Xue Cheng; Ya-Feng Wang; Rui-Jie He; Bing-Yuan Yang; Zhang-Bin Liu; Yong-Lin Huang (Phytochemistry Letters, 2024)

Research on the effect of shallow draft on the performance of azimuth thruster under bollard conditions - Heng Li; Jian-Qiang Wang; Xue-Qin Liu; Guo-Rui Ji; Yan Zhang; Zhi-Yuan Wei (Ocean Engineering, 2024)

Inactivation of microorganisms on fabrics using plasma-activated nebulized mist driven by different plasma gases - Pengyu Zhao; Sihong Ma; Li Guo; Yikang Jia; Rui Zhang; Min Chen; Zifeng Wang; Dingxin Liu; Yuan Zhao; Xiaohua Wang; Mingzhe Rong (Journal of Hazardous Materials, 2024)

Hydration properties and mesoscopic structures of different depolymerized konjac glucomannan: Experiments and molecular dynamics simulations - Yi Zhao; Juan Wang; Yuan Zhang; Rui He; Yuming Du; Geng Zhong (Food Hydrocolloids, 2024)

Enteral nutrition in the management of acute pancreatitis: Modulates gut microbiome and alleviates inflammation - Fang-Yuan Yang; Yi-Jing Cai; Xiao-Ying Niu; Shun-Fu Wang; Yu-Qi Wang; Sabola Eluby Esmie; Rui-Cong Chen; Sheng-Jie Dai; Hong-Ru Kong; Hong-Wei Sun; Ke-Qing Shi (Food Bioscience, 2024)

Cellulose-based magnetic nanomaterials immobilized esterases as a reusable and effective detoxification agent for patulin in apple juice - Xiaoshuang Liu; Linlin Gao; Shiqi Li; Leran Wang; Rui Cai; Tianli Yue; Yahong Yuan; Xubo Zhao; Zhouli Wang (Food Control, 2024)

Implantation of Adipose-Derived Mesenchymal Stromal Cells (ADSCs)-Lining Prosthetic Graft Promotes Vascular Regeneration in Monkeys and Pigs - Xiao Zuo; Pengfei Han; Ding Yuan; Ying Xiao; Yushi Huang; Rui Li; Xia Jiang; Li Feng; Yijun Li; Yaya Zhang; Ping Zhu; Hongge Wang; et al. (Tissue Engineering and Regenerative Medicine, 2024)
Background: Current replacement procedures for stenosis or occluded arteries using prosthetic grafts have serious limitations in clinical applications, particularly, endothelialization of the luminal surface is a long-standing unresolved problem. Method: We produced a cell-based hybrid vascular graft using a bioink engulfing adipose-derived mesenchymal stromal cells (ADSCs) and a 3D bioprinting process lining the ADSCs on the luminal surface of GORE-Tex grafts. The hybrid graft was implanted as an interposition conduit to replace a 3-cm-long segment of the infrarenal abdominal aorta in Rhesus monkeys. Results: Complete endothelium layer and smooth muscle layer were fully developed within 21 days post-implantation, along with normalized collagen deposition and crosslinking in the regenerated vasculature in all monkeys. The regenerated blood vessels showed normal functionality for the longest observation of more than 1650 days. The same procedure was also conducted in miniature pigs for the interposition replacement of a 10-cm-long right iliac artery and showed the same long-term effective and safe outcome. Conclusion: This cell-based vascular graft is ready to undergo clinical trials for human patients.

Suitability of reduced dose glucocorticoids therapy regimen for antibody-associated vasculitis patients with TB: a retrospective study - Rui Wen; Jingni Xiao; Ning Ding; Yong Zhong; Qiong Yuan; Jiali Li; Qi Wang; Hebin Xie; Jiao Qin (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Unlocking the potential of biochar: an iron-phosphorus-based composite modified adsorbent for adsorption of Pb(II) and Cd(II) in aqueous environments and response surface optimization of adsorption conditions - Xu Li; Yuan Chi; Feng Ma; Xiaoxin Wang; Rui Du; Zhipeng Wang; Xiaoyan Dang; Chaoyue Zhao; Yanping Zhang; Shumin He; Youzhao Wang; Tong Zhu (Environmental Science and Pollution Research, 2024)

Ultrastable superhydrophobic melamine sponge via a one-step aqueous solution-based approach for oil/water separation - Yuan Meng; Chenyang Wang; Rui Xie; Linfeng Fei; Jingjing Liao (Journal of Water Process Engineering, 2024)

Using shell to enhance the phosphorus adsorption capability of aluminum-based drinking water treatment residue-dominant sintered ceramsite - Nannan Yuan; Rui Liu; Dongsiao Li; Lingli Yao; Changhui Wang (Journal of Water Process Engineering, 2024)

Biotemplated fabrication of N/O co-doped porous carbon confined spinel NiFe2O4 heterostructured mimetics for triple-mode sensing of antioxidants and ameliorating packaging properties - Yuan Gao; Juan Wang; Lin-Lan Zhao; Bo-Yi Yuan; Ya-Nan Kong; Jing-Jing Luo; Shu-Chang Zhao; Wei-Ming Yang; Rui-Lin Liu (Food Chemistry, 2024)

Effects of plastic film mulching on yield, water use efficiency, and nitrogen use efficiency of different crops in China: A meta-analysis - Tiantian Huang; Qianxiang Wu; Yangyang Yuan; Xintong Zhang; Ruiqi Sun; Rui Hao; Xiaohua Yang; Congfeng Li; Xiaoliang Qin; Fangqi Song; Charles O. Joseph; Wen Wang; et al. (Field Crops Research, 2024)

Enhanced efficiency nitrogen fertilizers (EENFs) can reduce nitrous oxide emissions and maintain high grain yields in a rain-fed spring maize cropping system - Yanling Du; Yuan Lu; Shengli Guo; Rui Wang; Xiaotong Song; Xiaotang Ju (Field Crops Research, 2024)

Identification of Circulating Inflammatory Proteins Associated with Calcific Aortic Valve Stenosis by Multiplex Analysis - Rui Lin; Yuexin Zhu; Weiyao Chen; Zhiao Wang; Yuan Wang; Jie Du (Cardiovascular Toxicology, 2024)

Triterpene hexahydroxydiphenoyl ester and phenol glucosides from the leaves of Castanopsis eyrie (Champ. ex Benth.) Hutch - Bing-Yuan Yang; Nao Pang; Rui-Jie He; Ya-Feng Wang; Yong-Lin Huang (Natural Product Research, 2024)

Preparation and application of biocontrol formulation of nematode-trapping fungus-Duddingtonia flagrans - Luyao Hao; Yuan Guo; Xiaomin Wang; Mingjuan Gao; Tonghai Liu; Yuan Ma; Yanni Zhang; Qiannan Li; Rui Wang; Xihuo You (Veterinary Parasitology, 2024)

Hypoxia preconditioning of human amniotic mesenchymal stem cells enhances proliferation and migration and promotes their homing via the HGF/C-MET signaling axis to augment the repair of acute liver failure - Qian Wang; Yuwen Li; Hui Yuan; Linya Peng; Zixing Dai; Ye Sun; Rui Liu; Wenting Li; Jun Li; Chuanlong Zhu (Tissue and Cell, 2024)

Carbazomycins I and J, two novel carbazole alkaloids isolated from Saccharopolyspora phattalungensis - Wen Wang; Er Juan Zhao; Ting Peng; Zhang Yuan Yan; Zhi Kai Guo; Rui Hua Jiao (Phytochemistry Letters, 2024)

Experimental analysis of a CO2 closed heat pump drying system combined with rotary dehumidification for drying banana slices drying - Zhili Sun; Qianqian Wang; Yingying Yuan; Dandan Wang; Qiang Zhou; Chunwei Xu; Kexin Meng; Haowei Peng; Lei Yan; Rui Jin; Lei Li; Haowei Liu; et al. (International Journal of Refrigeration, 2024)

Enhancing soil redox dynamics: Comparative effects of Fe-modified biochar (N–Fe and S–Fe) on Fe oxide transformation and Cd immobilization - Tianren Si; Rui Yuan; Yanjie Qi; Yuhao Zhang; Yan Wang; Rongjun Bian; Xiaoyu Liu; Xuhui Zhang; Stephen Joseph; Lianqing Li; Genxing Pan (Environmental Pollution, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

Seismic evidence for break-off of the Molucca Sea slab - Tianmeng Yuan; Zewei Wang; Dapeng Zhao; Rui Gao; Xiaofei Chen (Tectonophysics, 2024)

Critical fractions in reclaimed water responsible for membrane fouling: Isolation, fouling characteristics, quantitative and qualitative variations in practical application - Yuan Bai; Rui-Ning Wang; Yin-Hu Wu; Song Xue; Zhuo Chen; Hong-Ying Hu (Science of The Total Environment, 2024)

Succinylated acetyl-CoA carboxylase contributes to aflatoxin biosynthesis, morphology development, and pathogenicity in Aspergillus flavus - Rui Xie; Bei Zhang; Elisabeth Tumukunde; Zhenhong Zhuang; Jun Yuan; Shihua Wang (International Journal of Food Microbiology, 2024)

Inactivation activity and mechanism of pulsed light against Alicyclobacillus acidoterrestris vegetative cells and spores in concentrated apple juice - Rui Cai; Yali Ma; Zhouli Wang; Yahong Yuan; Hong Guo; Qinglin Sheng; Tianli Yue (International Journal of Food Microbiology, 2024)

Catalytic reforming of polypropylene to produce hydrogen: Influence of support characteristics and active metal type in catalyst - Shuxiao Wang; Yibo Sun; Rui Shan; Jing Gu; Haoran Yuan; Yong Chen (Fuel, 2024)

Sources and transformation of nitrate in an agricultural riverine reservoir watershed of the Sichuan Basin - Fen Xu; Kexin He; Hong Wang; Xiaoxia He; Yaqian Zhou; Jie Qin; Lishan Wu; Rui Yang; Jianfei Yuan (Applied Geochemistry, 2024)

Co-application of concentrated biogas slurry and pyroligneous liquor mitigates ammonia emission and sustainably releases ammonium from paddy soil - Zichuan Li; Rui Zhang; Jianfeng Jiang; Yanjun Chai; Haijun Yang; Yutong Zong; Wenbin Tong; Mengting Yuan; Ronghui Li; Lanting Wang; Shengdao Shan; Ming Hung Wong (Science of The Total Environment, 2024)

Epsilon-poly-l-lysine alleviates brown blotch disease of postharvest Agaricus bisporus mushrooms by directly inhibiting Pseudomonas tolaasii and inducing mushroom disease resistance - Rui Song; Xiuhong Wang; Lu Jiao; Hanyue Jiang; Shuai Yuan; Lei Zhang; Zixuan Shi; Zhenchuan Fan; Demei Meng (Pesticide Biochemistry and Physiology, 2024)

Chuaria and Tawuia fossils from ∼1.0 Ga rocks in North China: Implications for a polyphyletic origin of Chuaria and a potential biological link between these two widespread Proterozoic taxa - Changtai Niu; Guangjin Li; Qing Tang; Xiaopeng Wang; Rui Huang; Hanzhi Qu; Mingyang Qiu; Bin Wan; Zhe Chen; Chuanming Zhou; Ke Pang; Xunlai Yuan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

The effect of climate oscillations on skipjack tuna (Katsuwonus pelamis) in the Indian Ocean - Shigang Liu; Liyan Zhang; Rui Wang; Puqing Song; Xing Miao; Hai Li; Yuan Li; Longshan Lin (Journal of Marine Systems, 2024)

Production of carbon nanotubes via catalytic pyrolysis of polyethylene over Ni/ZSM-5 prepared by ethylene glycol assisted impregnation - Qing-Lin Li; Rui Shan; Shu-Xiao Wang; Tao-li Huhe; Hao-Ran Yuan; Yong Chen (Fuel, 2024)

Complexities of regulating climate by promoting marine primary production with ocean iron fertilization - Hai-Bo Jiang; David A. Hutchins; Hao-Ran Zhang; Yuan-Yuan Feng; Rui-Feng Zhang; Wei-Wei Sun; Wentao Ma; Yan Bai; Mark Wells; Ding He; Nianzhi Jiao; Yuntao Wang; et al. (Earth-Science Reviews, 2024)

Functionalized Sr2MgSi2O7:(Eu,Dy)@CdS heterojunction photocatalyst for round-the-clock hydrogen production - Jing Wang; Runhui Pan; Zijie Yuan; Qi Hao; Xingyu Niu; Rui Wang; Jilei Ye; Hui Ying Yang; Yuping Wu (Chemical Engineering Journal, 2024)

α-Glucan derivatives as selective blockers of aldolase A: Computer-aided structure optimization and the effects on HCC - Qian-Han Xiao; Ze-Zhi Li; Li Ren; Shu-Yao Wang; Xiao-Qiang Li; Hong-Xin Bai; Rui-Zhi Qiao; Na Tang; Wen-Juan Liu; Jing-Mei Wang; Guang-Yuan Ma; Dian-Chao Dong; et al. (Carbohydrate Polymers, 2024)

HNF4A as a potential target of PFOA and PFOS leading to hepatic steatosis: Integrated molecular docking, molecular dynamic and transcriptomic analyses - Rui Li; Zijing Zhang; Yuxin Xuan; Yulu Wang; Yuyan Zhong; Lingyin Zhang; Jinrui Zhang; Qian Chen; Shuling Yu; Jintao Yuan (Chemico-Biological Interactions, 2024)

The effect of bta-miR-1296 on the proliferation and extracellular matrix synthesis of bovine mammary fibroblasts - Yuejie Yang; Tao Yuan; Rui Wu; Zijian Geng; Shuai Lian; Jianfa Wang (In Vitro Cellular & Developmental Biology - Animal, 2024)

New 4',5'-methylenedioxyflavone derivatives from the whole plant of sarcandra glabra - Ya-Qiu Qin; Wei Liu; Rui Yin; Ping-Ting Xiao; Zi-Yuan Wang; Tian-Qing Huang; E-Hu Liu (Natural Product Research, 2024)

Numerical Investigation of the Impacts of Large Particles on the Turbulent Flow and Surface Wear in Series-Connected Bends - Yuan-Hang Zhang; Xiao-Jie Wang; Xu-Zhen Zhang; Maoukouf Saad; Rui-Jie Zhao (Journal of Marine Science and Engineering, 2024)
The deep sea harbors abundant mineral, oil, and gas resources, making it highly valuable for commercial development, including the extraction of minerals. Due to the relatively large particle size of these minerals, how they interact with fluids is significantly different from that of small particles. However, there has been limited simulation research on the impacts of large particles (the diameter of particles is at the level of centimeters) on the flow and wear characteristics in bends, because the simulation of the particles at such a size is difficult. Additionally, in the field of deep-sea mining, multiple bends are simultaneously connected in series, and the wear in such bends has garnered increasing attention. Based on an improved CFD-DEM model, this article solved the issue that traditional unresolved CFD-DEM methods cannot accurately simulate large particles in a hydraulic conveying pipe and bend. After validating the accuracy of this model against classical experiments, the paper comprehensively analyzes the modulation effect of large particles on turbulence, and the effects of different particle diameters, particle transport concentrations, and transport velocities on the wear of bends connected serially. Finally, the bends connected serially in various configurations are simulated to study the wear on the bent interior surfaces. Results indicate a pronounced modulation effect of large particles on turbulence at higher transport concentrations; the wear rate in the combined bends does not exhibit a linear correlation with the collision frequency of particles on the wall surface. Furthermore, different configurations of serially connected bends exhibit significant differences in the wear morphology of the second bend.

Distribution Characteristics and Factors Controlling Different Phosphorus Fractions in the Soils and Sediments of an Inland Lagoon - Kun Yuan; Rui Wang; Bo He; Guowei Fu; Yanwei Song; Lixin Pei; Shichao Fan; Fangyi Gao (Journal of Marine Science and Engineering, 2024)
Lagoons, significant coastal wetlands, stand out for their vital role in the cycles and transformations of phosphorus. However, the relationship between the spatial distributions of various phosphorus forms in the soil and sediments of lagoon areas remains unclear. This study investigated the phosphorus fractions and distribution patterns in the soil and sediments from Shimei Inland Sea, Hainan Province, China, and identified the factors controlling phosphorus distribution and its relationship with lagoon eutrophication. The results revealed significant enrichment of inorganic phosphorus (IP) in the Shimei Inland Sea (64.1–679.0 mg/kg) and offshore areas (56–627.2 mg/kg), while organic phosphorus (OP) was relatively concentrated in land (60–744.3 mg/kg), suggesting that the productivity of the terrestrial ecosystem controlled the OP content and IP formed from the mineralization of OP was more likely to leach into the water and combine with minerals. Total phosphorus (TP) content was negatively affected by pH, and organic matter, cation exchange capacity and iron/aluminum oxides showed significant positive correlations with TP content. These findings highlighted the coupled impact of soil and sediment physicochemical properties on phosphorus enrichment and transformation, providing theoretical support for the ecological restoration of ecosystems in tropical coastal wetlands.

Aridity drives the variability of desert soil microbiomes across north-western China - Lei Dong; Mei-Xiang Li; Shuai Li; Ling-Xiang Yue; Mukhtiar Ali; Jia-Rui Han; Wen-Hui Lian; Chao-Jian Hu; Zhi-Liang Lin; Guo-Yuan Shi; Pan-Deng Wang; Shao-Ming Gao; et al. (Science of The Total Environment, 2024)

Climatic limitations on grassland photosynthesis over the Tibetan Plateau shifted from temperature to water - Jiangliu Xie; Gaofei Yin; Dujuan Ma; Rui Chen; Wei Zhao; Qiaoyun Xie; Cong Wang; Shangrong Lin; Wenping Yuan (Science of The Total Environment, 2024)

Effect of different water and organic matter content on the resistivity of loess - Rui Lv; Qiang Sun; Pengfei Li; Jishi Geng; Yuan Xin; Shaofei Wang (Science of The Total Environment, 2024)

Stytontriterpenes A−C, three unusual oleanane-derived triterpenoids from the resin of Styrax tonkinensis as potential immunosuppressive agents in atherosclerosis - Rui-Yan Jiang; Ling-Wen Yao; Yin-Hong Lv; Zhong-Tian Guo; Fei-Fei Wang; Hong-Hua Cui; Yuan-Yuan Cheng; Feng Wang (Phytochemistry, 2024)

An experimental and modeling study on the oxidation of ammonia-methanol mixtures in a jet stirred reactor - Yuan Zhuang; Ruikang Wu; Xinyan Wang; Rui Zhai.; Changyong Gao (Fuel, 2024)

Investigation of the synergistic effect of O2/H2O pretreatment and Na addition on the NO-semichar reaction - Lei Zhang; Yongxin Chen; Rui Sun; Zhuozhi Wang; Wenkun Zhu; Xingyi Wang; Mengfan Yuan; Dengke Chen (Fuel, 2024)

Unlocking the potential of N-acetylcysteine: Improving hepatopancreas inflammation, antioxidant capacity and health in common carp (Cyprinus carpio) via the MAPK/NF-κB/Nrf2 signalling pathway - Rui Zhu; Guo-Jun Shang; Bao-Yuan Zhang; Hao-Tong Wang; Liang Li; Xiao-fang Wei; Deng-Lai Li; Zhi-Yong Yang; Zi-Hui Qu; Ya-Nan Quan; Si-Ying Liu; Yin-Tao Wang; et al. (Fish & Shellfish Immunology, 2024)

High titer (>100 g/L) ethanol production from pretreated corn stover hydrolysate by modified yeast strains - Rui Zhao; Hongshen Li; Qi Li; Zefang Jia; Shizhong Li; Ling Zhao; Shan Li; Yuwei Wang; Wenxin Fan; Ruoqi Ren; Zitong Yuan; Mengchan Yang; et al. (Bioresource Technology, 2024)

The Protective Effect of Chronic Intermittent Hypobaric Hypoxia on Preventing the Destruction of CD34+ Haematopoietic Stem Cells in Aplastic Anaemia by Modulating the Th1/Th2 Balance - Hui Guo; Yilin Zhao; Rui Mu; Guangdao Zhang; Shuxian Chen; Xinwei Cao; Kangcan Liu; Yiran Liu; Baiyun Dai; Yuan Zhou; Chuan Wang; Jing Yang (Stem Cell Reviews and Reports, 2024)

Dietary supplementation with polysaccharides from Rhizoma dioscoreae resulting in the enhanced immunity and the structural modulation of the intestinal microbiota in Luciobarbus capito - Yuan Sun; Xiaowei Hu; Xianwei Meng; Rui Liu; Zhigang Zhao; Shihui Wang; Rui Zhang; Kun Guo; Liang Luo (Aquaculture, 2023)

Moderate selenium alleviates the pulmonary function impairment induced by cadmium and lead in adults: A population-based study - Heze Fan; Ying Xiong; Yuzhi Huang; Lijun Wang; Chenbo Xu; Wenyuan Li; Xueying Feng; Yuxuan Yang; Rui Hua; Zihao Wang; Zuyi Yuan; Juan Zhou (Science of The Total Environment, 2023)

Protective and immunomodulatory effects of mesenchymal stem cells on multiorgan injury in male rats with heatstroke - Yuyan Liu; Yun Li; Zihui Deng; Yan Zhao; Rui Yuan; Mengmeng Yang; Lu Wang; Yuan Fang; Dengfeng Ding; Feihu Zhou; Hongjun Kang (Journal of Thermal Biology, 2023)

Significant methane ebullition from large shallow eutrophic lakes of the semi-arid region of northern China - Linxiang Zhang; Xiangwei Li; Ruihong Yu; Yue Geng; Liangqi Sun; Heyang Sun; Yuan Li; Zhonghua Zhang; Xiangyu Zhang; Xue Lei; Rui Wang; Changwei Lu; et al. (Journal of Environmental Management, 2023)

Unraveling symbiotic microbial communities, metabolomics and volatilomics profiles of kombucha from diverse regions in China - Shiqi Li; Saiqun Wang; Leran Wang; Xiaoshuang Liu; Xingnan Wang; Rui Cai; Yahong Yuan; Tianli Yue; Zhouli Wang (Food Research International, 2023)

Effects of dry-salting and brine-pickling on physicochemical properties and flavor of spaghetti squash shreds - Yi Luo; Rui Wang; Hui Han; Shuo Wang; Jianxiang Ma; Chunlong Yuan; Yamei Ren (Food Bioscience, 2023)

Seasonal variation regulate the endogenous phosphorus release in sediments of Shijiuhu Lake via water-level fluctuation - Yiwei Cai; Haixiang Wang; Tianxin Zhang; Yanwen Zhou; Azhong Dong; Rui Huang; Qingfei Zeng; Hezhong Yuan (Environmental Research, 2023)

Anti-freezing hydrogel thermocells with confined microcrystallization for enhanced low-grade heat harvest - Ping-Fan Li; Ting-Yuan Hu; Tao Luo; Zhuang Liu; Xiao-Jie Ju; Rui Xie; Da-Wei Pan; Wei Wang; Liang-Yin Chu (Chemical Engineering Journal, 2023)

Classification of Glomerular Pathology Images in Children Using Convolutional Neural Networks with Improved SE-ResNet Module - Xiang-Yong Kong; Xin-Shen Zhao; Xiao-Han Sun; Ping Wang; Ying Wu; Rui-Yang Peng; Qi-Yuan Zhang; Yu-Ze Wang; Rong Li; Yi-Heng Yang; Ying-Rui Lv (Interdisciplinary Sciences: Computational Life Sciences, 2023)

Two truxinate derivatives and a phenyldilactone from the leaves of Castanopsis eyrei - Ya-feng Wang; Nao Pang; Zhen-hua Liang; Yong-lin Huang; Rui-jie He; Bing-yuan Yang; Zhang-bin Liu (Natural Product Research, 2023)

Carboniferous-Permian high-resolution conodont biostratigraphy and paleoclimate change in North China - Yuan Wang; Jianghai Yang; Charles M. Henderson; Dongxun Yuan; Rui Ma; Jia Liu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Pyrolysis of different types of waste cooking oil in the presence/absence HZSM-5 catalyst: Influence of feedstock characteristics on aromatic formation - Yuanyuan Wang; Yuan Zeng; Liangliang Fan; Qiuhao Wu; Letian Zhang; Jianyun Xiong; Jiahui Zhang; Rui Liao; Kirk Cobb; Yuhuan Liu; Roger Ruan; Yunpu Wang (Fuel, 2023)

In-season prediction of maize stem lodging risk using an active canopy sensor - Rui Dong; Yuxin Miao; Pete Berry; Xinbing Wang; Fei Yuan; Krzysztof Kusnierek; Chris Baker; Mark Sterling (European Journal of Agronomy, 2023)

Ferrostatin-1-loaded thermosensitive nanodelivery system for noise-induced hearing loss treatment - Peng-Wei Ma; Pei-Heng Lu; Hao Yuan; Jia-Wei Chen; Wei Gao; Yu-Qiang Lun; Jia-Ning Guo; Xue-Rui Ding; Rui Liang; Si-Yu Li; Zi Wang; Wei-Long Wang; et al. (Chemical Engineering Journal, 2023)

Demethylation-Driven ligase chain reaction for simultaneously sensitive detection of m6A demethylase FTO and m1A demethylase ALKBH3 in breast cancer at Single-Molecule level - Ming-hao Liu; Qian Zhang; Wan-tong Yu; Jian-Ge Qiu; Hui-min Yuan; Chuan-rui Wang; Bing-Hua Jiang; Yan Zhang; Chun-yang Zhang (Chemical Engineering Journal, 2023)

Transient, printable and recyclable gelatin hydrogels with enhanced mechanical sensing and electromagnetic shielding performance by incorporation of reduced graphene oxide - Rui Yin; Chen Zhang; Youyou Chen; Yu Wang; Qiang Feng; Yaming Liu; Minghan Yu; Yunhuan Yuan; Cheng-Yan Xu; Feihua Liu; Weiwei Zhao (Chemical Engineering Journal, 2023)

Rape straw biochar enhanced Cd immobilization in flooded paddy soil by promoting Fe and sulfur transformation - Rui Yuan; Tianren Si; Qingquan Lu; Rongjun Bian; Yan Wang; Xiaoyu Liu; Xuhui Zhang; Jufeng Zheng; Kun Cheng; Stephen Joseph; Lianqing Li; Genxing Pan (Chemosphere, 2023)

IFN-γ promotes PANoptosis in Pasteurella multocida toxin-induced pneumonia in mice - Hang Xiao; Qin Zhao; Jianlin Yuan; Wei Liang; Rui Wu; Yiping Wen; Senyan Du; Yiping Wang; Shan Zhao; Yifei Lang; Qigui Yan; Xiaobo Huang; et al. (Veterinary Microbiology, 2023)

Effects of multi-frequency ultrasound on inactivating Chironomus kiiensis eggs: Evidence from a case study in drinking water treatment plant - Hai-guang Yuan; Rui-jian Zhang; Ye-qin Xu; Zhi Dang; Yong Hu; Qian-Bin Wang; Hao-tao Dong; Jia-xin Liu; Shu-juan Pu; Zhi-li Du; Ying-shi Liu; Zong-jia Zhang (Journal of Water Process Engineering, 2023)

Direct immobilization of Se(IV) from acidic Se(IV)-rich wastewater via ferric selenite Co-precipitation - Zidan Yuan; Rui Su; Xu Ma; Le Yu; Yuanming Pan; Ning Chen; Roman Chernikov; Leo Ka Long Cheung; Reza Deevsalar; Ayetullah Tunc; Liang Wang; Xiangfeng Zeng; et al. (Journal of Hazardous Materials, 2023)

Role of suspended solids on the co-precipitation of pathogenic indicators and antibiotic resistance genes with struvite from digested swine wastewater - Wenjing Bai; Rui Tang; Guangxue Wu; Wei Wang; Shoujun Yuan; Liwen Xiao; Xinmin Zhan; Zhen-Hu Hu (Journal of Hazardous Materials, 2023)

Association between urinary neonicotinoid insecticide levels and dyslipidemia risk: A cross-sectional study in Chinese community-dwelling elderly - Jian Sun; Pei He; Rui Wang; Zhong-Yuan Zhang; Yu-Qing Dai; Xiao-Yu Li; Si-Yu Duan; Cai-Ping Liu; Hao Hu; Guang-Jun Wang; Yan-Ping Zhang; Fei Xu; et al. (Journal of Hazardous Materials, 2023)

Citrus medica var. Sarcodactylus (Siebold ex Hoola van Nooten) Swingle: an insight into its botany, traditional uses, phytochemistry, and pharmacological properties - Qin-Ge Ma; Jie Chen; Li-Hua Chen; Guang Wu; Mei-Ning Zhu; Neng-Xin He; Qin-Yuan Wang; Zhi-Pei Sang; Cai-Qing Zhu; Yong-Zhong Wu; Rong-Rui Wei (Phytochemistry Reviews, 2023)

FOXO4-D-Retro-Inverso targets extracellular matrix production in fibroblasts and ameliorates bleomycin-induced pulmonary fibrosis in mice - Ying Liu; Qinhui Hou; Rui Wang; Yuan Liu; Zhenshun Cheng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Urine 2-hydroxyphenanthrene is associated with current asthma: evidence from NHANES 2007–2012 - Lingyi Lu; Tingfeng Mao; Rui Xu; Lanxia Liu; Jiefeng Qian; Kai Yang; Anjie Yuan; Xinyue Wang; Rong Ni (International Archives of Occupational and Environmental Health, 2023)

Ultra-sensitive photoelectrochemical biosensor for determination of African swine fever virus based on surface plasmon resonance - Ruishuang Yuan; Jie Wei; Rui Geng; Bin Li; Wei Xiong; Xueen Fang; Peng Lü; Kun Wang (Analytica Chimica Acta, 2023)

Comparative transcriptome profiling reveals RNA splicing alterations and biological function in patients exposed to occupational noise - Jia-Wei Chen; Jun-Jie Shao; Shao-Fei Zhao; Pei-Heng Lu; Si-Yu Li; Hao Yuan; Peng-Wei Ma; Yu-Qiang Lun; Wei-Long Wang; Rui Liang; Wei Gao; Qian Yang; et al. (Environmental Science and Pollution Research, 2023)

Carbon source shaped microbial ecology, metabolism and performance in denitrification systems - Yuan Pan; Rui-Zhe Sun; Yan Wang; Guan-Lin Chen; Ying-Ying Fu; Han-Qing Yu (Water Research, 2023)

Association between PM2.5 exposure and the outcomes of ART treatment: A prospective birth cohort study - Yifan Wang; Yun Qiu; Bo Huang; Jiangbo Du; Liya Liu; Tao Jiang; Yangqian Jiang; Hong Lv; Qun Lu; Rui Qin; Shiyao Tao; Lei Huang; et al. (Science of The Total Environment, 2023)

Achieving reasonable waste heat utilization in all truck operating conditions via a dual-pressure organic rankine cycle and its operating strategy - Xuanang Zhang; Xuan Wang; Jinwen Cai; Rui Wang; Xingyan Bian; Ping Yuan; Hua Tian; Gequn Shu (Journal of Cleaner Production, 2023)

Comprehensive understanding of tetracycline hydrochloride adsorption mechanism onto biochar-based gel pellets based on the combination of characterization-based and approximate site energy distribution methods - Bai-Qin Zhou; Qian-Qian Sang; Yu-Jun Wang; Hui Huang; Fang-Jun Wang; Rui-Chun Yang; Yuan-Tian Zhao; Zi-Jie Xiao; Chun-Yue Zhang; Hui-Ping Li (Journal of Cleaner Production, 2023)

A multi-source data-driven model of lake water level based on variational modal decomposition and external factors with optimized bi-directional long short-term memory neural network - Rui Tan; Yuan Hu; Zhaocai Wang (Environmental Modelling & Software, 2023)

Tailoring zincophilicity via amorphous Se-rich selenides coating for stable Zn anode - Guoquan Jiang; Rui Xue; Linxin He; Junchao Zhu; Nan Qiu; Yuan Wang (Chemical Engineering Journal, 2023)

COS and H2S simultaneous removal from blast furnace gas over a tailored Cu/Zr co-doped K@TiO2 bifunctional catalyst under low temperature - Xiang Li; Xueqian Wang; Li Yuan; Langlang Wang; Yixing Ma; You Wu; Yibing Xie; Rui Cao; Yiran Xiong; Ping Ning (Chemical Engineering Journal, 2023)

Dual-layer drug release system based on ureteral stents inhibits the formation of ureteral stricture - Zhiduan Cai; Wenjun Luo; Haoquan Zhuang; Congling Ren; Xiaolin Pan; Yuyu Xu; Haoran Wang; Xiezhao Li; Yaoji Yuan; Rui Zhu; Xiangyu Zhan; Lin Jin; et al. (Chemical Engineering Journal, 2023)

Structural characteristics of the moss (bryophyte) layer and its underlying soil structure and water retention characteristics - Xia Hu; Zhou Gao; Xiao-Yan Li; Rui-Zhe Wang; Yuan-Ming Wang (Plant and Soil, 2023)

Phylogenetic analysis and molecular characterization of the co-infection of the new variant of the porcine epidemic diarrhea virus and the novel porcine kobuvirus isolated from piglets with diarrhea - Ran Wei; Rui Shang; Kaihui Cheng; Song Wang; Xiaoyuan Yuan; Jiaqiang Wu; Zhijun Yu (Brazilian Journal of Microbiology, 2023)

Predictive value of serum proteomic biomarkers for noise-induced hearing loss - Yuqiang Lun; Jiawei Chen; Peiheng Lu; Hao Yuan; Pengwei Ma; Weilong Wang; Rui Liang; Siyu Li; Wei Gao; Xuerui Ding; Zi Wang; Jianing Guo; et al. (Environmental Science and Pollution Research, 2023)

Association between prenatal exposure to trace elements mixture and visual acuity in infants: A prospective birth cohort study - Zijin Wang; Yuanyan Dou; Wenhui Guo; Yuan Lin; Yangqian Jiang; Tao Jiang; Rui Qin; Hong Lv; Qun Lu; Guangfu Jin; Hongxia Ma; Zhibin Hu; et al. (Chemosphere, 2023)

Can China achieve its 2030 and 2060 CO2 commitments? Scenario analysis based on the integration of LEAP model with LMDI decomposition - Yimin Huang; Yuan Wang; Jiaoting Peng; Fan Li; Lin Zhu; Huihui Zhao; Rui Shi (Science of The Total Environment, 2023)

Localized host-rock porosity near sealed fractures at 7 km depth: Geochemical evidence of deep-seated porosity controls - Denglin Han; Jizhen Zhang; Chenchen Wang; Wei Lin; Rui Yuan; Xin Nie; Juan Zhang (Journal of Structural Geology, 2023)

Co-precipitation of heavy metals with struvite from digested swine wastewater: Role of suspended solids - Wenjing Bai; Rui Tang; Guangxue Wu; Wei Wang; Shoujun Yuan; Liwen Xiao; Xinmin Zhan; Zhen-Hu Hu (Journal of Hazardous Materials, 2023)

Enhanced recovery of germanium(IV) from zinc residue leachate by tartaric acid functionalized chitosan: Experiments and DFT calculation - Hongrui Xiang; Zhihui Yang; Xiaobo Min; Yanjie Liang; Cong Peng; Xiaoyun Liu; Rui Yuan; Qingwei Wang; Feiping Zhao (Hydrometallurgy, 2023)

Will the southward center of gravity migration of population, floor area, and building energy consumption facilitate building carbon emission reduction in China? - Rui Li; Kairui You; Weiguang Cai; Jiebing Wang; Yuan Liu; Yanhui Yu (Building and Environment, 2023)

Assessment of Chloride Salt Release Flux from Fluidized Cohesive Sediments in Quiescent Water - Jing Yuan; Binghui Zheng; Rui Wang; Minxi Zhang; Guoliang Yu (Water, Air, & Soil Pollution, 2023)

High prevalence of vitamin D deficiency in Asia: A systematic review and meta-analysis - Zhiwei Jiang; Rui Pu; Na Li; Chaozhen Chen; Jialu Li; Wei Dai; Yuchen Wang; Jinxing Hu; Danji Zhu; Qiong Yu; Yuan Shi; Guoli Yang (Critical Reviews in Food Science and Nutrition, 2023)

Two new isoflavones from the barks of Dalbergia hancei Benth - Xiao-Mei Li; Nao Pang; Ya-Feng Wang; Rui-Jie He; Li Ge; Bing-Yuan Yang; Ke-Di Yang; Yong-Lin Huang (Natural Product Research, 2023)

Inactivation of Alicyclobacillus contaminans spores by dielectric barrier discharge plasma and its biological mechanism - Zewei Wang; Qiannan Zhao; Yuan Gan; Qiuxia Fan; Zhongqiu Hu; Zhouli Wang; Rui Cai; Tianli Yue; Yahong Yuan (Innovative Food Science & Emerging Technologies, 2023)

Carbon nanotubes production from catalytic pyrolysis of polyethylene over nickel-based catalysts: The influence of support materials - Qing-Lin Li; Rui Shan; Shu-Xiao Wang; Hao-Ran Yuan; Yong Chen (Fuel, 2023)

Intraspecific variations of adaptive strategies of native and invasive plant species along an elevational gradient - Hasigerili; Kun Guo; Miao-Miao Zheng; Rui-Ling Liu; Yan-Yan Wang; Yuan Gao; Li Shu; Xiao-Ran Wang; Jian Zhang; Wen-Yong Guo (Flora, 2023)

In situ polymerization of polypyrrole in oil body for efficient solar-driven freshwater collection - Hongxiang Liu; Tianshu Zou; Xingyu Cui; Miao Ding; Biao Zhang; Xiaodong Yang; Yu Han; Shuwei Nie; Yuan Zhang; Enze Wang; Lili Wang; Yan Cheng; et al. (Chemical Engineering Journal, 2023)

Toxicity and synergistic effect of secondary metabolites isolated from the endophytic fungus LS-Y-1 of Rhododendron przewalskii against Tribolium castaneum - Junyu Liang; Haoshu Wu; Xudong Wang; Rui Feng; Peiyu Lu; Jie Xu; Weibao Kong; Yuan Li (South African Journal of Botany, 2023)

Differential effects of petroleum-based and bio-based microplastics on anaerobic digestion: A review - Zezhou Shang; Rui Wang; Xiyi Zhang; Yongle Tu; Chenjing Sheng; Huan Yuan; Lei Wen; Yulu Li; Jing Zhang; Xiaojiao Wang; Gaihe Yang; Yongzhong Feng; et al. (Science of The Total Environment, 2023)

Degradation of aflatoxins in apple juice by pulsed light and the analysis of their degradation products - Lige Qi; Yali Ma; Rui Cai; Yu Li; Ruinan Wang; Tianli Yue; Yahong Yuan; Zhenpeng Gao; Zhouli Wang (Food Control, 2023)

Production of antifungal iturins from vegetable straw: A combined chemical-bacterial process - Yuan Yuan; Depeng Chu; Jiajun Fan; Zhenzhen Cui; Rui Wang; Han Zhang; Xiangwei You; Yiqiang Li; Xiaoqiang Wang (Bioresource Technology, 2023)

FHB resistance conferred by Fhb1 is under inhibitory regulation of two genetic loci in wheat (Triticum aestivum L.) - Guoqiang Li; Yang Yuan; Jiyang Zhou; Rui Cheng; Ruitong Chen; Xianmin Luo; Jinxing Shi; Heyu Wang; Boyang Xu; Youyu Duan; Jinkun Zhong; Xin Wang; et al. (Theoretical and Applied Genetics, 2023)

Measuring static and dynamic industrial eco-efficiency in China based on the MinDS–Malmquist–Luenberger model - Pei-Pei Jiang; Yuan Wang; Jin Luo; Lin Zhu; Rui Shi; Song Hu; Xiaodong Zhu (Environment, Development and Sustainability, 2023)

Sources and historical records of metal(loid)s in river sediments from an agricultural tributary of Tuojiang river: Evidence from geochemical analyses and Pb isotope - Fen Xu; Rui Yang; Hong Wang; Xiaoxia He; Weiwei Li; Yao Wei; Linlin Bao; Jianfei Yuan; Hongjin Tong (Chemosphere, 2023)

Driving forces and variation in water footprint before and after the COVID-19 lockdown in Fujian Province of China - Fan Yu; Yuan Wang; Xin Liu; Jinru Yu; Dandan Zhao; Haijun Deng; Bin Guo; Rui Shi; Bowei Wu; Huayang Chen (Journal of Cleaner Production, 2023)

Emerging trends in pectin functional processing and its fortification for synbiotics: A review - Rui Sun; Yefan Niu; Menghui Li; Yuanye Liu; Kai Wang; Zhenpeng Gao; Zhouli Wang; Tianli Yue; Yahong Yuan (Trends in Food Science & Technology, 2023)

Phosphorus – The main limiting factor in riverine ecosystems in China - Yan Chen; Jie Chen; Rui Xia; Wenpan Li; Yuan Zhang; Kai Zhang; Shanlin Tong; Ruining Jia; Qiang Hu; Lu Wang; Xiaojiao Zhang (Science of The Total Environment, 2023)

Sulfoxaflor adversely influences the biological characteristics of Coccinella septempunctata by suppressing vitellogenin expression and predation activity - Li Wang; Yanhui Zhai; Junshu Zhu; Qinqin Wang; Xuejiao Ji; Wenjie Wang; Huizhu Yuan; Changhui Rui; Li Cui (Journal of Hazardous Materials, 2023)

Magnetic field assisted enhancement of electronic metal-support interactions in FexCuy@TiO2-δ catalysts for arsine catalytic oxidation - Yibing Xie; Xueqian Wang; Ping Ning; Langlang Wang; Yixing Ma; Yuan Li; Rui Cao; Hui Zhang; Xiang Li; Bowen Xu (Journal of Cleaner Production, 2023)

Litchi-like glucose oxidase-integrated magnetic metal-organic framework as glucose-triggered cascade catalyst for antibacterial treatment - Hang Jia; Shiqi Fan; Rui Cai; Zhouli Wang; Yahong Yuan; Tianli Yue (Journal of Environmental Chemical Engineering, 2023)

Investigation of the synergetic regulation of O2/Ar preheating treatment and sodium salt addition on semichar combustion characteristics - Lei Zhang; Wenkun Zhu; Zhuozhi Wang; Mengfan Yuan; Xingyi Wang; Xu Yang; Rui Sun (Fuel, 2023)

A critical review on graphene oxide membrane for industrial wastewater treatment - Ye-Chen An; Xiao-Xu Gao; Wen-Li Jiang; Jing-Long Han; Yuan Ye; Tian-Ming Chen; Rui-Yun Ren; Jia-Hui Zhang; Bin Liang; Zhi-Ling Li; Ai-Jie Wang; Nan-Qi Ren (Environmental Research, 2023)

Targeting Senescent Tendon Stem/Progenitor Cells to Prevent or Treat Age-Related Tendon Disorders - Hao Wang; Guang-Chun Dai; Ying-Juan Li; Min-Hao Chen; Pan-Pan Lu; Yuan-Wei Zhang; Ming -Zhang; Mu-Min Cao; Yun-Feng Rui (Stem Cell Reviews and Reports, 2023)

Modification of fluorescence staining method for small-sized microplastic quantification: Focus on the interference exclusion and exposure time optimization - Wentao Hu; Rui Tang; Shoujun Yuan; Miao Gong; Penghui Shi; Wei Wang; Zhen-Hu Hu (Environmental Science and Pollution Research, 2023)

Reduced plastic film mulching under zero tillage boosts water use efficiency and soil health in semiarid rainfed maize field - Ai-Tian Ren; Ji-Yuan Li; Ling Zhao; Rui Zhou; Jian-Sheng Ye; Yi-Bo Wang; Xu-Cheng Zhang; Kiprotich Wesly; Ming-Sheng Ma; You-Cai Xiong (Resources, Conservation and Recycling, 2023)

Detoxification of patulin in apple juice by enzymes and evaluation of its degradation products - Xiaoshuang Liu; Leran Wang; Saiqun Wang; Rui Cai; Tianli Yue; Yahong Yuan; Zhenpeng Gao; Zhouli Wang (Food Control, 2023)

Molecular characterization of a teleost-specific toll-like receptor 22 (tlr22) gene from yellow catfish (Pelteobagrus fulvidraco) and its transcriptional change in response to poly I:C and Aeromonas hydrophila stimuli - Xiu-Ying Wei; Jun Wang; Sheng-Tao Guo; Yun-Yun Lv; Yan-Ping Li; Chuan-Jie Qin; Yuan-Chao Zou; Qing-Chao Shi; Peng Hu; Xiao-Qin Xiong; Yang He; Rui Li; et al. (Fish & Shellfish Immunology, 2023)

High density mapping of wheat stripe rust resistance gene QYrXN3517-1BL using QTL mapping, BSE-Seq and candidate gene analysis - Shuo Huang; Yibo Zhang; Hui Ren; Xin Zhang; Rui Yu; Shengjie Liu; Qingdong Zeng; Qilin Wang; Fengping Yuan; Ravi P. Singh; Sridhar Bhavani; Jianhui Wu; et al. (Theoretical and Applied Genetics, 2023)

Vitellogenin accumulation leads to reproductive senescence by impairing lysosomal function - Jie Tang; Yi-Cheng Ma; Yuan-Li Chen; Rui-Qiu Yang; Heng-Chen Liu; Xin Wang; Baosen Ni; Cheng-Gang Zou; Ke-Qin Zhang (Science China Life Sciences, 2023)

Genome-wide identification and expression analysis of the cotton patatin-related phospholipase A genes and response to stress tolerance - Yunxiao Wei; Zhili Chong; Chao Lu; Kaili Li; Chengzhen Liang; Zhigang Meng; Yuan Wang; Sandui Guo; Liangrong He; Rui Zhang (Planta, 2023)

Effects of Vertical Water Column Temperature on Distribution of Juvenile Tuna Species in the South China Sea - Shigang Liu; Yuan Li; Rui Wang; Xing Miao; Ran Zhang; Siyuan Chen; Puqing Song; Longshan Lin (Fishes, 2023)
In this study, we conducted two surveys in the central and southern parts of the South China Sea, in autumn 2012 and spring 2013. Six juvenile tuna species were caught in each survey. Gradient forest analysis (GFA) and a generalized additive model (GAM) were used to analyze the relationship between the catch per unit effort (CPUE) for the juvenile tuna species and six sea temperature indices for the South China Sea. In the GFA, the temperature difference between the sea surface and 50 m depth (D50) showed the highest importance to CPUE than other indices, which indicates that D50 was the best predictor of the abundance of juvenile tuna species. The GAM analysis showed that lower deep-water temperature, a shallow mixed layer depth, and a higher difference in temperature between the surface and deeper water were associated with increased CPUE. The results indicate that a relatively rapid decrease in vertical water temperature is favorable for the aggregation of juvenile tuna. These results contribute to understanding of the distribution mechanism of juvenile tuna species in the South China Sea and provide a scientific basis for the rational development and utilization of tuna resources.

The alteration of the expression level of neuropathy target esterase in human neuroblastoma SK-N-SH cells disrupts cellular phospholipids homeostasis - Wei-Yuan Hou; Xiaohua Song; Yuzhen Wang; Pingan Chang; Rui Chen; Yi-Jun Wu (Toxicology in Vitro, 2023)

The effects of salt flow on the cross-section restoration of salt-bearing fold-and-thrust belts: An example from the Kuqa depression - Wanhui He; Wei Wang; Huiwen Xie; Hongwei Yin; Dong Jia; Zhenping Xu; Haoyu Luo; Rui Yuan (Journal of Structural Geology, 2023)

MiR-130/SNAP-25 axis regulate presynaptic alteration in anterior cingulate cortex involved in lead induced attention deficits - Tao Wang; Rui-Li Guan; Yun-Feng Zou; Gang Zheng; Xue-Feng Shen; Zi-Peng Cao; Rui-Hua Yang; Ming-Chao Liu; Ke-Jun Du; Xue-Hang Li; Michael Aschner; Ming-Gao Zhao; et al. (Journal of Hazardous Materials, 2023)

Antimicrobial activity and mechanism of preservatives against Alicyclobacillus acidoterrestris and its application in apple juice - Zhouli Wang; Yu Tian; Qi Wang; Tianmin Guo; Yahong Yuan; Tianli Yue; Hang Jia; Qian Ge; Zidan Zhao; Rui Cai (International Journal of Food Microbiology, 2023)

Estimating the magnitude of early Permian relative sea-level changes in southern North China - Rui Ma; Jianghai Yang; Yuan Wang; Jiaxin Yan; Jia Liu (Global and Planetary Change, 2023)

Long-term exposure to ambient particulate matter and kidney function in older adults - Yingxin Li; Xueli Yuan; Jing Wei; Yuanying Sun; Wenqing Ni; Hongmin Zhang; Yan Zhang; Rui Wang; Ruijun Xu; Gongbo Chen; Yuewei Liu; Jian Xu (Atmospheric Environment, 2023)

Research on Multi-Objective Energy Efficiency Optimization Method of Ships Considering Carbon Tax - Yupeng Yuan; Xiaoyu Wang; Liang Tong; Rui Yang; Boyang Shen (Journal of Marine Science and Engineering, 2023)
Various measures have been taken to improve ship energy efficiency while decreasing CO2 emissions. In this work, the navigation environment between Wuhan and Shanghai in China has been classified based on an improved K-means algorithm in order to realize route division. A fuel consumption prediction model considering the navigation environment factors has been established. Consequently, speed optimization models with multiple different optimization objectives have been constructed and tested based on an actual case using an artificial fish swarm algorithm. Finally, sensitivity analysis has been carried out focusing on the navigation time, fuel price, charter rate, free carbon credits, and carbon tax rate. The results show that the total shipping cost and CO2 emissions could be reduced by 0.94% and 0.38%, respectively, after the optimization. Considering a carbon tax policy with a tax rate of roughly 1300 RMB/t, the optimization result (including the carbon tax cost) is close to the compromised solution of multi-objective optimization, and the corresponding carbon tax rate can provide a useful reference for policymakers.

Calculation method and mechanism of ultimate side resistance of screw pile - Hong-wei Ma; Li Liu; Peng Wang; Song Yuan; Qing-rui He; Xiao-li Yang (Marine Georesources & Geotechnology, 2023)

Development of a recombinant adenovirus-vectored vaccine against both infectious hematopoietic necrosis virus and infectious pancreatic necrosis virus in rainbow trout (Oncorhynchus mykiss) - Shouhu Li; Xincang Li; Rui Yuan; Xiaoxue Chen; Shouxu Chen; Yu Qiu; Qingfeng Yang; Meng Wang; Jiangao Shi; Shuo Zhang (Fish & Shellfish Immunology, 2023)

Interfacial modulation of organic-inorganic two-dimensional superlattices for efficient electromagnetic wave absorption - Wenjian Wang; Ke Ran; Xingwang Hou; Yilin Huang; Zidong Zhang; Dongxu He; Yuan Fang; Shuai Wang; Yu Liu; Rui Zhao; Xiao-Yu Yang; Weidong Xue (Chemical Engineering Journal, 2023)

Ulva prolifera polysaccharide enhances the root colonisation by Bacillus amyloliquefaciens strain Cas02 - Depeng Chu; Xiaoqiang Wang; Jiajun Fan; Lijuan Peng; Jinchang Liang; Yanfen Zheng; Rui Wang; Xiangwei You; Changliang Jing; James Clark; Yiqiang Li; Yuan Yuan (Carbohydrate Polymers, 2023)

LncRNA as potential biomarker and therapeutic target in glioma - Xun Xu; Yuan Liang; Ilgiz Gareev; Yanchao Liang; Rui Liu; Ning Wang; Guang Yang (Molecular Biology Reports, 2023)

Receptor and Ionic Mechanism of Histamine on Mouse Dorsolateral Striatal Neurons - Jian-Ya Peng; Kang-Li Shen; Xiu-Juan Fan; Zeng-Xin Qi; Hui-Wei Huang; Jian-Lan Jiang; Jian-Hua Lu; Xiao-Qin Wang; Xiao-Xia Fang; Wang-Rui Yuan; Qiao-Xuan Deng; Shu Chen; et al. (Molecular Neurobiology, 2023)

Occurrence, correlation, and partitioning of organophosphate esters in soil and tree bark from a megacity, Western China - Can Wang; Rui-Yu Yuan; Shi-Qiang Wei; Ming-Jing He (Environmental Science and Pollution Research, 2023)

Development, characterisation, and in vitro anti-tumor effect of self-microemulsifying drug delivery system containing polyphyllin I - Xin Wang; Rui Zhang; Shu Wang; Minju Gu; Yuan Li; Xiuping Zhuang; Chao Chen; Peimin Yang; Gongling Guo; Ping Sun (Drug Delivery and Translational Research, 2023)

Modification of TiO2 by Er3+ and rGO enhancing visible photocatalytic degradation of arsanilic acid - Xinghao Ren; Hang Yao; Rui Tang; Rong A; Shoujun Yuan; Wei Wang; Ibrahim Mohamed Ali; Zhen-Hu Hu (Environmental Science and Pollution Research, 2022)

Efficacy and Safety of Recombinant Human Prourokinase in Acute Ischemic Stroke: A Phase IIa Randomized Clinical Trial - Haiqing Song; Yuan Wang; Qingfeng Ma; Huisheng Chen; Bo Liu; Yi Yang; Jianguo Zhu; Shigang Zhao; Xiaoping Jin; Yongqiu Li; Yanyong Wang; Runxiu Zhu; et al. (Translational Stroke Research, 2022)

GITRL impairs the immunosuppressive function of MDSCs via PTEN-mediated signaling pathway in experimental Sjögren syndrome - Jie Tian; Beibei Zhang; Qingfang Yuan; Xueqing Sun; Na Peng; Bo Zhu; Chang Liu; Xiaoran Wang; Man Han; Meng Cao; Fan Xiao; Shengjun Wang; et al. (Inflammation Research, 2022)

Conodont Biostratigraphic Constraint on the Lower Taiyuan Formation in Southern North China and Its Paleogeographic Implications - Yuan Wang; Jianghai Yang; Dong-Xun Yuan; Jia Liu; Rui Ma (Journal of Earth Science, 2022)

MicroRNA alteration in cerebrospinal fluid from comatose patients with traumatic brain injury after right median nerve stimulation - Ying Jia; Yi-fan He; Ye Tian; Yuan-zhi Wang; Rui-ting Zhao; Xiao-chun Li; Jian Sun; Ying-sheng Wei; Shuo An; Heng-jie Yuan; Chun-xiao Wan; Rong-cai Jiang (Experimental Brain Research, 2022)

The effects of dietary fermented wheat bran polysaccharides on mucosal and serum immune parameters, hepatopancreas antioxidant indicators, and immune-related gene expression of common carp (Cyprinus carpio) juveniles - Rui-Fang Wang; Yuan Wang; Jun Zhang; Mei-Qi Weng; Yu-Hui Liu; Qiu-Yan Cheng; Min Song; Yan-Ping Yang; Xiao-Ping An; Jing-Wei Qi (Aquaculture International, 2022)

RIG-I acts as a tumor suppressor in melanoma via regulating the activation of the MKK/p38MAPK signaling pathway - Rui Guo; Shun-Yuan Lu; Jin-Xia Ma; Qian-Lan Wang; Lu Zhang; Ling-Yun Tang; Yan Shen; Chun-Ling Shen; Jin-Jin Wang; Li-Ming Lu; Zhu-Gang Wang; Hong-Xin Zhang (Human Cell, 2022)
Studies have indicated that RIG-I may act as a tumor suppressor and participate in the tumorigenesis of some malignant diseases. However, RIG-I induces distinct cellular responses via different downstream signaling pathways depending on the cell type. To investigate the biological function and underlying molecular mechanism of RIG-I in the tumorigenesis of melanoma, we constructed RIG-I knockout, RIG-I -overexpressing B16-F10 and RIG-I knockdown A375 melanoma cell lines, and analyzed the RIG-I-mediated change in the biological behavior of tumor cells in spontaneous and poly (I:C)-induced RIG-I activation. Cell proliferation, cell cycling, apoptosis and migration were detected by CCK-8 assay, BrdU incorporation assay, Annexin V–PI staining assay and Transwell assay, respectively. In vivo tumorigenicity was evaluated by tumor xenograft growth in nude mice and subsequently by Ki67 staining and TUNEL assays. Furthermore, Western blotting was utilized to explore the underlying mechanism of RIG-I in melanoma cells. Our data showed that RIG-I promotes apoptosis and inhibits proliferation by G1 phase cell cycle arrest in the melanoma cell lines. Mechanistically, RIG-I induced the phosphorylation of p38 MAPK and MAPK kinases MKK3 and MKK4. In conclusion, the current study demonstrated that RIG-I suppressed the development of melanoma by regulating the activity of the MKK/p38 MAPK signaling pathway, which is relevant to research on novel therapeutic targets for this malignant disease.

Thermal crosslinking synthesis of ethylene–vinyl acetate copolymer supported floating TiO2 photocatalyst: characterization and photocatalytic performance - Qiang Wu; Jizhong Meng; Hang Yao; Rui Tang; Shoujun Yuan; Yulan Wang; Wei Wang; Haiping Luo; Zhen-Hu Hu (Environmental Science and Pollution Research, 2022)

Reduction the contamination of patulin during the brewing of apple cider and its characteristics - Zhouli Wang; Leran Wang; Qiaoying Ming; Tianli Yue; Qian Ge; Yahong Yuan; Zhenpeng Gao; Rui Cai (Food Additives & Contaminants: Part A, 2022)

Erratum to: Generating broad-spectrum tolerance to ALS-inhibiting herbicides in rice by base editing - Rui Zhang; Sha Chen; Xiangbing Meng; Zhuangzhuang Chai; Delin Wang; Yuge Yuan; Kunling Chen; Linjian Jiang; Jiayang Li; Caixia Gao (Science China Life Sciences, 2022)

Combining leaf fluorescence and active canopy reflectance sensing technologies to diagnose maize nitrogen status across growth stages - Rui Dong; Yuxin Miao; Xinbing Wang; Fei Yuan; Krzysztof Kusnierek (Precision Agriculture, 2022)

Analyzing the mechanism of nitrous oxide production in aerobic phase of anoxic/aerobic sequential batch reactor from the perspective of key enzymes - Rui Yang; Lin-jiang Yuan; Ru Wang; Zhi-xian He; Lin Lei; Yan-chen Ma (Environmental Science and Pollution Research, 2022)

Application of nanostructures as antimicrobials in the control of foodborne pathogen - Yu Tian; Rui Cai; Tianli Yue; Zhenpeng Gao; Yahong Yuan; Zhouli Wang (Critical Reviews in Food Science and Nutrition, 2022)

Two new dammarane-type triterpenoids from the green walnut husks of Juglans mandshurica Maxim - Yuan-Yuan Zhou; Hui-Rui Gao; Hong-Juan Song; Dan-Da Ma; Xiao-Juan Zhang; Yan-Ping Sun; Yan Liu; Xiao-Li Wang; Bing-You Yang; Hai-Xue Kuang (Natural Product Research, 2022)

Chrysomutanin and related meroterpenoids from a DES mutant of the marine-derived fungus Penicillium chrysogenum S-3-25 - Hua Qiao; Shu-Hua Zhang; Yuan Dong; Yu Yang; Rui Xu; Bo Chen; Yi Wang; Tian-Jiao Zhu; Cheng-Bin Cui; Guo-Gang Zhang; Chang-Wei Li (Natural Product Research, 2022)

AT1 Receptors: Their Actions from Hypertension to Cognitive Impairment - Hanxue Wu; Qi Sun; Shenglan Yuan; Jiawei Wang; Fanni Li; Hongli Gao; Xingjuan Chen; Rui Yang; Jiaxi Xu (Cardiovascular Toxicology, 2022)

Glacier lanternfish (Benthosema glaciale) first found on the continental slope of the Pacific Arctic - Ran Zhang; Yuan Li; Qiaohong Liu; Puqing Song; Hai Li; Rui Wang; Shaoxiong Ding; Longshan Lin (Polar Biology, 2022)

QTL mapping and candidate gene prediction for fiber yield and quality traits in a high-generation cotton chromosome substitution line with Gossypium barbadense segments - Quanwei Lu; Pengtao Li; Rui Yang; Xianghui Xiao; Ziyin Li; Qiuyu Wu; Juwu Gong; Qun Ge; Aiying Liu; Shengli Du; Jundi Wang; Yuzhen Shi; et al. (Molecular Genetics and Genomics, 2022)

Study on mechanical properties and damage mechanism of strongly weathered gneiss under freeze–thaw cycles - Xianghui Deng; Yu Zhang; Rui Wang; Dongyang Yuan (Arabian Journal of Geosciences, 2022)

Plant growth‐promoting and antibacterial activities of cultivable bacteria alive in tobacco field against Ralstonia solanacearum - Wenfang Yuan; Song Ruan; Gaofu Qi; Rui Wang; Xiuyun Zhao (Environmental Microbiology, 2022)
Summary Bacterial wilt disease caused by Ralstonia solanacearum leads to decrease of crops yield. Investigation of cultivable bacteria diversity provides more microbial species for screening antagonistic bacteria. In the present study, a variety of cultivation methods were used to investigate the diversity of cultivable bacteria alive in tobacco field. A total of 441 bacterial strains were obtained that belonged to four phyla, 49 genera and 146 species. Actinobacteria and Proteobacteria were the dominant phyla. Agrobacterium , Arthrobacter , Bacillus , Klebsiella , Paenarthrobacter , Pseudomonas and Pseudarthrobacter were the dominant genera. Some rare genera were discovered including Bosea , Cedecea , Delftia and Dyella . Diversity, species and abundances of bacteria altered under different cultivation conditions. One hundred three bacterial strains showed plant growth‐promoting attributes. Twenty Bacillus strains showed high antibacterial activity against R. solanacearum . In field experiments, individual strain and consortia of Bacillus subtilis , B. siamensis and B. vallismortis effectively inhibited bacterial wilt. The core genes that controlled synthesis of secondary metabolites were knocked out in B. vallismortis SSB‐10. Difficidin, which was synthesized by dif operon and controlled by sfp gene, was the antibacterial substance produced by SSB‐10. Difficidin destroyed cell wall and cell membrane of R. solanacearum and inhibited its motility, production of extracellular polysaccharides and cellulase activity.

Spatio-temporal characteristics of demersal fish community in the Chukchi and northern Bering Seas: significant distributional records and interannual variations in species composition and biodiversity - Ran Zhang; Puqing Song; Hai Li; Rui Wang; Yuan Li; Xing Miao; Longshan Lin; Shaoxiong Ding (Polar Biology, 2022)

Prediction of the electromagnetic responses of geological bodies based on a temporal convolutional network model - Chongxin Yuan; Xuben Wang; Fei Deng; Kunpeng Wang; Rui Yang (Acta Geophysica, 2022)

Secondary metabolites isolated from Agrimonia pilosa Ledeb. - Hong-Rui Li; Yu-Kui Li; Jian Xiao; Cui Yang; Meng-Yuan Jiang; Kai Tian; Wei Wang; Yan-Hong Li; Xiang-Zhong Huang (Natural Product Research, 2022)

Peripheral Administration of an Opioid Peptide Analog Ameliorates Morphine-Produced Hyperalgesia in a Spared Nerve Injury Model - Yuan Wang; Meng-tao Ma; Jing Wang; Chao-zhen-yi Han; Kai Li; Qiao-min Ru; Na Li; Xin Liu; Rui Wang (International Journal of Peptide Research and Therapeutics, 2022)

An Integrated, Size-Structured Stock Assessment of Antarctic Krill, Euphausia superba - Rui Wang; Puqing Song; Yuan Li; Longshan Lin (Frontiers in Marine Science, 2021)
The Antarctic krill ( Euphausia superba ) fishery is the largest fishery in the Southern Ocean, and it has been operating for over 45 years. In the past decade, the spatial distribution of the krill fishery has focused on the Bransfield Strait off the Antarctic Peninsula (subarea 48.1). However, the high fishing effort and climate change have placed great pressure on krill resources in this region, and conservation concerns have been raised. Because aging krill is difficult and uncertain, we developed an integrated size-structured model to estimate the fishing mortality, recruitment and spawning biomass of krill. The results indicated that in 1992–2011, the average spawning biomass of krill ranged from 1.14 × 10 6 to 1.45 × 10 6 tons, the estimated biomass of the maximum sustainable yield (BMSY) ranged from 3.96 × 10 5 to 4.90 × 10 5 tons and the estimated average recruitment ranged from 2.3 × 10 12 to 5.03 × 10 12 individuals in the research area. We explored the effect of different data weighting schemes for the length data on the assessment output. However, our estimates also have uncertainties. In addition, an attempt was made to analyze the correlation between model-estimated recruitment and mature biomass with climate change. Future stock assessments of krill resources should be comprehensive and multimethod, and the management of krill resources should be based on science that considers the demand of fishing communities and ecosystem protection.

A New Instrumental Array in Sichuan, China, to Monitor Vibrations and Perturbations of the Lithosphere, Atmosphere, and Ionosphere - Chieh-Hung Chen; Yang-Yi Sun; Kai Lin; Chen Zhou; Rui Xu; Haiyin Qing; Yongxin Gao; Tao Chen; Fei Wang; Huaizhong Yu; Peng Han; Chi-Chia Tang; et al. (Surveys in Geophysics, 2021)

Loganin ameliorates depression-like behaviors of mice via modulation of serotoninergic system - Chen-Hao Pan; Cong-Yuan Xia; Yu Yan; Yan Han; Rui Shi; Jun He; Ze-Xing Wang; Yu-Ming Wang; Wei-Ku Zhang; Jie-Kun Xu (Psychopharmacology, 2021)

Association between ambient air pollution and multiple sclerosis: a systemic review and meta-analysis - Chao Tang; Qing-Ru Li; Yan-Mei Mao; Yuan-Rui Xia; Heng-Sheng Guo; Jun-Ping Wang; Zong-Wen Shuai; Dong-Qing Ye (Environmental Science and Pollution Research, 2021)

Generating broad-spectrum tolerance to ALS-inhibiting herbicides in rice by base editing - Rui Zhang; Sha Chen; Xiangbing Meng; Zhuangzhuang Chai; Delin Wang; Yuge Yuan; Kunling Chen; Linjian Jiang; Jiayang Li; Caixia Gao (Science China Life Sciences, 2021)

Genetic control of Fusarium head blight resistance in two Yangmai 158-derived recombinant inbred line populations - Haisheng Yan; Guoqiang Li; Jinxing Shi; ShunShun Tian; Xiaoqiu Zhang; Rui Cheng; Xin Wang; Yang Yuan; Shouyang Cao; Jiyang Zhou; Zhongxin Kong; Haiyan Jia; et al. (Theoretical and Applied Genetics, 2021)

Elevation of GhDREB1B transcription by a copy number variant significantly improves chilling tolerance in cotton - Yanan Wang; Yuan Wang; Zhigang Meng; Yunxiao Wei; Xiongming Du; Chengzhen Liang; Rui Zhang (Planta, 2021)

Expanding our understanding of marine viral diversity through metagenomic analyses of biofilms - Wei Ding; Ruojun Wang; Zhicong Liang; Rui Zhang; Pei-Yuan Qian; Weipeng Zhang (Marine Life Science & Technology, 2021)

Comparison of different sampling strategies for debris flow susceptibility mapping: A case study using the centroids of the scarp area, flowing area and accumulation area of debris flow watersheds - Rui-yuan Gao; Chang-ming Wang; Zhu Liang (Journal of Mountain Science, 2021)

Comparative Transcriptomic Analyses of Haemophilus parasuis Reveal Differently Expressed Genes among Strains with Different Virulence Degrees - Yuan Y. Zhou; Chao Wang; Jing Yuan; Rong L. Yin; Xin Chen; Rui Li; Xue L. Zhang; Jing Wang; Chen Huang; Rong H. Yin (Current Microbiology, 2021)

Polymorphisms in the DC-SIGN gene and their association with the severity of hand, foot, and mouth disease caused by enterovirus 71 - Ya-Ping Li; Mu-Qi Wang; Chen-Rui Liu; Hui-Ling Deng; Yuan Wu; Shuang-Suo Dang; Li-Hong Xu (Archives of Virology, 2021)

Fracture characterization in oil-based mud boreholes using image logs: example form tight sandstones of Lower Cretaceous Bashijiqike Formation of KS5 well area, Kuqa Depression, Tarim Basin, China - Rui Yuan; Denglin Han; Yangang Tang; Hongxing Wei; Tao Mo; Chenchen Wang (Arabian Journal of Geosciences, 2021)

Phytochemical constituents, chemotaxonomic significance and anti-arthritic effect of Eucommia ulmoides Oliver staminate flowers - Rui Li; Lanlan Nie; Qing Wang; Danwei Ouyang; Lei Zhang; Ying Yuan; Yanlong Hong; Jianying Wang; Xiao Hu (Natural Product Research, 2020)

Gas Reservoir Characterization Using Lp-Norm Constrained High-Resolution Seismic Spectral Attributes - Tieyi Wang; Sanyi Yuan; Rui Wang; Shan Yang; Shangxu Wang (Pure and Applied Geophysics, 2020)

Prevalence of Clonorchis sinensis infection in fish in South‐East Asia: A systematic review and meta‐analysis - Ying Zhang; Qing‐Long Gong; Qing‐Bo Lv; Yang‐Yuan Qiu; Yan‐Chun Wang; Hong‐Yu Qiu; Xin‐Rui Guo; Jun‐Feng Gao; Qiao‐Cheng Chang; Chun‐Ren Wang (Journal of Fish Diseases, 2020)
Clonorchis sinensis , an important fish‐borne zoonotic trematode, is widely distributed in South‐East Asia, especially in China. Infections from human and animal reservoir hosts occur due to the consumption of raw or undercooked fish with C. sinensis metacercariae. This study aimed to evaluate the prevalence of C. sinensis metacercariae in fish in South‐East Asia via systematic review and meta‐analysis. We searched PubMed, ScienceDirect, China National Knowledge Infrastructure, Wanfang and Chongqing VIP databases for studies published between 1976 and 2020 that are related to the prevalence of C. sinensis metacercariae in fish. Studies were screened with keywords based on inclusion and exclusion criteria. Seventy‐one eligible articles were identified, covering three countries: China, Korea and Vietnam. The pooled prevalence of C. sinensis metacercariae in fish from South‐East Asia was 30.5%, with 35.1% in China, 29.7% in Korea and 8.4% in Vietnam. In subgroup analyses of climate, season, water source and publication date, the highest prevalence was identified in the Dwb climate type (43.3%), summer (70.2%), river (34.5%) and pre‐2001 publications (38.9%), respectively. In comparison, the lowest prevalence was found in the Dfa climate type (14.5%), winter (19.5%), lake (8.0%) and post‐2001 publications (23.8%). Meta‐regression results indicated that country ( p = .009), the published time ( p = .035) and water source subgroups ( p = .003) may be the source of heterogeneity. Overall, our study indicates that a high prevalence of C. sinensis infections occurs in fish in China, Korea and Vietnam, illuminating a significant public health concern in these countries.

Multi-AUVs Cooperative Target Search Based on Autonomous Cooperative Search Learning Algorithm - Yuan Liu; Min Wang; Zhou Su; Jun Luo; Shaorong Xie; Yan Peng; Huayan Pu; Jiajia Xie; Rui Zhou (Journal of Marine Science and Engineering, 2020)
As a new type of marine unmanned intelligent equipment, autonomous underwater vehicle (AUV) has been widely used in the field of ocean observation, maritime rescue, mine countermeasures, intelligence reconnaissance, etc. Especially in the underwater search mission, the technical advantages of AUV are particularly obvious. However, limited operational capability and sophisticated mission environments are also difficulties faced by AUV. To make better use of AUV in the search mission, we establish the DMACSS (distributed multi-AUVs collaborative search system) and propose the ACSLA (autonomous collaborative search learning algorithm) integrated into the DMACSS. Compared with the previous system, DMACSS adopts a distributed control structure to improve the system robustness and combines an information fusion mechanism and a time stamp mechanism, making each AUV in the system able to exchange and fuse information during the mission. ACSLA is an adaptive learning algorithm trained by the RL (Reinforcement learning) method with a tailored design of state information, reward function, and training framework, which can give the system optimal search path in real-time according to the environment. We test DMACSS and ACSLA in the simulation test. The test results demonstrate that the DMACSS runs stably, the search accuracy and efficiency of ACSLA outperform other search methods, thus better realizing the cooperation between AUVs, making the DMACSS find the target more accurately and faster.

Evaluating Spatial Heterogeneity of Land Surface Hydrothermal Conditions in the Heihe River Basin - Yuan Zhang; Shaomin Liu; Xiao Hu; Jianghao Wang; Xiang Li; Ziwei Xu; Yanfei Ma; Rui Liu; Tongren Xu; Xiaofan Yang (Chinese Geographical Science, 2020)

The abscisic acid receptor gene VvPYL4 positively regulates grapevine resistance to Plasmopara viticola - Li Liu; Chang-Yuan Liu; Hui Wang; Shu-Yi Yu; Tian-Shu Guan; Yu-Fei Huang; Rui-Chun Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Ablation of olfactory bulb glutamatergic neurons induces depressive-like behaviors and sleep disturbances in mice - Mao-Yun Yuan; Ze-Ka Chen; Jian Ni; Tian-Xiao Wang; Shi-Yu Jiang; Hui Dong; Wei-Min Qu; Zhi-Li Huang; Rui-Xi Li (Psychopharmacology, 2020)

α -Tetralone glycosides from the green walnut husks of Juglans mandshurica Maxim. and their cytotoxic activities - Yuan-Yuan Zhou; Shuang Guo; Ying Wang; Hong-Juan Song; Hui-Rui Gao; Xiao-Juan Zhang; Yan-Ping Sun; Yan Liu; Bing-You Yang; Hai-Xue Kuang (Natural Product Research, 2020)

Moderate parasitoidism on pollinators contributes to population oscillations and increases species diversity in the fig-fig wasp community - Lin Wang; Li-Yuan Yang; Feng Zhang; Rui-Wu Wang (Theoretical Ecology, 2020)

Tracing solute sources and carbon dynamics under various hydrological conditions in a karst river in southwestern China - Jing Liu; Bo Chen; Zhu-Yan Xu; Yuan Wei; Zhi-Hua Su; Rui Yang; Yong-Xue Ji; Xiao-Dan Wang; Li-Li Zhang; Ning An; Fei Yang (Environmental Science and Pollution Research, 2020)

Separating and imaging diffractions in dip domain on the basis of slope analysis - Xue Kong; De-Ying Wang; Zhen-Chun Li; Rui-Xiang Zhang; Qiu-Yuan Hu (Applied Geophysics, 2020)

Stimulation of heterotrophic nitrification and N2O production, inhibition of autotrophic nitrification in soil by adding readily degradable carbon - Ting Lan; Rui Liu; Helen Suter; Ouping Deng; Xuesong Gao; Ling Luo; Shu Yuan; Changquan Wang; Deli Chen (Journal of Soils and Sediments, 2020)

Preparation and In vitro Evaluation of FDM 3D-Printed Ellipsoid-Shaped Gastric Floating Tablets with Low Infill Percentages - Di Chen; Xiang-Yu Xu; Rui Li; Gen-Ao Zang; Yue Zhang; Ming-Rui Wang; Meng-Fei Xiong; Jia-Rui Xu; Ting Wang; Hui Fu; Qin Hu; Bin Wu; et al. (AAPS PharmSciTech, 2020)

Re-examining the role of ventral tegmental area dopaminergic neurons in motor activity and reinforcement by chemogenetic and optogenetic manipulation in mice - Man-Yi Jing; Xiao Han; Tai-Yun Zhao; Zhi-Yuan Wang; Guan-Yi Lu; Ning Wu; Rui Song; Jin Li (Metabolic Brain Disease, 2019)

Design and synthesis of organic rectorite-based composite nanofiber membrane with enhanced adsorption performance for bisphenol A - Zhiming Sun; Fang Yuan; Xinchao Zhang; Rui Zhu; Xinyi Shen; Bingyan Sun; Bin Wang (Environmental Science and Pollution Research, 2019)

A new triterpene from the green walnut husks of Juglans mandshurica Maxim - Yuan-Yuan Zhou; Hong-Juan Song; Shuang Guo; Ying Wang; Hui-Rui Gao; Xiao-Juan Zhang; Yan-Ping Sun; Yan Liu; Bing-You Yang; Hai-Xue Kuang (Journal of Natural Medicines, 2019)

Metabolomics reveals the drought-tolerance mechanism in wild soybean (Glycine soja) - Xiaoxia Wang; Rui Guo; Mingxia Li; Yuan Liu; Mingli Zhao; Hui Fu; Xueying Liu; Shiyao Wang; Lianxuan Shi (Acta Physiologiae Plantarum, 2019)

Complete mitochondrial genome of a kind of snakehead fish Channa siamensis and its phylogenetic consideration - Rui Li; Gang Wang; Zheng-Yong Wen; Yuan-Chao Zou; Chuan-Jie Qin; Yu Luo; Jun Wang; Gui-Hong Chen (Genes & Genomics, 2019)

Using multiple superpixel segmentation and merging of digital image method to auto-estimate gravel grain size - Chao Wang; Rui Yuan; Yuqiu Sun; Changsheng Chen; Huimin Zhang (Arabian Journal of Geosciences, 2019)

Development of polymorphic microsatellite loci for Ceratosolen gravelyi (Hymenoptera: Agaonidae), the pollinating wasp of Ficus semicordata (Urticales: Moraceae) - Li-Yuan Yang; Ai-Ying Wang; Zhu-Zeng Huang; Rui-Wu Wang; Da-Yong Zhang (Applied Entomology and Zoology, 2019)

Isolation and characterization of mineral-dissolving bacteria from different levels of altered mica schist surfaces and the adjacent soil - Yuan Li Wang; Qi Wang; Rui Yuan; Xia Fang Sheng; Lin Yan He (World Journal of Microbiology and Biotechnology, 2019)

MiR-429 improved the hypoxia tolerance of human amniotic cells by targeting HIF-1α - Lihao Ge; Yuyan Wang; Yang Cao; Gang Li; Rui Sun; Peng Teng; Yansong Wang; Yunlong Bi; Zhanpeng Guo; Yajiang Yuan; Deshui Yu (Biotechnology Letters, 2018)

Identification of the complete mitochondrial genome of Garra pingi pingi (Cypriniformes, Cyprinidae) - Yuan-Chao Zou; Mei Chen; Chuan-Jie Qin; Yong-Ming Wang; Rui Li; Ze-Min Qi; Zheng-Yong Wen (Conservation Genetics Resources, 2018)

Carbon pools and fluxes in the China Seas and adjacent oceans - Nianzhi Jiao; Yantao Liang; Yongyu Zhang; Jihua Liu; Yao Zhang; Rui Zhang; Meixun Zhao; Minhan Dai; Weidong Zhai; Kunshan Gao; Jinming Song; Dongliang Yuan; et al. (Science China Earth Sciences, 2018)

Utilizing skew normal distribution to unmix grain-size distribution of swampy lakeshore: example from Lake Ulungur, China - Rui Yuan; Changmin Zhang; Xulong Wang; Rui Zhu (Arabian Journal of Geosciences, 2018)

The role of autophagy in pulmonary hypertension: a double-edge sword - Rui Chen; Meiping Jiang; Bo Li; Wei Zhong; Zhongqun Wang; Wei Yuan; Jinchuan Yan (Apoptosis, 2018)

SNAI1, an endothelial–mesenchymal transition transcription factor, promotes the early phase of ocular neovascularization - Jia-Xing Sun; Tian-Fang Chang; Man-Hong Li; Li-Juan Sun; Xian-Chun Yan; Zi-Yan Yang; Yuan Liu; Wen-Qin Xu; Yang Lv; Jing-Bo Su; Liang Liang; Hua Han; et al. (Angiogenesis, 2018)

Comparative growth increments of gladius surface and cross-sections to estimate Sthenoteuthis oualaniensis age - Xue Feng Wang; Bi Lin Liu; Jian Hua Li; Rui Jiang; Jing Yuan Lin; Teng Li (Marine Biology, 2018)

Overexpression of Nogo receptor 3 (NgR3) correlates with poor prognosis and contributes to the migration of epithelial cells of nasopharyngeal carcinoma patients - Jiang-Yi He; Ping Han; Yu Zhang; Yong-Dong Liu; Shi-Jian Song; Guo-Kai Feng; Yu An; Ai-Jun Zhou; Hong-Bo Wang; Li Yuan; Zhi-Rui Lin; Tian-Liang Xia; et al. (Journal of Molecular Medicine, 2018)

CD137–CD137L interaction modulates neointima formation and the phenotype transformation of vascular smooth muscle cells via NFATc1 signaling - Wei Zhong; Bo Li; Ping Yang; Rui Chen; Cuiping Wang; Zhongqun Wang; Chen Shao; Wei Yuan; Jinchuan Yan (Molecular and Cellular Biochemistry, 2018)

Spatial trends and pollution assessment for mercury in the surface soils of the Nansi Lake catchment, China - Ming-Yi Ren; Li-Yuan Yang; Long-Feng Wang; Xue-mei Han; Jie-Rui Dai; Xu-Gui Pang (Environmental Science and Pollution Research, 2018)

The complete mitochondrial genome of a threatened loach (Beaufortia kweichowensis) and its phylogeny - Zheng-Yong Wen; Bi-Wen Xie; Chuan-Jie Qin; Jun Wang; Deng-Yue Yuan; Rui Li; Yuan-Chao Zou (Conservation Genetics Resources, 2017)

Genetic Diversity in Various Accessions of Pineapple [Ananas comosus (L.) Merr.] Using ISSR and SSR Markers - Jian-sheng Wang; Jun-hu He; Hua-rui Chen; Ye-yuan Chen; Fei Qiao (Biochemical Genetics, 2017)

Nominal effective immunoreaction volume of magnetic beads at single bead level - Rui Wang; Yuan Chen; Kai Fan; Feng Ji; Jian Wu; Yong-hua Yu (Journal of Zhejiang University-SCIENCE B, 2017)

Diffraction separation by plane-wave prediction filtering - Xue Kong; De-Ying Wang; Zhen-Chun Li; Rui-Xiang Zhang; Qiu-Yuan Hu (Applied Geophysics, 2017)

Occurrence and profiles of polybrominated diphenyl ethers (PBDEs) in riverine sediments of Shanghai: a combinative study with human serum from the locals - Ming-Hong Wu; Ben-Tuo Xu; Gang Xu; Ming-Nan Wang; Jing Ma; Chen-Yuan Pan; Rui Sun; Tao Han; Liang Tang (Environmental Geochemistry and Health, 2017)

The complete mitochondrial genome of a threatened loach (Sinibotia reevesae) and its phylogeny - Yuan-Chao Zou; Bi-Wen Xie; Chuan-Jie Qin; Yong-Ming Wang; Deng-Yue Yuan; Rui Li; Zheng-Yong Wen (Genes & Genomics, 2017)

Increased lateral root formation by CRISPR/Cas9-mediated editing of arginase genes in cotton - Yanling Wang; Zhigang Meng; Chengzhen Liang; Zhaohong Meng; Yuan Wang; Guoqing Sun; Tao Zhu; Yongping Cai; Sandui Guo; Rui Zhang; Yi Lin (Science China Life Sciences, 2017)

Land use legacies and nitrogen fertilization affect methane emissions in the early years of rice field development - Rui Shao; Ming Xu; Renqiang Li; Xiaoqin Dai; Lixiang Liu; Ye Yuan; Huimin Wang; Fengting Yang (Nutrient Cycling in Agroecosystems, 2017)

IP-10/CXCR3 Axis Promotes the Proliferation of Vascular Smooth Muscle Cells through ERK1/2/CREB Signaling Pathway - Hui-jin Wang; Yu Zhou; Rui-ming Liu; Yuan-sen Qin; Ying-huan Cen; Ling-yu Hu; Shen-ming Wang; Zuo-jun Hu (Cell Biochemistry and Biophysics, 2017)

Blood Flow and Oxygen Transport in Descending Branch of Lateral Femoral Circumflex Arteries After Transfemoral Amputation: A Numerical Study - Fei Yan; Wen-Tao Jiang; Rui-Qi Dong; Qing-Yuan Wang; Yu-Bo Fan; Ming Zhang (Journal of Medical and Biological Engineering, 2017)

Increasing the recovery of heavy metal ions using two microbial fuel cells operating in parallel with no power output - Xiaohui Wang; Jing Li; Zhao Wang; Hairti Tursun; Rui Liu; Yanmei Gao; Yuan Li (Environmental Science and Pollution Research, 2016)

Characterization and expression analyses of the H+-pyrophosphatase gene in rye - CHANG-SHUI WANG; QIAN-TAO JIANG; JIAN MA; XIU-YING WANG; JI-RUI WANG; GUO-YUE CHEN; PENG-FEI QI; YUAN-YING PENG; XIU-JIN LAN; YOU-LIANG ZHENG; YU-MING WEI (Journal of Genetics, 2016)

Lead Exposure Impairs Hippocampus Related Learning and Memory by Altering Synaptic Plasticity and Morphology During Juvenile Period - Tao Wang; Rui-Li Guan; Ming-Chao Liu; Xue-Feng Shen; Jing Yuan Chen; Ming-Gao Zhao; Wen-Jing Luo (Molecular Neurobiology, 2016)

Magnetic effervescent tablet-assisted ionic liquid dispersive liquid–liquid microextraction of selenium for speciation in foods and beverages - Xiaojun Wang; Long Wu; Jiaqi Cao; Xincheng Hong; Rui Ye; Weiji Chen; Ting Yuan (Food Additives & Contaminants: Part A, 2016)

A cell wall-bound anionic peroxidase, PtrPO21, is involved in lignin polymerization in Populus trichocarpa - Chien-Yuan Lin; Quanzi Li; Sermsawat Tunlaya-Anukit; Rui Shi; Ying-Hsuan Sun; Jack P. Wang; Jie Liu; Philip Loziuk; Charles W. Edmunds; Zachary D. Miller; Ilona Peszlen; David C. Muddiman; et al. (Tree Genetics & Genomes, 2016)

Synthesis, Luminescent Properties of aza-Boron-Diquinomethene Difluoride Complexes and Their Application for Fluorescent Security Inks - Long Gu; Rui Liu; Hong Shi; Qiang Wang; Guangliang Song; Xiaolin Zhu; Shidong Yuan; Hongjun Zhu (Journal of Fluorescence, 2016)

Two new eunicellin diterpenoids from the South China Sea gorgonian Muricella sibogae and their bioactivities - Xing-Wang Zhang; Xu-Li Tang; Hong-Rui Yuan; Dan-Qing Feng; Pei Su; Ping-Lin Li; Guo-Qiang Li (Natural Product Research, 2015)

Distribution of the Vrn-D1b allele associated with facultative growth habit in Chinese wheat accessions - Xian-rui Guo; Yuan-yuan Wang; Ling-zhi Meng; Hong-wei Liu; Li Yang; Yang Zhou; Hong-jun Zhang (Euphytica, 2015)

Endogenous level of TIGAR in brain is associated with vulnerability of neurons to ischemic injury - Lijuan Cao; Jieyu Chen; Mei Li; Yuan-Yuan Qin; Meiling Sun; Rui Sheng; Feng Han; Guanghui Wang; Zheng-Hong Qin (Neuroscience Bulletin, 2015)

Regulation of three isoforms of SOD gene by environmental stresses in citrus red mite, Panonychus citri - Ying-Cai Feng; Chong-Yu Liao; Wen-Kai Xia; Xuan-Zhao Jiang; Feng Shang; Guo-Rui Yuan; Jin-Jun Wang (Experimental and Applied Acarology, 2015)

Tree‐ring reconstruction of July–May precipitation ( AD 1816–2010) in the northwestern marginal zone of the East Asian summer monsoon reveals the monsoon‐related climate signals - Feng Chen; Huiqin Wang; Fa‐hu Chen; Yujiang Yuan; Rui‐bo Zhang (International Journal of Climatology, 2015)
A July–May precipitation reconstruction for the period AD 1816–2010 was developed from a tree‐ring width chronology of Picea wilsonii for the Xinglong Mountains area of Lanzhou. The reconstruction explains 55.8% of the actual precipitation variance during the calibration period from 1951 to 2010. Wet conditions prevailed during the periods 1822–1835, 1843–1858, 1870–1877, 1884–1891, 1911–1921, 1933–1938, 1944–1979 and 2009–2010. Dry episodes occurred during 1816–1821, 1836–1842, 1859–1869, 1878–1883, 1892–1910, 1922–1932, 1939–1943 and 1980–2008. Multi‐taper method spectral analysis indicates the existence of some significant peaks at 2.8, 3.0 and 3.5 years. Spatial correlations with gridded land surface precipitation data revealed that our reconstruction represents regional precipitation signal for a large area of North China linked to the East Asian summer monsoon (EASM). Comparison with other tree‐ring‐based precipitation/drought reconstructions from surrounding areas implies a high degree of confidence for our reconstruction. Precipitation variations in the study area are significantly correlated with sea surface temperatures in eastern equatorial Pacific Ocean and tropical western Pacific Ocean, suggesting a possible connection of regional precipitation variations to the EASM and the El Niño‐Southern Oscillation (ENSO).

Quantitative trait locus mapping for seed dormancy in different post-ripening stages in a Tibetan semi-wild wheat (Triticum aestivum ssp. tibetanum Shao) - Yun-Feng Jiang; Ji-Rui Wang; Wei Luo; Yu-Ming Wei; Peng-Fei Qi; Ya-Xi Liu; Qian-Tao Jiang; Yuan-Ying Peng; Guo-Yue Chen; Shou-Fen Dai; You-Liang Zheng; Xiu-Jin Lan (Euphytica, 2015)

GITRL as a genetic adjuvant enhances enterovirus 71 VP1 DNA vaccine immunogenicity - Jing Yuan; Xinyi Tang; Kai Yin; Jie Tian; Ke Rui; Jie Ma; Chaoming Mao; Jianguo Chen; Liwei Lu; Huaxi Xu; Shengjun Wang (Immunologic Research, 2015)

Tumor Necrosis Factor-Related Apoptosis Inducing Ligand Gene Polymorphisms are Correlated with Gastric Cancer in Central China - Changgao Wang; Shufang Xu; Fengming Yi; Xiaobing Wang; Yuan Lei; Sha Huang; Rui Zhou; Bing Xia (Pharmaceutical Research, 2015)

Contribution weight of engineering technology on pollutant emission reduction based on IPAT and LMDI methods - Hairti Tursun; Zhenyang Li; Rui Liu; Yuan Li; Xiaohui Wang (Clean Technologies and Environmental Policy, 2015)

Molecular cloning and expression analysis of mannose receptor in blunt snout bream (Megalobrama amblycephala) - Xiaoling Liu; Xiaocheng Tang; Li Wang; Jie Li; Hong Wang; Shun Wei; Rui Fang; Wei Ji; Gailing Yuan; Nan Chen; Zemao Gu; Xueqin Liu; et al. (Molecular Biology Reports, 2014)

Purification and photodynamic bioactivity of phycoerythrin and phycocyanin from Porphyra yezoensis Ueda - Chuner Cai; Yuan Wang; Chunxia Li; Ziye Guo; Rui Jia; Weining Wu; Yan Hu; Peimin He (Journal of Ocean University of China, 2014)

Down-regulated Six2 by knockdown of neurofibromin results in apoptosis of metanephric mesenchyme cells in vitro - Puhui Zhou; Tielin Chen; Yin Fang; Honglian Wang; Mi Li; Pengpeng Ma; Lu He; Qianyin Li; Tianming Liu; Xianggui Yang; Fang Nie; Xiaoyan Wang; et al. (Molecular and Cellular Biochemistry, 2014)

Isolation, culture, and characterization of primordial germ cells in Mongolian sheep - Chun Xia Liu; Wen Long Wang; Rui Yuan Zhao; Hai Tao Wang; Yi Yi Liu; Shen Yuan Wang; Huan Min Zhou (In Vitro Cellular & Developmental Biology - Animal, 2014)

Priming of Anti-Herbivore Defense in Tomato by Arbuscular Mycorrhizal Fungus and Involvement of the Jasmonate Pathway - Yuan Yuan Song; Mao Ye; Chuan You Li; Rui Long Wang; Xiao Chen Wei; Shi Ming Luo; Ren Sen Zeng (Journal of Chemical Ecology, 2013)

Structure and evolution of the mitochondrial genome of Exorista sorbillans: the Tachinidae (Diptera: Calyptratae) perspective - Yuan-jun Shao; Xian-qiong Hu; Guang-da Peng; Rui-xian Wang; Rui-na Gao; Chao Lin; Wei-de Shen; Rui Li; Bing Li (Molecular Biology Reports, 2012)

Postconditioning with vagal stimulation attenuates local and systemic inflammatory responses to myocardial ischemia reperfusion injury in rats - Qiang Wang; Yi Cheng; Fu-Shan Xue; Yu-Jing Yuan; Jun Xiong; Rui-Ping Li; Xu Liao; Jian-Hua Liu (Inflammation Research, 2012)

Does glyphosate impact on Cu uptake by, and toxicity to, the earthworm Eisenia fetida? - Chui-Fan Zhou; Yu-Jun Wang; Yuan-Chun Yu; Rui-Juan Sun; Xiang-Dong Zhu; Hai-Lin Zhang; Dong-Mei Zhou (Ecotoxicology, 2012)

CSMD1 exhibits antitumor activity in A375 melanoma cells through activation of the Smad pathway - Ming-Rui Tang; Yu-Xin Wang; Shu Guo; Si-Yuan Han; Di Wang (Apoptosis, 2012)

Haplotype variations of gene Ppd-D1 in Aegilops tauschii and their implications on wheat origin - Lin Huang; Qing Wang; Lian-Quan Zhang; Zhong-Wei Yuan; Ji-Rui Wang; Huai-Gang Zhang; You-Liang Zheng; Deng-Cai Liu (Genetic Resources and Crop Evolution, 2012)

Novel HMW glutenin genes from Aegilops tauschii and their unique structures - Wen-Jie Chen; Zhong-Wei Yuan; Lian-Quan Zhang; Xing Fan; Ze-Hong Yan; Ji-Rui Wang; You-Liang Zheng; Huai-Gang Zhang; Deng-Cai Liu (Genes & Genomics, 2012)

Gene expression profile of campylobacter jejuni-induced GBS in bama miniature pigs - Feng Xue; Dexin Zeng; Fei Xu; Rui Zhang; Yang Chen; Yuefei Yang; Xiaobo Wang; Zhenzhong Li; Xiaorong Zhang; Yuan Jiang (Cell and Tissue Research, 2012)

Analysis of 2,297 expressed sequence tags (ESTs) from a cDNA library of flax (Linum ustitatissimum L.) bark tissue - Song-Hua Long; Xin Deng; Yu-Fu Wang; Xiang Li; Rui-Qing Qiao; Cai-Sheng Qiu; Yuan Guo; Dong-Mei Hao; Wan-Qi Jia; Xin-Bo Chen (Molecular Biology Reports, 2012)

Gene expression profiling of Sinapis alba leaves under drought stress and rewatering growth conditions with Illumina deep sequencing - Cai-Hua Dong; Chen Li; Xiao-Hong Yan; Shun-Mou Huang; Jin-Yong Huang; Li-Jun Wang; Rui-Xing Guo; Guang-Yuan Lu; Xue-Kun Zhang; Xiao-Ping Fang; Wen-Hui Wei (Molecular Biology Reports, 2012)

Expression and Clinical Significance of CK19 and CK20 Expressions in Transverse Mesocolon Biopsies from Patients with Gastric Carcinoma - Guo-Rui Sun; Xiao-Yuan Dong; Qing-Si He; Hui Qu; Yan-Min Wang (Cell Biochemistry and Biophysics, 2012)

Chaiqin Chengqi Decoction decreases IL-6 levels in patients with acute pancreatitis - Ling Wang; Yuan Li; Qin Ma; Yong Liu; Yuan-yi Rui; Ping Xue; Zong-guang Zhou (Journal of Zhejiang University-SCIENCE B, 2011)

Induction of DIMBOA accumulation and systemic defense responses as a mechanism of enhanced resistance of mycorrhizal corn (Zea mays L.) to sheath blight - Yuan Yuan Song; Man Cao; Li Jun Xie; Xiao Ting Liang; Ren Sen Zeng; Yi Juan Su; Jing Hua Huang; Rui Long Wang; Shi Ming Luo (Mycorrhiza, 2011)

Organochlorine pesticides in the soil of a karst cave in Guilin, China - Yinghui Wang; Songjun Guo; Rui Xue; Shihua Qi; Yiyin Xu; Baoming Xue; Daoxian Yuan (Environmental Monitoring and Assessment, 2011)

Identification of a Novel Bacterial K+ Channel - Guanghua Tang; Bo Jiang; Yuan Huang; Ming Fu; Lingyun Wu; Rui Wang (The Journal of Membrane Biology, 2011)

A systemic proteomic analysis of Populus chloroplast by using shotgun method - Hong-Mei Yuan; Kai-Long Li; Rui-Juan Ni; Wen-Dong Guo; Zhuo Shen; Chuan-Ping Yang; Bai-Chen Wang; Gui-Feng Liu; Chang-Hong Guo; Jing Jiang (Molecular Biology Reports, 2011)

Cytosolic PrP Induces Apoptosis of Cell by Disrupting Microtubule Assembly - Xiao-Li Li; Gui-Rong Wang; Yuan-Yuan Jing; Ming-Ming Pan; Chen-Fang Dong; Rui-Min Zhou; Zhao-Yun Wang; Qi Shi; Chen Gao; Xiao-Ping Dong (Journal of Molecular Neuroscience, 2011)

A PKC-β inhibitor protects against cardiac microvascular ischemia reperfusion injury in diabetic rats - Liping Wei; Dongdong Sun; Zhiyong Yin; Yuan Yuan; Andrew Hwang; Yingmei Zhang; Rui Si; Rongqing Zhang; Wenyi Guo; Feng Cao; Haichang Wang (Apoptosis, 2010)

Bacterial communities in PAH contaminated soils at an electronic-waste processing center in China - Wen Zhang; Hui Wang; Rui Zhang; Xie-Zhi Yu; Pei-Yuan Qian; M. H. Wong (Ecotoxicology, 2010)

Liquefaction macrophenomena in the great Wenchuan earthquake - Longwei Chen; Xiaoming Yuan; Zhenzhong Cao; Longqing Hou; Rui Sun; Lin Dong; Weiming Wang; Fanchao Meng; Hongjuan Chen (Earthquake Engineering and Engineering Vibration, 2009)

Transformation of sugarcane with ACC oxidase antisense gene - Ai-Qin Wang; Wei-Qing Dong; Yuan-Wen Wei; Cheng-Mei Huang; Long-Fei He; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2009)

Expression of thyrotropin-releasing hormone receptors in rat testis and their role in isolated Leydig cells - Yong Zhao; Wu-Gang Hou; Hua-Ping Zhu; Jie Zhao; Rui-An Wang; Ruo-Jun Xu; Yuan-Qiang Zhang (Cell and Tissue Research, 2008)

Vesicular stomatitis virus matrix protein gene enhances the antitumor effects of radiation via induction of apoptosis - Xiao-Bo Du; Jin-Yi Lang; Jian-Rong XU; You Lu; Yan-Jun Wen; Ju-Mei Zhao; Peng Diao; Zhi-Ping Yuan; Bin Yao; Ling-Yu Fan; Guo-Qing Wang; Li Liu; et al. (Apoptosis, 2008)

The induction of growth arrest in fibroblasts by SV40 T antigen - Xinwen Wang; Yuan Liu; Rui Dong; Yan Jin (Molecular Biology Reports, 2006)

Identification and functional characterization of a leucine-rich repeat receptor-like kinase gene that is involved in regulation of soybean leaf senescence - Xiao-Ping Li; Rui Gan; Peng-Li Li; Yuan-Yuan Ma; Li-Wen Zhang; Ren Zhang; Yong Wang; Ning Ning Wang (Plant Molecular Biology, 2006)

Development of highly regenerable callus lines and Agrobacterium-mediated transformation of Chinese lawngrass (Zoysia sinica Hance) with a cold inducible transcription factor, CBF1 - Rui-fen Li; Jian-hua Wei; Hong-zhi Wang; Jie He; Zhen-yuan Sun (Plant Cell, Tissue and Organ Culture (PCTOC), 2006)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)